Enhancing sustainability in large-scale multi-microgrid systems: A framework for renewable integration and blockchain-enabled peer-to-peer energy trading - Thi Huynh Anh Le; Jatinder N.D. Gupta; Vincent F. Yu (Energy Policy, 2026)

Corrigendum to ‘Cyclosporine A protects against wasp venom-induced rhabdomyolysis in rats by inhibiting the CypD-mPTP pathway’ [Toxicon 281 (2026) 109187] - S. Li; F. Deng; C. Yang; S. Liu; J. Zhou; F. Guo; A. Yu; T. Zhang (Toxicon, 2026)

Results of synchronous lidar studies of atmospheric aerosol transport features in the coastal zone of Lake Baikal - S. V. Nasonov; Yu S. Balin; M. G. Klemasheva; G. P. Kokhanenko; A. S. Nasonova; M. M. Novoselov; I. E. Penner; T. F. Gazimov (Meteorology and Atmospheric Physics, 2026)

Ghost carbonate in Archean granitoids marks a geodynamic transition in the Mesoarchean - Ya-Wen Zhang; Shui-Jiong Wang; Hao Wang; Bin Su; Béatrice Luais; Yu Wang; Hui-Min Yu; Da Wang; Stephen F. Foley; Xian-Hua Li (Lithos, 2026)

Electrochemical detection of gallic acid using carboxylic acid-functionalized carbon black integrated with an iron disulfide nanocomposite for sensitive and selective analysis of natural food samples - Nithishkumar Marimuthu; Arunkumar Selvam; Huda F. Khalil; Mohammed M. Algaradah; Vairamuthu Raj; Chih-Yu Kuo; Mani Govindasamy (Food Chemistry, 2026)

Association of exposure to phthalates and substitutes with infection risk among U.S. children - Yu Zhang; Siqi Jin; Zichuan Li; Liang Wang; Mariana F. Fernández; Ainhoa Pérez-Cantero; Yang Sun; Yi-Xin Wang; Carmen Messerlian; Vicente Mustieles (Environmental Pollution, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

A Review of 35 Years in Developing Constitutive Models for the Callovo-Oxfordian Claystone Behavior - M. N. Vu; G. Armand; J. Talandier; C. Plua; M. Souley; J. F. Shao; Z. Yu; J. B. Colliat; J. Vaunat; A. Gens; S. Olivella; F. Collin; et al. (Rock Mechanics and Rock Engineering, 2026)

Oral Language Skills of Children and Adolescents with Neurofibromatosis Type 1: a Systematic Review and Meta-analysis - Liyan Yu; Dan Liu; Jonathan M. Payne; Heather L. Thompson; Xian Wu; Julia Moreira; Lauren Morey; Michael Peper; Hannah Iroff; Benjamin F. Mujica; Yang Hou (Neuropsychology Review, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Geology of the Eurasia Basin and Gakkel Ridge, Arctic Ocean: Review and update - Anatoly M. Nikishin; Ksenia F. Aleshina; Viktor Yu. Tatarinov; Gillian R. Foulger; Oxana A. Khlebnikova; Aleksey G. Pilitsin; Henry W. Posamentier; Elizaveta A. Rodina; Andrey A. Chernykh; Vladimir E. Verzhbitsky (Earth-Science Reviews, 2026)

Plant area index estimation from UAV LiDAR time-series over cherry orchards - Marcel M. El Hajj; Kasper Johansen; Oliver M. Lopez Valencia; Fabio Veiga de Camargo; Yu-Hsuan Tu; Samer K. Al Mashaharawi; Omar A. López Camargo; Victor Angulo; Dominique Courault; Matthew F. McCabe (Precision Agriculture, 2026)

Regional integration and firms’ environmental performance: Evidence from Chinese urban agglomerations under relative regulatory stringency - Chenyang Yu; Harry F. Lee; Hongyu Long (Environment, Development and Sustainability, 2026)
Regional integration is widely promoted as a path to greener urban agglomerations, but its firm-level environmental effect remains uncertain because integration can also lower the cost of pollution relocation. This study examines how the regulatory gap between core and peripheral cities conditions this effect in China. Using data on 130,727 industrial firms in 137 cities across 16 urban agglomerations, we estimate firm environmental performance with the Kumbhakar–Lien–Hardaker stochastic frontier approach. Regional integration is measured by a spatial division-of-labor index, while relative environmental regulation captures core–periphery regulatory disparity. The results show that regional integration improves firm environmental performance on average, but the effect weakens as the regulatory gap widens. In core cities, the positive effect turns negative when the relative regulation ratio exceeds 1.464. In peripheral cities, the threshold is 1.600, which means that core cities reach the turning point earlier. Robustness tests using alternative performance measures and a hierarchical linear model support this nonlinear pattern. Further analysis shows that the interaction mainly affects the time-varying component of environmental performance, indicating short-term firm adjustment. The threshold mechanism is more evident among non-state-owned firms and non-energy-intensive firms. It is also observed in developed and developing urban agglomerations, but not in forming ones. The findings suggest that integration supports cleaner firm performance only when regulatory gaps are controlled. Policy should use threshold-based regulatory monitoring and firm-level cross-city accountability to prevent pollution relocation.

Clockwise or Counterclockwise: Hysteresis in the Response of Ecosystem Respiration to Temperature - Houkun Chu; Lìyǐn L. Liáng; Miko U. F. Kirschbaum; Jianyang Xia; Ashley Ballantyne; Kailiang Yu; Zheng Fu; Song Wang; Weinan Chen; Dashuan Tian; Qinyu Zheng; Jiaqiang Liao; et al. (Global Change Biology, 2026)
Ecosystem respiration (ER) often responds asymmetrically to seasonal warming and cooling, producing thermal hysteresis. Yet, its global patterns and drivers remain unknown. Here, we used daily ER data from 324 eddy‐covariance sites worldwide and revealed two contrasting hysteresis patterns in the temperature response of ER: clockwise hysteresis (ER is higher during the warming than cooling season) at 173 sites and counterclockwise hysteresis (ER is higher during the cooling than warming season) at 151 sites. The direction and magnitude of ER hysteresis were largely governed by the seasonal timing mismatch between precipitation and vegetation‐derived substrate availability. Higher substrate availability during the warming season enhanced ER and promoted clockwise hysteresis, whereas moisture limitation suppressed ER during the warming season and caused counterclockwise hysteresis. These findings provide robust evidence that ER is a complex process responding to the availability of carbon substrate and regulated differentially by seasonal temperature and precipitation. Our results highlight that the hysteresis of terrestrial carbon release is a key aspect of the global carbon cycle, with important implications for understanding and projecting land carbon‐climate feedbacks.

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Storm-Resolving Earth: How Well Do Global Kilometer-scale Models Simulate Storms in East Asia’s 2020 Record-breaking Wet Summer? - Xiaotong Huang; Puxi Li; Hongyong Yu; Xuelin Hu; Haoming Chen; Jian Li; Andreas F. Prein; Yuanchun Zhang; Moran Zhuang; Yufei Wu; Tianjun Zhou (Advances in Atmospheric Sciences, 2026)
High-performance computing now enables a new generation of global kilometer-scale models. As part of the World Climate Research Programme (WCRP) Global Hackathon 2025 initiative, for the first time, multiple cutting-edge global kilometer-scale models have been run for an entire year. All of them have covered the summer of 2020, when East Asia experienced record-breaking precipitation and catastrophic floods, mainly driven by mesoscale convective systems (MCSs). Using an updated storm-tracking algorithm, this study investigated the performance of six global kilometer-scale models in simulating MCS characteristics during the record-breaking wet summer of 2020 in East Asia. Results revealed that all models generally reproduced MCS characteristics, including MCS size, duration, and key features of convection and precipitation. Models also generally captured finer characteristics such as diurnal variations and the frequency–intensity distribution of hourly precipitation. Among the models, Integrated Forecast System (IFS) performs best in capturing MCS rainfall spatial patterns, Nonhydrostatic ICosahedral Atmospheric Model (NICAM) excels in simulating MCS size, and Simple Cloud-Resolving E3SM Atmosphere Model (SCREAM) most accurately represents the land–sea contrast in MCS precipitation intensity. A common bias across models is the underestimation of rainfall area and overestimation of heavy precipitation intensity, indicating simulated convective cores are stronger than observed. Our results demonstrate that global kilometer-scale modeling has reached a significant benchmark, yet persistent biases remain in MCS simulation. Continued improvements in these models will not only enhance the reliability of modeling but also improve disaster risk reduction and climate change adaptation.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Hepatoprotective and anti-inflammatory dibenzocyclooctadiene lignans from fruits of Kadsura coccinea - Guy Paulin M. Kemayou; Juan-jiang Wu; Wen-chao Zhou; Shi-qi Liu; Piao-piao Jiang; Hanwen Yuan; Wei Su; Bin Li; Simeon F. Kouam; Wei Wang; Yu-pei Yang (Phytochemistry Letters, 2026)

Mixed Anxious-Depressive Disorder in the Early Period of Ischemic Stroke and Its Treatment with Ampakines - A. L. Khokhlov; E. G. Lileeva; Yu.V. Rybachkova; Ch.A. Petrova; E. F. Oko; O. Yu. Arseenkova; A. V. Kiselev (Neuroscience and Behavioral Physiology, 2026)

Predation, Climate and Species Traits Interact to Shape Global Patterns of Avian Nest Architecture - Stephanie Y. Chia; Yu Tsai‐Chen; Yi‐Ru Cheng; Mao‐Ning Tuanmu; William F. Fagan (Global Ecology and Biogeography, 2026)
Aim Bird nest structures are critical for reproductive success and vary widely across species. However, the ecological and evolutionary drivers behind enclosed nests (domes and cavities) remain unclear, with previous studies yielding conflicting results. Leveraging recently available comprehensive nest trait data, we aim to clarify whether enclosed nests primarily function as protection from predation or for regulation of microclimate. Location Global. Time Period Contemporary (environmental data from 1981 to 2010). Major Taxa Studied Birds (Aves). Methods Using phylogenetic logistic regression models for 7427 bird species, we examined whether the observed relationships between nest structure and potential environmental drivers and species traits were consistent with the predictions of the two functional hypotheses. To explore potential variations in the function, we built separate models for domes and cavities, as well as for passerines and non‐passerines. Results Predation risk increases the likelihood of dome use, especially in passerines, where a stronger increase is among the species that are more susceptible to nest predation such as ground‐nesting, non‐cooperative and larger clutch size species. Climatic effects are more pronounced in cavity nesters, with aridity promoting cavity use among passerines, and both cold and hot temperatures increasing cavity use among small non‐passerine species. Main Conclusions Different types of enclosed nests correspond to distinct environmental challenges, with dome nests primarily associated with predation pressure and cavities with adverse climatic conditions. These findings contribute to resolving long‐standing debates about the functional significance of enclosed nests and offer insights into the evolution of avian nest structures.

NAD+ depletion transdifferentiates the gastric stem cells to intestinal goblet cells in patient-derived gastric organoids - Bin Liu; Xiaoyang Zhang; Xia Xue; Fazhan Li; Feifei Ren; Ihtisham Bukhari; Baitong Hu; Xiangdong Sun; Bo Zhang; Yong Yu; Quan Zheng; Wanqing Wu; et al. (Chemical Engineering Journal, 2026)

Metagenomic analysis of fecal microbial communities in dairy goats from different farms - Liang Chengcheng; Zhou Yanduo; Wang Zhebin; Li Jianzhang; Zhu Yangtao; Li Jun; Li Yu; Hashim R. Felemban; Othman Yahya Alyahyawy; Ahmad F. Alhomodi; Fatimah Hadadi; Ali Shaibah; et al. (Protoplasma, 2026)

Screening an aptamer against Amphidinium carterae by WC-SELEX coupled with optimization by G-quadruplex-forming mutation - Guo F. Chen; Yu L. Qin; Jing R. Dai; Wen Q. Chen; Yuan Y. Wang; Chang L. Guo; Chun Y. Zhang (Marine Biology, 2026)

Features of disturbances during November 4–5, 2023, multi-step geospace storm: comparative study of the “ionosphere-thermosphere” system response - Leonid F. Chernogors; Maksym Yu. Tkachenko (Advances in Space Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Effects of urban canopy on kinematic and boundary layer structures of the landfalling Typhoon Lekima (2019) - Xiangyu Ao; Robert F. Rogers; Huan-Cong Liu; Hui Yu; Wei Huang (Urban Climate, 2026)

Extreme wave events inferred from large subaerial carbonate boulders on a rocky coast in Pasuquin, Ilocos Norte, Philippines - Edrian M. Tubalado; Noelynna T. Ramos; Lyndon P. Nawanao; Ace Matthew F. Cantillep; Alec Benjamin G. Ramirez; Jelian S. Reyes; Kathrine V. Maxwell; Shou-Yeh Gong; Tsai-Luen Yu; Chuan-Chou Shen (Marine Geology, 2026)

Fabricating polyphosphonic acid-based ion exchanger with spatially symmetric structure for efficient removal of uranium - Shichang Zhang; Zheng Qin; Zihang Yi; Weiping Liu; Lifeng Chen; Mohammed F. Hamza; Yuezhou Wei; Jie Yu; Shunyan Ning (Journal of Cleaner Production, 2026)

Urinary cotinine cut-offs for tobacco smoke exposure in pregnancy and associations with child intelligence quotient: A multi-cohort analysis - Yu Ni; Logan C. Dearborn; Adam A. Szpiro; Christine T. Loftus; Qi Zhao; Nicole R. Bush; Kaja Z. LeWinn; Marnie F. Hazlehurst; Thomas F. Northrup; Penelope J.E. Quintana; Eunha Hoh; Georg Matt; et al. (International Journal of Hygiene and Environmental Health, 2026)

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Waste minimization in zeolites synthesis from coal fly ash by recycling alkaline waste - Wei Feng; Brent Young; Wei Yu; Xuehai Yu; Eric F. May; Dong Xu; Gang Kevin Li (Journal of Environmental Chemical Engineering, 2026)

Phyllosphere to soil: How long-term fencing reshapes grassland microbial community construction and the functional genes - Jian Li; Yu Zhu; Daniel F. Petticord; David W. Frey; Lijie Huang; Ming-Kang Jin; Michiel Op de Beeck; Quan-Hui Ma; Shu-Huan Jin; Hong Ying; Xi-Mei Xue; Ling Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

Species-specific responses of fish sperm to thermal incubation and activation during short-term storage - Songpei Zhang; Shuang Peng; Yu Gao; Zhijun Ma; Thales S. França; Yu Cheng; Nururshopa Eskander Shazada; Fátima Fernández-García; Jaime Pérez-Sánchez; Juan F. Asturiano; Serhii Boryshpolets; Marek Rodina; et al. (Aquaculture, 2026)

Post-LGM sedimentation history and deglaciation processes in the southern Gulf of St. Lawrence, Canada - I. Schulten; V. Maselli; E.L. King; M. Schmidt; C. Hensen; T. Müller; A. Asioli; A. Micallef; C. Berndt; C.J. Brown; F. Córdoba-Ramírez; J. Elger; et al. (Quaternary Science Reviews, 2026)

Intensification of extreme precipitation across the Tibetan Plateau and its climatic drivers over 1982−2020 - Yiming Song; Shiqin Xu; Dennis P. Lettenmaier; Hylke E. Beck; Xiaodong Chen; Zhongbo Yu; Ningpeng Dong; Qian Cao; Xiaolei Fu; Zhe Yang; Yuliang Zhang; Matthew F. McCabe (Global and Planetary Change, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Hepatoprotective compounds from fruits of (Lem.) A. C. Smith (Schisandraceae) and their chemotaxonomic significance - Guy Paulin M. Kemayou; Ya-shi Wang; Wen-Chao Zhou; Gervais M. Happi; Shi-qi Liu; Wei Su; Bin Li; Simeon F. Kouam; Wei Wang; Yu-pei Yang (Biochemical Systematics and Ecology, 2026)

Reply to the letter : To consider the exercise density in the dose–response relationship: the idea is promising, the operationalization tricky! - Fabian Herold; Liye Zou; Paula Theobald; Patrick Manser; Ryan S. Falck; Qian Yu; Teresa Liu-Ambrose; Arthur F. Kramer; Kirk I. Erickson; Boris Cheval; Yanxia Chen; Matthew Heath; et al. (European Journal of Applied Physiology, 2026)

Association of CLOCK rs1801260 Polymorphism with Sleep Quality in Residents of the Far North - D. G. Gubin; S. N. Kolomeychuk; M. F. Borisenkov; I. M. Petrov; A. A. Markov; Yu. A. Petrova; K. A. Voronin; M. S. Mezhakova; Yu. V. Boldyreva; V. A. Markov; A. U. Shigabaeva (Bulletin of Experimental Biology and Medicine, 2026)

Global Molecular Taxonomy, Phylogeny and Biogeography of the Clam Genus Corbicula (Bivalvia: Cyrenidae) - Yulia V. Bespalaya; Alexander V. Kropotin; Olga V. Aksenova; Mikhail Yu. Gofarov; Alexander V. Kondakov; Ekaterina S. Konopleva; Irina S. Khrebtova; Youness Mabrouki; Dmitry M. Palatov; Alexander A. Prokin; Dmitry P. Karabanov; Oksana V. Travina; et al. (Zoologica Scripta, 2026)
The Corbicula clams (Bivalvia: Cyrenidae) are an ecologically significant and widespread group of fresh‐ and brackish‐water molluscs, playing a keystone role in aquatic ecosystems. Some species of this genus are subglobal invaders. The taxonomy of Corbicula remains very confusing, which hinders both fundamental and applied research on this genus. A comprehensive revision of the taxonomic structure of this group has been lacking so far. In this paper, we clarify the taxonomy, distribution, and evolutionary biogeography of the living representatives of the genus Corbicula , including species widely distributed in their non‐native ranges, on the basis of the largest dataset of DNA sequences ever analysed. Our data reveal that the genus Corbicula contains two subgenus‐level clades: Corbicula s.s. and Sphaerocorbicula Bolotov, Bespalaya & Aksenova subgen. nov. Our COI mtDNA and two‐locus phylogenies reveal that the genus Corbicula contains not Corbicula bilini Bespalaya, Kropotin, Kondakov, Konopleva & Bolotov sp. nov. (Bilin River, Myanmar) and C. lemroae Bespalaya, Kropotin, Kondakov, Konopleva & Bolotov sp. nov. (Lemro River, Myanmar). A new synonymy is established for five species of Corbicula and one is transferred from the family Sphaeriidae to Cyrenidae. Our fossil‐calibrated phylogeny and generalised biogeographic model indicate that the most recent common ancestor of the genus Corbicula could have originated somewhere within a broad area covering Asia near the upper boundary of the Middle Cretaceous.

Comparative Population Genomics of Relictual Caribbean Island Gossypium hirsutum - Weixuan Ning; Guanjing Hu; Daojun Yuan; Mark A. Arick; Chuan‐Yu Hsu; Zenaida V. Magbanua; Olga Pechanova; Daniel G. Peterson; Yating Dong; Joshua A. Udall; Corrinne E. Grover; Jonathan F. Wendel (Molecular Ecology, 2026)
Gossypium hirsutum is the world's most important source of cotton fibre, yet the diversity and population structure of its wild forms remain largely unexplored. The complex domestication history of G. hirsutum combined with reciprocal introgression with a second domesticated species, G. barbadense , has generated a wealth of morphological forms and feral derivatives of both species and their interspecies recombinants, which collectively are scattered across a large geographic range in arid regions of the Caribbean basin. Here we assessed genetic diversity within and among populations from two Caribbean islands, Puerto Rico ( n = 43, five sites) and Guadeloupe ( n = 25, one site), which contain putative wild or introgressed forms. Using whole‐genome resequencing data and a phylogenomic framework derived from a broader genomic survey, we parsed individuals into feral derivatives and truly wild forms. Feral cottons display uneven levels of genetic and morphological resemblance to domesticated cottons, with diverse patterns of genetic variation and heterozygosity. These patterns are inferred to reflect a complex history of interspecific and intraspecific gene flow that is spatially highly variable in its effects. Wild cottons in both Caribbean islands appear to be relatively inbred, especially the Guadeloupe samples. Our results highlight the dynamics of population demographics in relictual wild cottons that experienced profound genetic bottlenecks associated with repeated habitat destruction superimposed on a natural ecogeographical distribution comprising widely scattered populations. These results have implications for conservation and utilisation of wild diversity in G. hirsutum .

Whole Mitochondrial Genome Analysis of Killer Whales Reveals the Presence of Resident and Transient Ecotypes Around Hokkaido - Momoka Suzuki; Mami Kawai; Takashi Hayakawa; Yuki F. Kita; Yu Sato; Miho Inoue‐Murayama; Akira Shiozaki; Shin Nishida; Shimpei F. Hiruta; Hiroshi Ohizumi; Fumio Nakahara; Shigeo Saino; et al. (Marine Mammal Science, 2026)
In the North Pacific, there are at least three genetically different ecotypes of killer whales ( Orcinus orca ), referred to as resident, offshore, and transient. A previous study suggested that killer whales around Hokkaido belong to fish‐eating (resident and/or offshore ecotypes) and mammal‐eating (transient ecotype) groups. These results were supported by haplotypes based on the combination of 1193 bp of cytochrome b and 420 bp of the control region in mitochondrial genomes. However, this analysis was not sufficient to discriminate between resident and offshore ecotypes because of the short sequence lengths. In this study, we analyzed whole mitochondrial genomes of 25 killer whales sampled around Hokkaido to clarify the ecotypes and mitochondrial genome haplotypes. Phylogenetic analysis revealed the presence of resident and transient ecotypes around Hokkaido. The whales identified as residents shared an identical haplotype, which is the most common haplotype in the western North Pacific. In contrast, the transients around Hokkaido exhibited eight haplotypes, including seven novel ones among the 19 individuals, and their haplotype richness was the highest among the North Pacific populations. This result suggests that the Hokkaido coast served as a refugium for transient killer whales during the Last Glacial Maximum.

Multi-gene phylogeny and morphological study reveal three new species of Amanita in the Russian Far East - Ekaterina F. Malysheva; Tatiana Yu. Svetasheva; Vera F. Malysheva (Mycological Progress, 2025)

Dynamic modeling and random vibration of long flexible cylinder with variable cross-section under distributed white noise excitation - Jian Tan; Miaozi Zheng; Peng Zhang; Yu Zhao; Chaoyang Wang; Yulong Zhang; Menglan Duan; Segen F. Estefen (Ocean Engineering, 2025)

A large, two-stage, anatectic, post-collisional late Triassic lithium pegmatite province in the Songpan-Garze Fold Belt (SGFB), Eastern Tibet, China: Constraints from geochemistry and multiple mineral U-Pb geochronology - Guangchun Fei; Julian F. Menuge; Xue Lu; Tianrui Li; Xiaolong Luo; Yunhua Cai; Huipai Zhu; Hua Tan; Chunmei Yu; Guibing Yang (Lithos, 2025)

Sr–Nd–Hf isotope evidence from Paleoproterozoic mafic–ultramafic intrusions, Pechenga belt, Russia: Implications for recycled oceanic crust in mantle plume - Sakine Moradi; Lie-Meng Chen; Qiao Su; Valery F. Smol’kin; Song-Yue Yu; Amjad Hussain (Gondwana Research, 2025)

Assessing the evidence for active volcanism on Venus: current limitations and prospects for future investigations - Justin Filiberto; Mikhail Yu. Zolotov; Erika Kohler; Piero D'Incecco; Dmitry A. Gorinov; Sriram S. Bhiravarasu; Matthew B. Weller; Jeremy F. Brossier; Iván López; Philippa J. Mason; Jemila A. Edmond; Nicola Mari; et al. (Geochemistry, 2025)

The study of the variation of mineral distribution and relative concentration on varieties of oat using synchrotron-based X-ray fluorescence imaging - Ganqi Deng; Miranda Vu; Malgorzata Korbas; Viorica F. Bondici; Chithra Karunakaran; Jarvis Stobbs; Kaiyang Tu; Fang-Xiang Wu; Peiqiang Yu (Food Research International, 2025)

Mesoporous Cu/Zn-ceria-based catalysts for low-temperature water gas shift reaction: A promising path to clean hydrogen production - Tejas S. Bhosale; Sanjubala Sahoo; Yu-Ti Chen; Abiodun Aderibigbe; Scott Bamonte; Luisa F. Posada; Isaac T. Olowookere; Justin Amengual; S. Pamir Alpay; Steven L. Suib (Chemical Engineering Journal, 2025)

Mg isotopes and in-situ Rb Sr dating reveal carbonate-rich and carbonate-poor sediments in mantle sources of lamproites beneath the North China Craton - Kaizhang Yu; Yongsheng Liu; Wei Chen; Chunfei Chen; Chutian Shu; Stephen F. Foley; Jixing Li; Zhaochu Hu (Chemical Geology, 2025)

Toward a harmonized regulatory framework for 3D-printed pharmaceutical products: the role of critical feedstock materials and process parameters - Riyad F. Alzhrani; Rawan A. Fitaihi; Majed A. Majrashi; Yu Zhang; Mohammed Maniruzzaman (Drug Delivery and Translational Research, 2025)
The commercialization of additive manufacturing (AM) in pharmaceuticals manufacturing has attracted significant attention for its potential to produce customized products. However, the process is slow and hindered by the lack of designated regulatory guidelines tailored to 3D-printed pharmaceutical products (3DPPs). The 3D-printing technology has paved the way for personalized medicine, enabled treatment of rare genetic disorders, and offered many other possibilities for patients. Despite the US Food and Drug Administration (FDA) approval of Spritam ® , a clear regulatory framework for licensing 3DPPs by the FDA or EMA remains unavailable. The current practice considers all products the same, regardless of their manufacturing method and/or complexity. While this approach has been generally accepted, it frequently fails to evaluate the unique quality attributes of 3DPPs. The lack of a harmonized regulatory framework tailored to the 3DPPs presents a major barrier to the widespread adoption of AM and other innovative technologies. To bridge this gap, this review highlights the most critical parameters related to the feedstock materials and 3D-printing processes, emphasizing their impact on the quality attributes of finished 3DPPs. Numerous scenarios have been proposed to encourage regulatory authorities to establish robust regulatory guidance for the 3D-printing technology at either industrial or point-of-care (PoC) settings. Coordinated efforts between regulatory authorities, industry partners and other stakeholders are necessary to define product specifications and identify appropriate analytical techniques for evaluating finished 3DPPs. By developing a harmonized regulatory framework and establishing quality control measures, the full potential of AM can be realized. This will ultimately ensure that novel 3DPPs and personalized medicines adhere to rigorous regulatory standards of quality, safety and efficacy. Graphical abstract

Production of Recombinant Neuraminidase NA Protein of Influenza A/H5N2 Virus and Its Application for the Detection of Virus-Specific IgG to Influenza A Viruses - T. V. Gupalova; E. A. Bormotova; G. F. Leontieva; T. A. Kramskaya; Yu. A. Desheva; A. N. Suvorov (Bulletin of Experimental Biology and Medicine, 2025)

3D-printed Zeolite–MgAl layered double oxides (3D-Ze/LDO) as a reusable adsorbent with dual functionality for effective anionic and cationic pollutant removal from water - Tarmizi Taher; Sephia Amanda Muhtar; Audrey Giftie Natasha Sianturi; Rizky Aflaha; Kuwat Triyana; Aldes Lesbani; Muhamad F. Arif; Dian Ahmad Hapidin; Khairurrijal Khairurrijal; Zhongliang Yu; Aditya Rianjanu (Applied Clay Science, 2025)

Effects of an environmentally relevant mixture of organophosphate esters on the phenotype and function of HepG2 liver cells - Dongwei Yu; Barbara F. Hales; Bernard Robaire (Archives of Toxicology, 2025)

Regional Emergence of Water‐Related Browning in a Greening World - Rene Orth; Jasper M. C. Denissen; Josephin Kroll; Sungmin O; Ana Bastos; Wantong Li; Diego G. Miralles; Melissa Ruiz‐Vásquez; Anne J. Hoek van Dijke; Andrew F. Feldman; Mirco Migliavacca; Lan Wang‐Erlandsson; et al. (Global Change Biology, 2025)
The Earth is greening in many regions under elevated atmospheric CO 2 concentrations, along with increasing temperature and land use changes. However, despite the continued rise in CO 2 , greening has stagnated or even reversed in some regions, suggesting a reduced capacity of the land surface to act as a carbon sink. Here, we show that declining water availability and rising atmospheric water demand have coincided with regional browning trends over recent decades in some tropical regions that have historically acted as prominent carbon sinks. A regression analysis considering a balanced set of water‐ and energy‐related variables alongside land cover change and climate extremes confirms that both water availability and atmospheric water demand are important contributors to inter‐annual variability in Leaf Area Index (LAI) there. Earth system models mostly reproduce the observed spatial extent of browning and concurrent related coinciding water changes in the multi‐model mean, but results from individual models differ strongly. Our findings provide a new constraint for related model development and highlight the need for enhanced monitoring and consideration of observation‐based water availability trends as an emerging driver of vegetation in future analyses and model development.

Vortex-induced vibrations of variable cross-section CWPs under axially varying tension: Numerical investigation with three flow profiles - Jian Tan; Yu Zhang; Yulong Zhang; Le Sun; Shuai Cui; Chen An; Segen F. Estefen (Ocean Engineering, 2025)

Thermo-hydro-mechanical responses of a high-level radioactive waste repository: Effects of short- and long-term nonlinear behavior of the host rock - M.N. Vu; C. Plúa; G. Armand; F. Bumbieler; C. De Lesquen; M. Souley; M. Alonso; J. Vaunat; A. Gens; Z. Yu; J.F. Shao (International Journal of Rock Mechanics and Mining Sciences, 2025)

Performance of soy-winter wheat relay intercropping under various water conditions - Jennifer B. Thompson; Thomas F. Döring; Sonoko D. Bellingrath-Kimura; Jing Yu; Moritz Reckling (Field Crops Research, 2025)

How waterbird communities respond to seasonal and environmental factors in rice fields adjacent to a Ramsar wetland - Yu Zheng; Yu Chen; Yunwei Song; Guangyao Wang; Yong Zhang; Xinsheng Chen; Chunlin Li; Willem F. de Boer (Agriculture, Ecosystems & Environment, 2025)

Asthenospheric flow and lithospheric erosion driving the outward growth of the northeastern Tibetan Plateau - Chutian Shu; Xiaoping Long; Stephen F. Foley; Kaizhang Yu; Zhuoying Zhang; Zheng-Xiang Li; Luc S. Doucet; Qiang Xu (Science Bulletin, 2025)

Enhanced electrocatalytic hydrogen evolution over a two-dimensional Ti3C2 MXene/FDU-12 templated-nanoporous NiO-decorated carbon paste electrode - Grandprix T.M. Kadja; Aninda F. Nuraini; Ria S. Rahayu; Agam Pamungkas; Ferry Iskandar; Munawar Khalil; Triati D.K. Wungu; Qingjun Yu; Xiaolong Tang; Honghong Yi; Muhammad H. Mahyuddin; Dewi Agustiningsih (Fuel, 2025)

Geographic variation of body size in a plateau anuran: evidence supporting the water availability and heat balance trade-off hypothesis - Tong L. Yu; Chao F. Gu (Evolutionary Ecology, 2025)

Beyond FITT: addressing density in understanding the dose–response relationships of physical activity with health—an example based on brain health - Fabian Herold; Liye Zou; Paula Theobald; Patrick Manser; Ryan S. Falck; Qian Yu; Teresa Liu-Ambrose; Arthur F. Kramer; Kirk I. Erickson; Boris Cheval; Yanxia Chen; Matthew Heath; et al. (European Journal of Applied Physiology, 2025)
Research on physical activity (PA) and health has a fundamental concern with dose–response relationships. The variables of (1) Frequency, (2) Intensity, (3) Time, and (4) Type (i.e., the FITT principle) have traditionally been used to operationalize the dosage of PA. We consider some limitations of FITT and propose that it can be complemented by the additional variable density (from the German exercise and training variable Belastungsdichte), which can be defined as the timing of successive work bouts within a single PA bout as well as the timing between successive PA bouts within a specific time period; it does so by quantifying the temporal intervals between successive work or PA bouts (i.e., time spent at a lower PA intensity or resting such as in napping/sleeping or sedentary behaviors). Using the field of PA and brain health as an example, we discuss the opportunities and challenges for further research employing the variable density and consider its potential to improve the understanding of dose–response relationships between PA and health outcomes.

Deep learning applications for multispectral remote sensing analysis of carbon sequestration dynamics in restored forest landscapes - Bo Yu; Haytham F. Isleem (Mitigation and Adaptation Strategies for Global Change, 2025)

Sale of critically endangered sharks in the United States - Savannah J. Ryburn; Tammy Yu; Kelly J. Ong; Eldridge Wisely; Meggan A. Alston; Ella Howie; Peyton LeRoy; Sarah Elizabeth Giang; William Ball; Jewel Benton; Robert Calhoun; Isabella Favreau; et al. (Frontiers in Marine Science, 2025)
In the United States, shark meat is sold in grocery stores, seafood markets, and online. The meat is often mislabeled as another species or generically labeled as “shark”. The ambiguity of these generic labels makes it challenging to assess the conservation implications of this practice and for consumers to avoid high trophic-level species that often have high mercury concentrations in their tissues. We purchased and DNA barcoded 29 shark products in the United States to determine their species identity. Our samples consisted of 19 filets sold in grocery stores, seafood markets, and Asian specialty markets (mostly in North Carolina) and 10 ordered online as “jerky”. Ninety three percent of samples (27 of 29) were ambiguously labeled as shark or mako shark but not as a specific species. Of the two samples that were labeled to species, one was mislabeled (e.g., shortfin mako shark labeled as blacktip shark) and the other was correctly labeled. Barcoding indicated that the 29 samples included 11 different species of shark, including three species listed by the IUCN as Critically Endangered: great hammerhead, scalloped hammerhead, and tope. Previous studies have found that the first two species contain very high levels of mercury, illustrating the implications of seafood mislabeling for human health. The availability of shark meat in U.S. grocery stores is surprising given the dramatic decline of shark populations globally. Moreover, the fact that nearly all shark meat is labeled ambiguously or incorrectly amplifies the problem. Accurate, verified product labels for shark meat would benefit consumers and shark conservation efforts, and should be a priority for the seafood industry.

LP-23 Epigenetic Signatures of Exosomal miRNAs in Chromium(VI)-Induced Genetic and Immunological Toxicity - S. Hong; Y. Zhang; G. Hu; L. Wang; S. Yu; X. Zhu; F. Yuan; G. Jia (Toxicology Letters, 2025)

Concept of approach to advanced Russian orbital station - Nikita A. Chudinov; Rafail F. Murtazin; Vladimir A. Soloviev; Victor V. Afonin; Alexander Yu. Kaleri (Journal of Space Safety Engineering, 2025)

Association between exposure to perfluoroalkyl compounds during early pregnancy and risk of late miscarriage: The Japan Environment and Children's Study - Nozomi Tatsuta; Miyuki Iwai-Shimada; Tomohiko Isobe; Shoji F. Nakayama; Makiko Sekiyama; Mai Takagi; Yayoi Kobayashi; Yu Taniguchi; Shin Yamazaki (International Journal of Hygiene and Environmental Health, 2025)

Viewing heat through ice: An infrared camera monitors hydrogel freezing and thawing during cryoapplication - Gennadiy O. Kovalov; Mykola O. Chyzh; Vyacheslav Yu Globa; Oleksandr F. Todrin; Galyna V. Shustakova; Eduard Yu Gordiyenko; Yuliya V. Fomenko; Oleh V. Ivakhnenko; Polina O. Kofman; Sergey N. Shevchenko (Cryobiology, 2025)

In vitro cytotoxicity evaluation of triphenylphosphonium (TPP) conjugates of some acetylenated nucleic bases and their analogues - Olga V. Andreeva; Alexandra D. Voloshina; Anna P. Lyubina; Andrey A. Parfenov; Bulat F. Garifullin; Irina Yu. Strobykina; Mayya G. Belenok; Olga B. Babaeva; Vasily M. Babaev; Liliya F. Saifina; Vyacheslav E. Semenov; Vladimir E. Kataev (Medicinal Chemistry Research, 2025)

Multidirectional effect of low-intensity neuromuscular electrical stimulation on gene expression and phenotype in thigh and calf muscles after one week of disuse - Anna A. Borzykh; Roman Y. Zhedyaev; Ivan I. Ponomarev; Tatiana F. Vepkhvadze; Viktor G. Zgoda; Mira A. Orlova; Nikita E. Vavilov; Nikita V. Shishkin; Egor M. Lednev; Pavel A. Makhnovskii; Kristina A. Sharlo; Anastasia R. Babkova; et al. (European Journal of Applied Physiology, 2025)

Chitin degradation by the aquatic pigment-producing bacteria of Janthinobacterium spp. from stream flows and springs of Shulgan River basin and Shulgan-Tash Cave, Southern Urals - Gleb E. Aktuganov; Elena A. Gilvanova; Polina Yu. Milman; Ravil R. Garafutdinov; Alena S. Ryabova; Nailya F. Galimzianova; Olga Ya. Chervyatsova; Lyudmila Yu. Kuzmina (Biodegradation, 2025)

Assessing inter-industrial ecosystem service flows and economic benefits of sponge city: A comprehensive input-output analysis - Weicen Chang; Gengyuan Liu; Yu Chen; Zhaoman Huo; Delin Fang; Feni Agostinho; Cecilia M.V.B. Almeida; Biagio F. Giannetti (Environmental Impact Assessment Review, 2025)

Assessment of Cognitive Functions in Elderly Patients with Type 2 Diabetes Mellitus - A. A. Akhmedova; F. O. Ushanova; T. Yu. Demidova (Neuroscience and Behavioral Physiology, 2025)

The April 20, 2023, hybrid eclipse features and their ionospheric signatures in the eastern equatorial and southern hemisphere region of the globe - Leonid F. Chernogor; Yurii B. Mylovanov; Yevhen H. Zhdanko; Yu Zheng (Advances in Space Research, 2025)

An ionospheric VTEC forecasting model over China based on the kernel ridge regression - Bang-min Han; Qiao Yu; Jian Wang; Leonid F. Chernogor; Yu Zheng (Advances in Space Research, 2025)

High-resolution dynamically downscaled projections of future extreme temperatures, heatwaves and exposure in Southeast Asia - Jianjun Yu; Aurel F. Moise; Sandeep Sahany; Venkatraman Prasanna; Xin Rong Chua; Chen Chen; Muhammad E.E. Hassim; Gerald Lim; Fei Luo; Anupam Kumar; Puyang Liu; Pavan Harika Raavi (Science of The Total Environment, 2025)

Rise and fall of archaeocyath reefs shaped early Cambrian skeletal animal abundance - Sara B. Pruss; Emily F. Smith; Andrey Yu Zhuravlev; Rhiannon Z. Nolan; Tessa C. McGann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Unraveling the origin and charge of Halahatang oils, Tarim Basin - Peng Sun; Chunfang Cai; Daowei Wang; Yu Qi; Chenlu Xu; Paul F. Greenwood (Organic Geochemistry, 2025)

3,7-Diazabicyclo[3.3.1]nonanes and 1,3-diazaadamantanes containing monoterpenoid moieties as synthetic adaptogens: synthesis, ADMET predictions, and in vivo biological activity - Anastasiia A. Kotliarova; Konstantin Yu. Ponomarev; Ekaterina A. Morozova; Evgeniy V. Suslov; Alla V. Pavlova; Tatyana G. Tolstikova; Konstantin P. Volcho; Nariman F. Salakhutdinov (Medicinal Chemistry Research, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Around the World in 26 Million Years: Diversification and Biogeography of Pantropical Grass‐Yellow Eurema Butterflies (Pieridae: Coliadinae) - Jing V. Leong; Pável Matos‐Maraví; Rayner Núñez; Renato Nunes; Weijun Liang; Michael F. Braby; Tenzing Doleck; Kwaku Aduse‐Poku; Yutaka Inayoshi; Yu‐Feng Hsu; Niklas Wahlberg; Djunijanti Peggie; et al. (Journal of Biogeography, 2025)
Aim Grass‐yellow butterflies ( Eurema ) are a group of pantropical Pieridae distributed throughout Asia, Australasia, Africa and the New World. However, little is known about their diversification, including the biogeographic mechanism(s) explaining their circumglobal distribution. We present the first densely sampled, time‐calibrated phylogeny and biogeographic reconstruction of grass‐yellows to confirm the monophyly of the genera, re‐evaluate their taxonomy and infer the biogeographic events contributing to their worldwide distribution. Location Global tropics and subtropics. Taxon The butterfly tribe Euremini (Pieridae: Coliadinae). Methods We analysed up to 391 genetic loci from 126 samples of 66 ingroup species. Divergence dating was accomplished in a Bayesian phylogenetic framework using secondary calibration points, and maximum likelihood models of various biogeographic models were fitted to the data using the R package BioGeoBEARS. We used the best fitting model to estimate relative dispersal events with biogeographical stochastic mapping. Finally, we estimated branch‐specific speciation and extinction rates to assess the diversification history of the group. Results Different phylogenomic analyses converged on similar topologies with robust support. Grass‐yellows emerged ca . 26 Mya in the New World, and a single extant lineage dispersed to Asia in the early Miocene, where they diversified and dispersed to Africa and Australasia. The fastest rates of diversification occurred in the Old World tropics during the late Miocene. Many of the grass‐yellow genera were either paraphyletic or polyphyletic as traditionally circumscribed. To maintain nomenclatural stability, we place all grass‐yellows in Eurema sensu lato and recognise two subgenera: Eurema ( Abaeis ) and Eurema ( Eurema ). Main Conclusions Grass‐yellow butterflies originated in the Americas and attained their global distributional patterns via dispersal. The Indo‐Australian and Caribbean archipelagoes seem to have accelerated the diversification of the group, and movement in and out of these island regions was frequent. Although the traditional view of founder‐event speciation envisions migrants from large landmasses (‘mainland’) colonising smaller landmasses (‘islands’), we find that island to mainland dispersal and differentiation were equally or more common.

Nutrient recovery from high-salinity dairy wastewater through the cultivation of acclimatized microalgae - Rui Xiao; Erika Carter; Austin Allen; Pei-Lin Tan; Yu-Hua Zheng; Qian Chen; Shun-Ni Zhu; Sudeep C. Popat; Allan Knopf; Clinton F. Williams; Howard H. Chou; Huan Chen (Journal of Water Process Engineering, 2025)

The mechanisms of zinc-induced root growth inhibition in the zinc hyperaccumulator Noccaea caerulescens and the non-accumulator Microthlaspi perfoliatum - Natalia V. Zhukovskaya; Anna D. Kozhevnikova; Nina F. Lunkova; Tatiana Yu. Lykova; Alexander V. Kartashov; Victor B. Ivanov; Henk Schat; Ilya V. Seregin (Plant and Soil, 2025)

Alternative Combinations of IL17A Polymorphic Variants with the Variants of TNF, IL1B, IL6, and IL8 Proinflammatory Cytokines Genes in Uterine Leiomyoma - V. I. Konenkov; V. F. Prokofiev; A. V. Shevchenko; E. G. Koroleva; Yu. S. Timofeeva; S. V. Aidagulova; I. O. Marinkin (Bulletin of Experimental Biology and Medicine, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

Overlooked importance: The supporting roles of satellite wetlands for waterbirds around the Yangtze-connected lakes, China - Guangyao Wang; Chengrong Pan; Shilong Yu; Sheng Xu; Shuheng Dai; Jingjing Ding; Xiangrong Song; Chunlin Li; Yong Zhang; Willem F. de Boer (Journal of Environmental Management, 2025)

Prenatal ozone exposure and child lung function: Exploring effect modification by oxidative balance score - Logan C. Dearborn; Marnie F. Hazlehurst; Melissa M. Melough; Adam A. Szpiro; Allison R. Sherris; Margaret A. Adgent; Yu Ni; Rosalind J. Wright; Neeta Thakur; Nicole R. Bush; Paul E. Moore; Christine T. Loftus; et al. (International Journal of Hygiene and Environmental Health, 2025)

Magnitude, spatial patterns and drivers of methane fluxes from coastal salt marshes and mangrove forests in China - Yixuan Yu; Derrick Y. F. Lai; Minjie Hu; Chuan Tong (Science China Earth Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Salinity-redox covariation in Mississippian Bowland Shale (Craven Basin, UK) controlled by eustasy and climate - Yu Jiao; Joseph F. Emmings; Lian Zhou; Thomas J. Algeo; Lanping Feng; Tao He; Jinhua Liu; Daqian Zhang; Jianping Wang (Chemical Geology, 2025)

Contrasting response of root traits of arbuscular mycorrhizal and ectomycorrhizal trees to phosphorus availability in subtropical forests - Yanwen Chen; Minxia Liang; David F. R. P. Burslem; David Johnson; Shixiao Yu; Xubing Liu (Plant and Soil, 2025)

Mechanisms of the Pathogenesis of Alzheimer’s Disease: The Role of the Basal Forebrain - V. F. Kitchigina; I. Yu. Popova; L. V. Shubina (Neuroscience and Behavioral Physiology, 2025)

Triphenylphosphonium (TPP) conjugates of 1,2,3-triazolyl nucleoside analogues. Synthesis, cytotoxicity and antimicrobial activity - Olga V. Andreeva; Alexandra D. Voloshina; Anna P. Lyubina; Bulat F. Garifullin; Anastasiia S. Sapunova; Syumbelya K. Amerhanova; Irina Yu. Strobykina; Mayya G. Belenok; Olga B. Babaeva; Vasily M. Babaev; Leysan R. Khabibulina; Liliya F. Saifina; et al. (Medicinal Chemistry Research, 2025)

Effect of Immunization with Type 5 Group A Streptococcal Antigens and Liposaccharide (LPS) In Vivo and In Vitro on Splenic and Bone Marrow Multipotent Stromal Cells in Mice - Yu. F. Gorskaya; T. A. Danilova; A. I. Tukhvatulin; A. Sh. Dzharullaeva; E. N. Semenova; L. M. Vavilova; E. V. Nagurskaya; V. A. Bekhalo; A. G. Minko; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2025)

Geomagnetic effect of the solar eclipse of April 8, 2024, in the North American sector - Leonid F. Chernogor; Marya Yu. Holub (Advances in Space Research, 2025)

Genomic determinants of biological age estimated by deep learning applied to retinal images - Yu Huang; Mohammad Ghouse Syed; Ruiye Chen; Cong Li; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Shulin Tang; Jing Liu; Shunming Liu; Sundar Srinivasan; et al. (GeroScience, 2025)
With the development of deep learning (DL) techniques, there has been a successful application of this approach to determine biological age from latent information contained in retinal images. Retinal age gap (RAG) defined as the difference between chronological age and predicted retinal age has been established previously to predict the age-related disease. In this study, we performed discovery genome-wide association analysis (GWAS) on the RAG using the 31,271 UK Biobank participants and replicated our findings in 8034 GoDARTS participants. The genetic correlation between RAGs predicted from the two cohorts was 0.67 ( P = 0.021). After meta-analysis, we found 13 RAG loci which might be related to retinal vessel density and other aging processes. The SNP-wide heritability ( h 2 ) of RAG was 0.15. Meanwhile, by performing Mendelian randomization analysis, we found that glycated hemoglobin, inflammation hemocytes, and anemia might be associated with accelerated retinal aging. Our study explored the biological implications and molecular-level mechanism of RAG, which might enable causal inference of the aging process as well as provide potential pharmaceutical intervention targets for further treatment. Graphical Abstract

Immunochemical Characteristics and Functional Activity of Monoclonal Antibodies Obtained to the Recombinant Form of Pneumolysin - I. V. Yakovleva; N. F. Gavrilova; E. A. Kurbatova; D. S. Vorobyev; E. S. Petukhova; I. B. Semenova; A. E. Zaitsev; Yu. V. Volokh; A. Yu. Leonova; A. V. Poddubikov (Bulletin of Experimental Biology and Medicine, 2025)

Soil Microbiome Inoculation for Resilient and Multifunctional New Forests in Post‐Agricultural Landscapes - Sofia I. F. Gomes; Per Gundersen; T. Martijn Bezemer; Davide Barsotti; Ludovica D'Imperio; Konstantinos Georgopoulos; Mathias Just Justesen; Karelle Rheault; Yamina M. Rosas; Inger Kappel Schmidt; Leho Tedersoo; Lars Vesterdal; et al. (Global Change Biology, 2025)
Afforestation is increasingly recognized as a critical strategy to restore ecosystems and enhance biodiversity on post‐agricultural landscapes. However, agricultural legacies, such as altered soil structure, nutrient imbalances, and depleted microbial diversity, can slow down forest establishment or cause ecosystems to deviate from expected successional trajectories. In this opinion paper, we explore the potential of soil inoculations as a tool to overcome these challenges by introducing beneficial microbial communities that can accelerate ecosystem recovery and forest development. Restoring soil biodiversity is a crucial aspect of this process that drives broader ecosystem functionality and resilience. We highlight the need to carefully consider the type and timing of inoculations and to ensure compatibility between the inoculum and recipient site characteristics to optimize the establishment of introduced species. While tree productivity is often a central focus of afforestation efforts, the restoration of soil biodiversity, which will also contribute to increased ecosystem‐level functions, should also be a priority for long‐term forest resilience. Agricultural legacies add complexities to the restoration process, creating unique challenges that need to be addressed in restoration planning. Thus, successful inoculation strategies require a thorough understanding of both donor and recipient site characteristics, also in relation to potential mismatches related to soil physiochemical properties to avoid unintended consequences such as the non‐establishment of introduced species. Additionally, we call for the re‐evaluation of afforestation targets and the development of standardized monitoring protocols that track the success of inoculation efforts, particularly regarding soil health, microbial community establishment, and biodiversity recovery. By integrating inoculation practices within a broader restoration framework, we can enhance the resilience, biodiversity, and ecosystem functionality of newly afforested landscapes. Ultimately, this approach may play a critical role in ensuring the success of large‐scale afforestation projects.

Main features of the geomagnetic effect of the October 14, 2023 annular solar eclipse in the Americas - Leonid F. Chernogor; Mariia Yu. Holub; Victor T. Rozumenko (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Metabolic pathway and network analysis integration for discovering the biomarkers in pig feces after a controlled fruit-vegetable dietary intervention - Zhihao Liu; Gloria Solano-Aguilar; Sukla Lakshman; Joseph F. Urban; Mengliang Zhang; Pei Chen; Liangli Lucy Yu; Jianghao Sun (Food Chemistry, 2024)

VOC emission rates from an indoor surface using a flux chamber and PTR-MS - Han N. Huynh; Jenna C. Ditto; Jie Yu; Michael F. Link; Dustin Poppendieck; Delphine K. Farmer; Marina E. Vance; Jonathan P.D. Abbatt (Atmospheric Environment, 2024)

Exogenous Application of Chitosan Mitigates the Inhibitory Effects of Zinc on the Growth of Wheat Seedlings by Modulating Zn Transport and ROS Scavenging - Lina Fan; Jingjing Zhang; Zhengyang Xu; Qiujuan Jiao; Zihao Song; Peiyi Yu; Deyuan Liu; Gezi Li; Shah Fahad; Zulfiqar Ali Sahito; Mohammed Ali Alshehri; Salah F. Abou-Elwafa; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Speculation on an early Pleistocene origin of the Parker dunes of southwest Arizona, USA - Yeong Bae Seong; Kenzie L. Shandonay; Ronald I. Dorn; Brian F. Gootee; Byong Yong Yu (Aeolian Research, 2024)

Unexpected nanoscale CeO2 structural transformations induced by ecologically relevant phosphate species - Tatiana V. Plakhova; Maria A. Vyshegorodtseva; Irina F. Seregina; Roman D. Svetogorov; Alexander L. Trigub; Daniil A. Kozlov; Alexander V. Egorov; Maria D. Shaulskaya; Dmitry M. Tsymbarenko; Anna Yu. Romanchuk; Vladimir K. Ivanov; Stepan N. Kalmykov (Chemosphere, 2024)

Letter to the Editor regarding Chappell et al., 2023, “Satellites reveal Earth's seasonally shifting dust emission sources” - Natalie Mahowald; Paul Ginoux; Gregory S. Okin; Jasper Kok; Samuel Albani; Yves Balkanski; Mian Chin; Gilles Bergametti; Thomas F. Eck; Carlos Pérez García-Pando; Antonis Gkikas; María Gonçalves Ageitos; et al. (Science of The Total Environment, 2024)

Phylogenetic relationships and historical biogeography of silkmoths (Lepidoptera: Bombycidae) suggest an origin in Southern Gondwana - Rung-Juen Lin; Yu-Chi Lin; Michael F. Braby; Andreas Zwick; Yu-Feng Hsu (Molecular Phylogenetics and Evolution, 2024)

Comparing evaporation from water balance framework and multiple models on a global scale - Jinghua Xiong; Abhishek; Chong Zhang; Li Xu; Hrishikesh A. Chandanpurkar; James S. Famiglietti; Pat J.-F. Yeh; Zhongbo Yu; Ningpeng Dong; Haoran Hao; Shuang Yi; Lei Cheng; et al. (Journal of Hydrology, 2024)

Trends in acrylamide content in selected potato/sweet potato products on the Canadian market - Zakir Hossain; Tony Zhao; Adam Becalski; Jakob Schneider; Sherry Yu Feng; Dorothea F. K. Rawn (Food Additives & Contaminants: Part A, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cryogenic vacuum distillation vs Cavitron methods in ecohydrology: Extraction protocol effects on plant water isotopic values - Hongxiu Wang; Haiyang Yu; Dong He; Min Li; Bingcheng Si; Jeffrey J. McDonnell; Magali F. Nehemy (Journal of Hydrology, 2024)

Comparative analysis of the dispersion modeling and dose projection results performed under BARCO international project - Yu. Balashevska; Yu. Kyrylenko; Z. Ivanov; F. Rocchi; A. Cervone; A. Guglielmelli; M. Ilvonen; J. Rossi; A. Slavickas; H. Thielen (Journal of Environmental Radioactivity, 2024)

Denitrifying communities enriched with mixed nitrogen oxides preferentially reduce N2O under conditions of electron competition in wastewater - Jinyu Ye; Marlene Mark Jensen; Estelle M. Goonesekera; Ran Yu; Barth F. Smets; Borja Valverde-Pérez; Carlos Domingo-Félez (Chemical Engineering Journal, 2024)

Ovarian hyperplasia linked to a mutation in MAN1A2 in a cow with excessive follicular growth and functional oocytes - Camila J. Cuellar; Gabriel A. Zayas; Thiago F. Amaral; Maura S. McGraw; Fahong Yu; Raluca G. Mateescu; Peter J. Hansen (Veterinary Research Communications, 2024)

A methodology for gene level omics-WAS integration identifies genes influencing traits associated with cardiovascular risks: the Long Life Family Study - Sandeep Acharya; Shu Liao; Wooseok J. Jung; Yu S. Kang; Vaha Akbary Moghaddam; Mary F. Feitosa; Mary K. Wojczynski; Shiow Lin; Jason A. Anema; Karen Schwander; Jeff O. Connell; Michael A. Province; et al. (Human Genetics, 2024)
The Long Life Family Study (LLFS) enrolled 4953 participants in 539 pedigrees displaying exceptional longevity. To identify genetic mechanisms that affect cardiovascular risks in the LLFS population, we developed a multi-omics integration pipeline and applied it to 11 traits associated with cardiovascular risks. Using our pipeline, we aggregated gene-level statistics from rare-variant analysis, GWAS, and gene expression-trait association by Correlated Meta-Analysis (CMA). Across all traits, CMA identified 64 significant genes after Bonferroni correction (p ≤ 2.8 × 10 –7 ), 29 of which replicated in the Framingham Heart Study (FHS) cohort. Notably, 20 of the 29 replicated genes do not have a previously known trait-associated variant in the GWAS Catalog within 50 kb. Thirteen modules in Protein–Protein Interaction (PPI) networks are significantly enriched in genes with low meta-analysis p-values for at least one trait, three of which are replicated in the FHS cohort. The functional annotation of genes in these modules showed a significant over-representation of trait-related biological processes including sterol transport, protein-lipid complex remodeling, and immune response regulation. Among major findings, our results suggest a role of triglyceride-associated and mast-cell functional genes FCER1A , MS4A2 , GATA2 , HDC , and HRH4 in atherosclerosis risks. Our findings also suggest that lower expression of ATG2A , a gene we found to be associated with BMI, may be both a cause and consequence of obesity. Finally, our results suggest that ENPP3 may play an intermediary role in triglyceride-induced inflammation. Our pipeline is freely available and implemented in the Nextflow workflow language, making it easily runnable on any compute platform ( https://nf-co.re/omicsgenetraitassociation ) .

P01-40 Contemporary in vitro toxicology assessment of a novel Herbal Heated Product (HHP) compared to cigarette smoke - E. Bishop; F. Yu; S. Bozhilova; F. Miazzi; Y. Li; L. Smith; D. Smart; D. Breheny (Toxicology Letters, 2024)

OS01-04 Review of New Approach Methodologies for application in risk assessment of nanoparticles in the food and feed sector: status and challenges - S.M. Usmani; S. Bremer-Hoffmann; K. Cheyns; F. Cubadda; V.I. Dumit; S.E. Escher; V. Fessard; A.C. Gutleb; T. Léger; Y.-C. Liu; J. Mast; E. McVey; et al. (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Recent advances made by reaction experiments on melting of heavily metasomatized hydrous mantle - Dejan Prelević; Michael W. Förster; Stephan Buhre; Fatma Gülmez; Tobias Grützner; Yu Wang; Stephen F. Foley (Earth-Science Reviews, 2024)

Kilometer-scale multi-physics simulations of heavy precipitation events in Northeast China - Hongyong Yu; Andreas F. Prein; Dan Qi; Kaicun Wang (Climate Dynamics, 2024)

High-pressure structural behavior of α-K2Ca3(CO3)4 up to 20 GPa - Mark A. Ignatov; Sergey V. Rashchenko; Anna Yu Likhacheva; Alexandr V. Romanenko; Anton F. Shatskiy; Anton V. Arefiev; Konstantin D. Litasov (Physics and Chemistry of Minerals, 2024)

Ventral wing hairs provide tactile feedback for aerial prey capture in the big brown bat, Eptesicus fuscus - Brittney L. Boublil; Chao Yu; Grant Shewmaker; Susanne Sterbing; Cynthia F. Moss (Journal of Comparative Physiology A, 2024)

Ensemble learning of decomposition-based machine learning models for multistep-ahead daily streamflow forecasting in northwest China - Haijiao Yu; Linshan Yang; Qi Feng; Rahim Barzegar; Jan F. Adamowski; Xiaohu Wen (Hydrological Sciences Journal, 2024)

Neuroanatomical and clinical factors predicting future cognitive impairment - Phoebe Imms; Nikhil N. Chaudhari; Nahian F. Chowdhury; Haoqing Wang; Xiaokun Yu; Anar Amgalan; Andrei Irimia (GeroScience, 2024)
Identifying cognitively normal (CN) older adults who will convert to cognitive impairment (CI) due to Alzheimer’s disease is crucial for early intervention. Clinical and neuroimaging measures were acquired from 301 CN adults who converted to CI within 15 years of baseline, and 294 who did not. Regional volumes and brain age measures were extracted from T 1 -weighted magnetic resonance images. Linear discriminant analysis compared non-converters’ characteristics against those of short-, mid-, and long-term converters. Conversion was associated with clinical measures such as hearing impairment and self-reported memory decline. Converters’ brain volumes were smaller than non-converters’ across 48 frontal, temporal, and subcortical structures. Brain age measures of 12 structures were correlated with shorter times to conversion. Conversion prediction accuracy increased from 81.5% to 90.5% as time to conversion decreased. Proximity to CI conversion is foreshadowed by anatomic features of brain aging that enhance the accuracy of predicting conversion.

Influence of divalent metal cations on α-lactalbumin fibril formation - L. R. Bogdanova; A. A. Nikiforova; S. A. Ziganshina; Yu. F. Zuev; I. A. Sedov (JBIC Journal of Biological Inorganic Chemistry, 2024)

Comparative analysis of physicochemical properties and biological activities of crude polysaccharides isolated from selected Auricularia cornea strains - Asif Ali Khan; Fang-Jie Yao; Feng-Jie Cui; Yu Li; Lixin Lu; Ismail Khan; Abdul Jalal; Ming Fang; Khulood Fahad Alabbosh; Mohamed F. Awad; Noureddine Elboughdiri; Muhammad Wajid Ullah (Food Bioscience, 2024)

Inhibition of ER stress using tauroursodeoxycholic acid rescues obesity-evoked cardiac remodeling and contractile anomalies through regulation of ferroptosis - Feng-Juan Li; Miyesaier Abudureyimu; Zeng-Hui Zhang; Jun Tao; Asli F. Ceylan; Jie Lin; Wei Yu; Russel J. Reiter; Milad Ashrafizadeh; Jun Guo; Jun Ren (Chemico-Biological Interactions, 2024)

Adsorption Performance of Chitosan and Glutaraldehyde Modified Biochars for Trivalent Antimony in Acidic Wastewater - Huifang Lei; Nora F. Y. Tam; Xinhua Geng; Meiling Zhong; Xiaolan Lao; Xiaotong Su; Xuexia Huang; Lezhang Wei; Yu Liu; Qihang Wu; Ying-heng Fei; Dinggui Luo; et al. (Water, Air, & Soil Pollution, 2024)

Transversely Isotropic Slates Subject to the Compressive Differential Cyclic Loading, Part I: Experimental Investigations - Z. Y. Song; T. Zhang; W. G. Dang; P. Hamdi; F. Song; Z. H. Yu; Z. Yang (Rock Mechanics and Rock Engineering, 2024)

The first ensemble of kilometer-scale simulations of a hydrological year over the third pole - Emily Collier; Nikolina Ban; Niklas Richter; Bodo Ahrens; Deliang Chen; Xingchao Chen; Hui-Wen Lai; Ruby Leung; Lu Li; Alzbeta Medvedova; Tinghai Ou; Praveen Kumar Pothapakula; et al. (Climate Dynamics, 2024)
An accurate understanding of the current and future water cycle over the Third Pole is of great societal importance, given the role this region plays as a water tower for densely populated areas downstream. An emerging and promising approach for skillful climate assessments over regions of complex terrain is kilometer-scale climate modeling. As a foundational step towards such simulations over the Third Pole, we present a multi-model and multi-physics ensemble of kilometer-scale regional simulations for the hydrological year of October 2019 to September 2020. The ensemble consists of 13 simulations performed by an international consortium of 10 research groups, configured with a horizontal grid spacing ranging from 2.2 to 4 km covering all of the Third Pole region. These simulations are driven by ERA5 and are part of a Coordinated Regional Climate Downscaling EXperiment Flagship Pilot Study on Convection-Permitting Third Pole. The simulations are compared against available gridded and in-situ observations and remote-sensing data, to assess the performance and spread of the model ensemble compared to the driving reanalysis during the cold and warm seasons. Although ensemble evaluation is hindered by large differences between the gridded precipitation datasets used as a reference over this region, we show that the ensemble improves on many warm-season precipitation metrics compared with ERA5, including most wet-day and hour statistics, and also adds value in the representation of wet spells in both seasons. As such, the ensemble will provide an invaluable resource for future improvements in the process understanding of the hydroclimate of this remote but important region.

The Influence of Metabolites of Microorganisms of the Genus Bacillus from Permafrost Rocks on T Lymphocyte Differentiation - S. A. Petrov; Yu. G. Sukovey; L. F. Kalenova; E. G. Kostolomova; A. M. Subbotin; M. V. Narushko; A. S. Bazhin (Bulletin of Experimental Biology and Medicine, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Specificity of Aptamers U2 and Gol1 to EGFR-Positive Human Glioblastoma Cells in Vitro - F. M. Dzarieva; D. V. Shamadykova; O. V. Sluchanko; S. A. Pavlova; L. V. Fab; A. V. Ryabova; D. Yu. Panteleev; A. M. Kopylov; D. Yu. Usachev; A. V. Golovin; G. V. Pavlova (Neuroscience and Behavioral Physiology, 2024)

Ensemble learning using multivariate variational mode decomposition based on the Transformer for multi-step-ahead streamflow forecasting - Jinjie Fang; Linshan Yang; Xiaohu Wen; Haijiao Yu; Weide Li; Jan F. Adamowski; Rahim Barzegar (Journal of Hydrology, 2024)

Antidepressant-related microstructural changes in the external capsule - Ariel Kerpel; Elizabeth Davenport; Amy L. Proskovec; Yin Xi; Jarett D. Berry; Zerrin Yetkin; Joseph Maldjian; Fang F. Yu (Brain Imaging and Behavior, 2024)

To and fro in the archipelago: Repeated inter-island dispersal and New Guinea’s orogeny affect diversification of Delias, the world’s largest butterfly genus - Weijun Liang; Renato Nunes; Jing V. Leong; Ana Paula S. Carvalho; Chris J. Müller; Michael F. Braby; Olivier Pequin; Sugihiko Hoshizaki; Sadaharu Morinaka; Djunijanti Peggie; Jade Aster T. Badon; Alma B. Mohagan; et al. (Molecular Phylogenetics and Evolution, 2024)

Associations of prenatal ambient air pollution exposures with asthma in middle childhood - Marnie F. Hazlehurst; Kecia N. Carroll; Paul E. Moore; Adam A. Szpiro; Margaret A. Adgent; Logan C. Dearborn; Allison R. Sherris; Christine T. Loftus; Yu Ni; Qi Zhao; Emily S. Barrett; Ruby H.N. Nguyen; et al. (International Journal of Hygiene and Environmental Health, 2024)

Experimental Modeling of Cranial Injury and Defect Reconstruction Using Superconstructive Polymers (PEEK) - F. M. Shakova; G. A. Romanova; S. Yu. Khashirova; A. S. Vindizheva; Kh.V. Mashukov; M. V. Gulyaev; Z. B. Semenova (Bulletin of Experimental Biology and Medicine, 2024)

Antiplatelet and Antithrombotic Properties of Compound L-36, a 6H-1,3,4-Thiadiazine Derivative - V. S. Sirotenko; A. A. Spasov; A. F. Kucheryavenko; K. A. Gaidukova; A. V. Smirnov; Yu. I. Velikorodnaya (Bulletin of Experimental Biology and Medicine, 2024)

Unearthing the soil‐borne microbiome of land plants - Raúl Ochoa‐Hueso; David J. Eldridge; Miguel Berdugo; Pankaj Trivedi; Blessing Sokoya; Concha Cano‐Díaz; Sebastian Abades; Fernando Alfaro; Adebola R. Bamigboye; Felipe Bastida; José L. Blanco‐Pastor; Asunción de los Rios; et al. (Global Change Biology, 2024)
Plant–soil biodiversity interactions are fundamental for the functioning of terrestrial ecosystems. Yet, the existence of a set of globally distributed topsoil microbial and small invertebrate organisms consistently associated with land plants (i.e., their consistent soil‐borne microbiome), together with the environmental preferences and functional capabilities of these organisms, remains unknown. We conducted a standardized field survey under 150 species of land plants, including 58 species of bryophytes and 92 of vascular plants, across 124 locations from all continents. We found that, despite the immense biodiversity of soil organisms, the land plants evaluated only shared a small fraction (less than 1%) of all microbial and invertebrate taxa that were present across contrasting climatic and soil conditions and vegetation types. These consistent taxa were dominated by generalist decomposers and phagotrophs and their presence was positively correlated with the abundance of functional genes linked to mineralization. Finally, we showed that crossing environmental thresholds in aridity (aridity index of 0.65, i.e., the transition from mesic to dry ecosystems), soil pH (5.5; i.e., the transition from acidic to strongly acidic soils), and carbon (less than 2%, the lower limit of fertile soils) can result in drastic disruptions in the associations between land plants and soil organisms, with potential implications for the delivery of soil ecosystem processes under ongoing global environmental change.

The relationship between alcohol consumption and amygdala volume in a community-based sample - Christine Pho; Fang F. Yu; Jayme M. Palka; E. Sherwood Brown (Brain Imaging and Behavior, 2024)

Mineral diagenesis in lacustrine organic-rich shales: Evolution pathways and implications for reservoir characteristics - Yu Yan; Min Wang; David Misch; Reinhard F. Sachsenhofer; Yan Wu; Jinbu Li (Journal of Asian Earth Sciences, 2024)

Changes in the Transcription of Proliferation- and Apoptosis-Related Genes in Embryos in Women of Different Ages under the Influence of Extracellular Vesicles from Donor Follicular Fluid In Vitro - O. S. Nepsha; O. V. Burmenskaya; Z. F. Akhmedova; E. A. Romanov; A. P. Sysoeva; K. V. Goryunov; Yu. A. Shevtsova; D. N. Silachev; N. P. Makarova; E. A. Kalinina (Bulletin of Experimental Biology and Medicine, 2024)

Traffic-related air pollution, chronic stress, and changes in exhaled nitric oxide and lung function among a panel of children with asthma living in an underresourced community - N. Ji; A. Baptista; C.H. Yu; C. Cepeda; F. Green; M. Greenberg; I. Colon Mincey; P. Ohman-Strickland; N. Fiedler; H.M. Kipen; R.J. Laumbach (Science of The Total Environment, 2024)

Modular ocean trace elements sampling for the international GEOTRACES studies – Evidence from analysis of dissolved Fe and Pb - J. Zhang; Z.T. Ni; J.L. Ren; F. Yu; X.Y. Diao; Y. Wang; S.J. Zhang; H. Su; S.L. Cong; Z.J. Lu; S. Jiang; J. Ou; et al. (Progress in Oceanography, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Long-term ozone exposure and lung function in middle childhood - Marnie F. Hazlehurst; Logan C. Dearborn; Allison R. Sherris; Christine T. Loftus; Margaret A. Adgent; Adam A. Szpiro; Yu Ni; Drew B. Day; Joel D. Kaufman; Neeta Thakur; Rosalind J. Wright; Sheela Sathyanarayana; et al. (Environmental Research, 2024)

O-GlcNAc modification of GSDMD attenuates LPS-induced endothelial cells pyroptosis - Fan Yu; Zhen Zhang; Yiping Leng; Alex F. Chen (Inflammation Research, 2024)
Objective Increased O -linked β- N -acetylglucosamine ( O -GlcNAc) stimulation has been reported to protect against sepsis associated mortality and cardiovascular derangement. Previous studies, including our own research, have indicated that gasdermin-D(GSDMD)-mediated endothelial cells pyroptosis contributes to sepsis-associated endothelial injury. This study explored the functions and mechanisms of O -GlcNAc modification on lipopolysaccharide (LPS)-induced pyroptosis and its effects on the function of GSDMD. Methods A LPS-induced septic mouse model administrated with O -GlcNAcase (OGA) inhibitor thiamet-G (TMG) was used to assess the effects of O -GlcNAcylation on sepsis-associated vascular dysfunction and pyroptosis. We conducted experiments on human umbilical vein endothelial cells (HUVECs) by challenging them with LPS and TMG to investigate the impact of O -GlcNAcylation on endothelial cell pyroptosis and implications of GSDMD. Additionally, we identified potential O -GlcNAcylation sites in GSDMD by utilizing four public O -GlcNAcylation site prediction database, and these sites were ultimately established through gene mutation. Results Septic mice with increased O -GlcNAc stimulation exhibited reduced endothelial injury, GSDMD cleavage (a marker of pyroptosis). O -GlcNAc modification of GSDMD mitigates LPS-induced pyroptosis in endothelial cells by preventing its interaction with caspase-11 (a human homologous of caspases-4/5). We also identified GSDMD Serine 338 (S338) as a novel site of O -GlcNAc modification, leading to decreased association with caspases-4 in HEK293T cells. Conclusions Our findings identified a novel post-translational modification of GSDMD and elucidated the O -GlcNAcylation of GSDMD inhibits LPS-induced endothelial injury, suggesting that O -GlcNAc modification-based treatments could serve as potential interventions for sepsis-associated vascular endothelial injury.

Morphofunctional State of the Ovaries in Rats with Experimental Model of Functional Cysts and Their Treatment with Gonadotropin-Releasing Hormone Antagonist - O. S. Timofeeva; S. V. Logvinov; I. A. Petrov; O. A. Tikhonovskaya; Yu. G. Samoilova; Zh. F. Gaifulina; L. R. Mustafina; M. S. Petrova; A. A. Zhdankina; I. G. Kutsenko; D. A. Kudlay; K. A. Sidorenkova (Bulletin of Experimental Biology and Medicine, 2024)

Effect of Gonadotropin-Releasing Hormone Antagonist on the Expression Patterns of Insulin-Like Growth Factor 1, Androgen Receptor, and Luteinizing Hormone Receptor in an Experimental Rat Model of Functional Ovarian Cysts - O. S. Timofeeva; S. V. Logvinov; I. A. Petrov; O. A. Tikhonovskaya; Yu. G. Samoilova; Zh. F. Gaifulina; L. R. Mustafina; M. S. Petrova; A. A. Zhdankina; I. G. Kutsenko; D. A. Kudlay; K. A. Sidorenkova (Bulletin of Experimental Biology and Medicine, 2024)

Interfacial adsorption of gold nanoparticles on arsenian pyrite: New insights for the transport and deposition of gold nanoparticles - Xin Nie; Quan Wan; Michael F. Hochella; Suxing Luo; Meizhi Yang; Shanshan Li; Yuhong Fu; Ping Zeng; Zonghua Qin; Wenbin Yu (Chemical Geology, 2023)

Single nucleotide polymorphism rs527236194 of the cytochrome B gene (MT-CYB) is associated with alterations in sperm parameters - Yulia Yu. Gromenko; Kamil S. Galimov; Irina R. Gilyazova; Elmira F. Galimova; Kirill V. Bulygin; Sergey N. Ryagin; Shamil N. Galimov; Peter F. Litvitskiy; Gennadii A. Piavchenko; Valentin N. Pavlov (Molecular Biology Reports, 2023)

Recombinant Pneumolysin of Pneumococci Induces TLR4 Expression and Maturation of Dendritic Cells In Vitro - N. K. Akhmatova; D. S. Vorobyev; E. S. Petukhova; I. B. Semenova; I. V. Yakovleva; N. F. Gavrilova; A. E. Zaitsev; E. A. Akhmatova; Yu.V. Volokh; A. Yu. Leonova; A. V. Poddubikov; E. A. Kurbatova (Bulletin of Experimental Biology and Medicine, 2023)

Insights on aerosol properties using two decades-long ground-based remote sensing datasets in Moldova, Eastern Europe - Dipesh Rupakheti; Alexandr Aculinin; Maheswar Rupakheti; Sishir Dahal; Mukesh Rai; Xiufeng Yin; Xingna Yu; Sabur F. Abdullaev; Jianlin Hu (Environmental Pollution, 2023)

Nitrogen from agriculture and temperature as the major drivers of deoxygenation in the central Bohai Sea - Fuxia Yang; Hao Wang; Alexander F. Bouwman; Arthur H.W. Beusen; Xiaochen Liu; Junjie Wang; Zhigang Yu; Qingzhen Yao (Science of The Total Environment, 2023)

On the development of a generalized atmospheric boundary layer velocity profile for offshore engineering applications considering wind–wave interaction - Jamie F. Townsend; Guoji Xu; Yuanjie Jin; Enbo Yu; Huan Wei; Yan Han (Ocean Engineering, 2023)

Origin of carbonate melts in orogenic belts by anatexis of downthrust carbonate sediments - Chengyuan Wang; Stephen F. Foley; Yongsheng Liu; Yu Wang; Yi-Gang Xu (Earth and Planetary Science Letters, 2023)

The Role of Inflammation in the Development of Diabetic Polyneuropathy and the Potential for Its Correction - L. A. Shchepankevich; M. A. Pervuninskaya; I. A. Gribacheva; T. F. Popova; Yu. A. Nicolaev; E. V. Taneeva; E. V. Petrova; M. S. Shchepankevich (Neuroscience and Behavioral Physiology, 2023)

Determination of DNA architecture of bacteria under various types of stress, methodological approaches, problems, and solutions - Yu. F. Krupyanskii (Biophysical Reviews, 2023)

The genome-wide characterization and associated cold-tolerance function of the superoxide dismutase in the cold response of the tick Haemaphysalis longicornis - Zhijun Yu; Ruotong Wang; Tianai Zhang; Tongxuan Wang; Chuks F. Nwanade; Tingwei Pei; Ruwei Bai; Zihao Wang; Jingze Liu (Pesticide Biochemistry and Physiology, 2023)

Optimal maintenance planning for offshore wind farms under an uncertain environment - Tai-Sheng Su; Xin-Yu Weng; Vincent F. Yu; Chin-Chun Wu (Ocean Engineering, 2023)

Distribution of micronutrients in Arborg oat (Avena sativa L.) using synchrotron X-ray fluorescence imaging - Ganqi Deng; Miranda Vu; Malgorzata Korbas; Viorica F. Bondici; Chithra Karunakaran; David Christensen; H.A. Bart Lardner; Peiqiang Yu (Food Chemistry, 2023)

Ischemia-Modified Albumin and Antioxidant Protection in Newborns with Asphyxia of Varying Severity - S. F. Delsuz; R. I. Shalina; E. Ya. Karaganova; M. A. Kurtser; I. V. Babenkova; Yu. O. Teselkin; A. N. Osipov; Yu. A. Vladimirov (Bulletin of Experimental Biology and Medicine, 2023)

Comparative study of calcification in human choroid plexus, pineal gland, and habenula - O. Junemann; A. G. Ivanova; I. Bukreeva; D. A. Zolotov; M. Fratini; A. Cedola; F. Wilde; I. G. Dyachkova; Yu. S. Krivonosov; D. A. Otlyga; S. V. Saveliev (Cell and Tissue Research, 2023)

Perturbations in the characteristics of ionospheric HF radio waves during the April 11, 2019, earthquake in Japan: Results from oblique sounding - Leonid F. Chernogor; Kostyantyn P. Garmash; Qiang Guo; Victor T. Rozumenko; Yu Zheng (Advances in Space Research, 2023)

Sex-dependent associations of plasma high-density lipoprotein cholesterol and mortality risk in healthy older men and women: two prospective cohort studies - Sultana Monira Hussain; Andrew M Tonkin; Gerald F Watts; Paul Lacaze; Chenglong Yu; Lawrence J Beilin; Zhen Zhou; Anne B Newman; Johannes T Neumann; Cammie Tran; John J McNeil (GeroScience, 2023)
The relationship between high plasma high-density lipoprotein cholesterol (HDL-C) and cause and mortality are not well established in healthy older people. This study examined the associations between HDL-C levels and mortality in initially healthy older men and women. This analysis included participants from the Aspirin in Reducing Events in the Elderly (ASPREE; n =18,668) trial and a matched cohort from the UK Biobank (UKB; n =62,849 ≥65 years). Cox regression was used to examine hazard ratios between HDL-C categories <1.03 mmol/L, 1.03–1.55 mmol/L (referent category), 1.55–2.07 mmol/L, and >2.07 mmol/L and all-cause, cancer, cardiovascular disease (CVD), and “non-cancer non-CVD” mortality. Genetic contributions were assessed using a polygenic score for HDL-C. Among ASPREE participants (aged 75±5 years), 1836 deaths occurred over a mean follow-up of 6.3±1.8 years. In men, the highest category of HDL-C levels was associated with increased risk of all-cause (HR 1.60, 95% CI 1.26–2.03), cancer (HR 1.37, 95% CI 0.96–2.00), and “non-cancer non-CVD” mortality (HR 2.35, 95% CI 1.41–3.42) but not CVD mortality (HR 1.08, 95% CI 0.60–1.94). The associations were replicated among UKB participants (aged 66.9±1.5 years), including 8739 deaths over a mean follow-up of 12.7±0.8 years. There was a non-linear association between HDL-C levels and all-cause and cause-specific mortality. The association between HDL-C levels and mortality was unrelated to variations in the HDL-C polygenic score. No significant association was found between HDL-C levels and mortality in women. Higher HDL-C levels are associated with increased risk from cancer and “non-cancer non-CVD” mortality in healthy older men but no such relationship was observed in women.

Diverse nature of the seasonally coastal eutrophication dominated by oceanic nutrients: An eco-system based analysis characterized by salmon migration and aquaculture - Jing Zhang; Pavel Ya Tishchenko; Zeng Jie Jiang; Pavel Yu. Semkin; Petr P. Tishchenko; Wei Zheng; Vyacheslav B. Lobanov; Alexander F. Sergeev; Shan Jiang (Marine Pollution Bulletin, 2023)

Chlorpyrifos fate in the Arctic: Importance of analyte structure in interactions with Arctic dissolved organic matter - Lauren E. O'Connor; Pippin Robison; Ginna Quesada; Jill F. Kerrigan; Robyn C. O'Halloran; Jennifer J. Guerard; Yu-Ping Chin (Water Research, 2023)

Synthesis, antiviral evaluation, molecular docking study and cytotoxicity of 5′-phosphorylated 1,2,3-triazolyl nucleoside analogues with thymine and 6-methyl uracil moieties - Bulat F. Garifullin; Dmitry A. Tatarinov; Olga V. Andreeva; Mayya G. Belenok; Irina Yu. Strobykina; Leysan R. Khabibulina; Anna V. Shepelina; Vladimir V. Zarubaev; Alexander V. Slita; Alexandrina S. Volobueva; Alexandra D. Voloshina; Anna P. Lyubina; et al. (Medicinal Chemistry Research, 2023)

Rapidly dissolving bilayer microneedles enabling minimally invasive and efficient protein delivery to the posterior segment of the eye - Yu Wu; Lalitkumar K. Vora; Ryan F. Donnelly; Thakur Raghu Raj Singh (Drug Delivery and Translational Research, 2023)
The discovery of proteins that neutralise vascular endothelial growth factors, such as pegaptanib, ranibizumab and aflibercept, can inhibit the process of angiogenesis, thereby restoring eyesight in individuals with retinal vascular disorders. However, due to the posterior location and chronic nature of retinal diseases, a safe and effective intraocular protein delivery system is currently lacking. Thus, dissolving bilayer microneedles (MNs) with the potential to deliver proteins to the back of the eye in an efficient and minimally invasive manner were developed in this study. A model protein, ovalbumin (OVA), was incorporated into MNs fabricated from different polymers, including hyaluronic acid (HA), polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP). Optimised PVA/PVP MNs were demonstrated to be robust enough to pierce porcine sclera with > 75% of the needle length penetrating the sclera and dissolving within 150 s. SDS-PAGE and OVA-specific ELISA revealed that the bioactivity of the model protein was maintained during the manufacture of MNs. In hen’s egg-chorioallantoic membrane test, MNs fabricated from all chosen polymers were classified as non-irritants. Furthermore, ex vivo permeation studies showed that optimised MNs could permeate 86.99 ± 7.37% of OVA through the sclera, twice that of the needle-free patch (42.16 ± 3.95%), highlighting the capability of MNs to circumvent physical barriers and promote protein delivery to the posterior segment of the eye. In this work, a novel, efficient and safe intraocular protein delivery system was successfully established. Graphical abstract

Aggregation kinetics and stability of biodegradable nanoplastics in aquatic environments: Effects of UV-weathering and proteins - Yingxue Yu; Anton F. Astner; Tahsin Md. Zahid; Indranil Chowdhury; Douglas G. Hayes; Markus Flury (Water Research, 2023)

Formation, behavior, properties and impact of micro- and nanoplastics on agricultural soil ecosystems (A Review) - Anton F. Astner; Alexis B. Gillmore; Yingxue Yu; Markus Flury; Jennifer M. DeBruyn; Sean M. Schaeffer; Douglas G. Hayes (NanoImpact, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

The Euwallacea fornicatus species complex (Coleoptera: Curculionidae); emerging economic pests of tea in Taiwan - Yi-Chang Liao; Fang-Ling Liu; Paul F. Rugman-Jones; Deena Husein; Hui-Hung Liang; Yu-Hung Yang; Chun-Yen Lee; Lan-Yu Liu; Shu-Jen Tuan; Richard Stouthamer (Crop Protection, 2023)

Divergent spatiotemporal variability of terrestrial water storage and eight hydroclimatic components over three different scales of the Yangtze River basin - Nengfang Chao; Fupeng Li; Nan Yu; Gang Chen; Zhengtao Wang; Guichong Ouyang; Pat J.-F. Yeh (Science of The Total Environment, 2023)

Immunopatological and Genetic Aspects of the Pathogenesisof CNS Lesions in VZV Infection - E. Yu. Skripchenko; G. F. Zheleznikova; N. V. Skripchenko; L. A. Alekseeva; O. V. Goleva; T. V. Bessonova; A. A. Zhirkov (Neuroscience and Behavioral Physiology, 2023)

Biophysical Factors Influence Methane Fluxes in Subtropical Freshwater Wetlands Using Eddy Covariance Methods - Zhuoran Yu; Christina L. Staudhammer; Sparkle L. Malone; Steven F. Oberbauer; Junbin Zhao; Julia A. Cherry; Gregory Starr (Ecosystems, 2023)

Effect of Activated Immunocompetent Cells on the Content of Multipotent Stromal Cells in Splenic Transplants of CBA and CBA/N Mice Administered with Polyvinylpyrrolidone - Yu. F. Gorskaya; A. I. Tukhvatulin; A. Sh. Dzharullaeva; E. N. Semenova; L. M. Vavilova; E. V. Nagurskaya; V. A. Bekhalo; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2023)

Sediment-moving winds and abrasion on Titan: Implications for yardangs - Shannon M. MacKenzie; Kirby D. Runyon; Xinting Yu; Jasper F. Kok; Claire Newman; Ralph D. Lorenz; Francesco Comola (Icarus, 2023)

Competitive advantages of HAB species under changing environmental conditions in the coastal waters of the Bohai Sea, Yellow Sea and East China Sea - Hao Wang; Alexander F. Bouwman; Junjie Wang; Zhigang Yu; Xiangbin Ran (Continental Shelf Research, 2023)

Determining meteorologically-favorable zones for seasonal influenza activity in Hong Kong - Ka Chun Chong; Paul K. S. Chan; Tsz Cheung Lee; Steven Y. F. Lau; Peng Wu; Christopher K. C. Lai; Kitty S. C. Fung; Cindy W. S. Tse; Shuk Yu Leung; Ka Li Kwok; Conglu Li; Xiaoting Jiang; et al. (International Journal of Biometeorology, 2023)

The loss of cardiac SIRT3 decreases metabolic flexibility and proteostasis in an age-dependent manner - Ping Li; Maria F. Newhardt; Satoshi Matsuzaki; Craig Eyster; Atul Pranay; Frederick F. Peelor; Albert Batushansky; Caroline Kinter; Kumar Subramani; Sandeep Subrahmanian; Jasimuddin Ahamed; Pengchun Yu; et al. (GeroScience, 2023)
SIRT3 is a longevity factor that acts as the primary deacetylase in mitochondria. Although ubiquitously expressed, previous global SIRT3 knockout studies have shown primarily a cardiac-specific phenotype. Here, we sought to determine how specifically knocking out SIRT3 in cardiomyocytes (SIRTcKO mice) temporally affects cardiac function and metabolism. Mice displayed an age-dependent increase in cardiac pathology, with 10-month-old mice exhibiting significant loss of systolic function, hypertrophy, and fibrosis. While mitochondrial function was maintained at 10 months, proteomics and metabolic phenotyping indicated SIRT3 hearts had increased reliance on glucose as an energy substrate. Additionally, there was a significant increase in branched-chain amino acids in SIRT3cKO hearts without concurrent increases in mTOR activity. Heavy water labeling experiments demonstrated that, by 3 months of age, there was an increase in protein synthesis that promoted hypertrophic growth with a potential loss of proteostasis in SIRT3cKO hearts. Cumulatively, these data show that the cardiomyocyte-specific loss of SIRT3 results in severe pathology with an accelerated aging phenotype.

Bioturbation in sediment cores from the Clarion-Clipperton Zone in the northeast Pacific: Evidence from excess 210Pb - W. Yu; F. Lin; L. Lin (Marine Pollution Bulletin, 2023)

Hindcasting harmful algal bloom risk due to land-based nutrient pollution in the Eastern Chinese coastal seas - Hao Wang; Alexander F. Bouwman; Jos Van Gils; Lauriane Vilmin; Arthur H.W. Beusen; Junjie Wang; Xiaochen Liu; Zhigang Yu; Xiangbin Ran (Water Research, 2023)

Human-driven long-term disconnect of nutrient inputs to the Yellow River basin and river export to the Bohai Sea - Fuxia Yang; Zhigang Yu; Alexander F. Bouwman; Hongtao Chen; Huimin Jian; Arthur H.W. Beusen; Xiaochen Liu; Qingzhen Yao (Journal of Hydrology, 2023)

Transition from tholeiitic to alkali basalts via interaction between decarbonated eclogite-derived melts and peridotite - Qiuhong Xie; Zhaochong Zhang; Stephen F. Foley; Chunfei Chen; Zhiguo Cheng; Yu Wang; Weiliang Kong; Yiwen Lv; M. Santosh; Qizhen Jin; Lukáš Krmíček; Xiangkun Zhu (Chemical Geology, 2023)

DNA sequence-specific ligands. XX. Synthesis, spectral properties, virological and biochemical studies of fluorescent dimeric trisbenzimidazoles DB3P(n) - Albert F. Arutyunyan; Alexey A. Kostyukov; Vladislav A. Lushpa; Konstantin S. Mineev; Sergey P. Korolev; Marina B. Gottikh; Regina R. Klimova; Alla A. Kushch; Kseniya V. Kalabina; Olga Yu. Susova; Alexei L. Zhuze (Medicinal Chemistry Research, 2023)

Eu(III) sorption on kaolinite: Experiments and modeling - Anna S. Semenkova; Anna Yu. Romanchuk; Irina F. Seregina; Ivan Mikheev; Valentina S. Svitelman; Stepan N. Kalmykov (Applied Clay Science, 2023)

The Role of the Dentate Gyrus in Mediating Hippocampal Functions: The Epileptic Brain - V. F. Kitchigina; L. V. Shubina; I. Yu. Popova (Neuroscience and Behavioral Physiology, 2023)

The Role of the Dentate Gyrus in Mediating Hippocampal Functions: The Healthy Brain - V. F. Kitchigina; L. V. Shubina; I. Yu. Popova (Neuroscience and Behavioral Physiology, 2023)

Integrating oculomics with genomics reveals imaging biomarkers for preventive and personalized prediction of arterial aneurysms - Yu Huang; Cong Li; Danli Shi; Huan Wang; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Yijun Hu; Shulin Tang; Shunming Liu; Songyuan Luo; et al. (EPMA Journal, 2023)
Objective Arterial aneurysms are life-threatening but usually asymptomatic before requiring hospitalization. Oculomics of retinal vascular features (RVFs) extracted from retinal fundus images can reflect systemic vascular properties and therefore were hypothesized to provide valuable information on detecting the risk of aneurysms. By integrating oculomics with genomics, this study aimed to (i) identify predictive RVFs as imaging biomarkers for aneurysms and (ii) evaluate the value of these RVFs in supporting early detection of aneurysms in the context of predictive, preventive and personalized medicine (PPPM). Methods This study involved 51,597 UK Biobank participants who had retinal images available to extract oculomics of RVFs. Phenome-wide association analyses (PheWASs) were conducted to identify RVFs associated with the genetic risks of the main types of aneurysms, including abdominal aortic aneurysm (AAA), thoracic aneurysm (TAA), intracranial aneurysm (ICA) and Marfan syndrome (MFS). An aneurysm-RVF model was then developed to predict future aneurysms. The performance of the model was assessed in both derivation and validation cohorts and was compared with other models employing clinical risk factors. An RVF risk score was derived from our aneurysm-RVF model to identify patients with an increased risk of aneurysms. Results PheWAS identified a total of 32 RVFs that were significantly associated with the genetic risks of aneurysms. Of these, the number of vessels in the optic disc (‘ntreeA’) was associated with both AAA ( β = −0.36, P = 6.75e−10) and ICA ( β = −0.11, P = 5.51e−06). In addition, the mean angles between each artery branch (‘curveangle_mean_a’) were commonly associated with 4 MFS genes ( FBN1 : β = −0.10, P = 1.63e−12; COL16A1 : β = −0.07, P = 3.14e−09; LOC105373592 : β = −0.06, P = 1.89e−05; C8orf81/LOC441376 : β = 0.07, P = 1.02e−05). The developed aneurysm-RVF model showed good discrimination ability in predicting the risks of aneurysms. In the derivation cohort, the C -index of the aneurysm-RVF model was 0.809 [95% CI: 0.780–0.838], which was similar to the clinical risk model (0.806 [0.778–0.834]) but higher than the baseline model (0.739 [0.733–0.746]). Similar performance was observed in the validation cohort, with a C -index of 0.798 (0.727–0.869) for the aneurysm-RVF model, 0.795 (0.718–0.871) for the clinical risk model and 0.719 (0.620–0.816) for the baseline model. An aneurysm risk score was derived from the aneurysm-RVF model for each study participant. The individuals in the upper tertile of the aneurysm risk score had a significantly higher risk of aneurysm compared to those in the lower tertile (hazard ratio = 17.8 [6.5–48.8], P = 1.02e−05). Conclusion We identified a significant association between certain RVFs and the risk of aneurysms and revealed the impressive capability of using RVFs to predict the future risk of aneurysms by a PPPM approach. Our finds have great potential to support not only the predictive diagnosis of aneurysms but also a preventive and more personalized screening plan which may benefit both patients and the healthcare system. Graphical abstract

A photosensitive composition based on an aromatic polyamide for LCD 4D printing of shape memory mechanically robust materials - Bato Ch. Kholkhoev; Kseniia N. Bardakova; Evgeniy O. Epifanov; Zakhar A. Matveev; Taisiya A. Shalygina; Evgeniy B. Atutov; Svetlana Yu. Voronina; Peter S. Timashev; Vitaliy F. Burdukovskii (Chemical Engineering Journal, 2023)

A deleterious Sar1c variant in rice inhibits export of seed storage proteins from the endoplasmic reticulum - Xiuhao Bao; Yongfei Wang; Yanzhou Qi; Cailin Lei; Yunlong Wang; Tian Pan; Mingzhou Yu; Yu Zhang; Hongming Wu; Pengcheng Zhang; Yi Ji; Hang Yang; et al. (Plant Molecular Biology, 2023)

The Role of Bilingualism in the Formation of Neurocognitive Reserve - A. S. Malyshevskaya; F. Gallo; A. A. Efremov; A. V. Myachykov; Yu. Yu. Shtyrov (Neuroscience and Behavioral Physiology, 2023)

Porphyry-epithermal Cu-Mo-Au–Ag mineralization in the Nakhodka ore field, Baimka Trend, Chukotka, Russia: a geological, mineralogical, and geochemical perspective - Andrey F. Chitalin; Ivan A. Baksheev; Yurii N. Nikolaev; Ekaterina V. Nagornaya; Yuliya N. Khabibullina; Irina Yu. Nikolaeva; Ildar A. Kalko; Daniel Müller (Mineralium Deposita, 2023)

Nature and evolution of diagenetic fluids in the deeply buried Cambrian Xiaoerbulake Formation, Tarim Basin, China - T. Y. Wei; C. F. Cai; Y. J. Hu; H. Y. Yu; D. W. Liu; Z. W. Jiang; D. W. Wang (Australian Journal of Earth Sciences, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

Characterization of columnar aerosol over a background site in Central Asia - Dipesh Rupakheti; Maheswar Rupakheti; Mukesh Rai; Xingna Yu; Xiufeng Yin; Shichang Kang; Musapar D. Orozaliev; Valery P. Sinyakov; Sabur F. Abdullaev; Ishaq Dimeji Sulaymon; Jianlin Hu (Environmental Pollution, 2023)

Structural characterization of SARS-CoV-2 dimeric ORF9b reveals potential fold-switching trigger mechanism - Xiyue Jin; Xue Sun; Yan Chai; Yu Bai; Ying Li; Tianjiao Hao; Jianxun Qi; Hao Song; Catherine C. L. Wong; George F. Gao (Science China Life Sciences, 2023)

Effects of Fragment ACTH15-18 and Its Analog ACTH15-18Pro-Gly-Pro on the Sequelae of Acute Stress - D. M. Manchenko; N. Yu. Glazova; E. A. Sebentsova; L. A. Andreeva; O. V. Dolotov; A. A. Kamensky; N. F. Myasoedov; N. G. Levitskaya (Neuroscience and Behavioral Physiology, 2023)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Methamphetamine-induced lethal toxicity in zebrafish larvae - Yu Chen; Alexander S. Wisner; Isaac T. Schiefer; Frederick E. Williams; F. Scott Hall (Psychopharmacology, 2022)

Electronic cigarette vaping with aged coils causes acute lung injury in mice - Shunsaku Goto; Robert M. H. Grange; Riccardo Pinciroli; Ivy A. Rosales; Rebecca Li; Sophie L. Boerboom; Katrina F. Ostrom; Eizo Marutani; Hatus V. Wanderley; Aranya Bagchi; Robert B. Colvin; Lorenzo Berra; et al. (Archives of Toxicology, 2022)

Effects of spatially heterogeneous lakeside development on nearshore biotic communities in a large, deep, oligotrophic lake - Michael F. Meyer; Ted Ozersky; Kara H. Woo; Kirill Shchapov; Aaron W. E. Galloway; Julie B. Schram; Emma J. Rosi; Daniel D. Snow; Maxim A. Timofeyev; Dmitry Yu. Karnaukhov; Matthew R. Brousil; Stephanie E. Hampton (Limnology and Oceanography, 2022)
Sewage released from lakeside development can reshape ecological communities. Nearshore periphyton can rapidly assimilate sewage‐associated nutrients, leading to increases of filamentous algal abundance, thus altering both food abundance and quality for grazers. In Lake Baikal, a large, ultra‐oligotrophic, remote lake in Siberia, filamentous algal abundance has increased near lakeside developments, and localized sewage input is the suspected cause. These shifts are of particular interest in Lake Baikal, where endemic littoral biodiversity is high, lakeside settlements are mostly small, tourism is relatively high (~1.2 million visitors annually), and settlements are separated by large tracts of undisturbed shoreline, enabling investigation of heterogeneity and gradients of disturbance. We surveyed sites along 40 km of Baikal's southwestern shore for sewage indicators—pharmaceuticals and personal care products (PPCPs) and microplastics—as well as periphyton and macroinvertebrate abundance and indicators of food web structure (stable isotopes and fatty acids). Summed PPCP concentrations were spatially related to lakeside development. As predicted, lakeside development was associated with more filamentous algae and lower abundance of sewage‐sensitive mollusks. Periphyton and macroinvertebrate stable isotopes and essential fatty acids suggested that food web structure otherwise remained similar across sites; yet, the invariance of amphipod fatty acid composition, relative to periphyton, suggested that grazers adjust behavior or metabolism to compensate for different periphyton assemblages. Our results demonstrate that even low levels of human disturbance can result in spatial heterogeneity of nearshore ecological responses, with potential for changing trophic interactions that propagate through the food web.

Experimental Correction of Homeostasis Changes during Alloxan-Induced Diabetes by Implantation of Islet Cells Cultured in Fibrous TiNi-Based Scaffold - O. V. Kokorev; I. A. Khlusov; E. S. Marchenko; Yu. F. Yasenchuk; G. Ts. Dambaev (Bulletin of Experimental Biology and Medicine, 2022)

Constitutive chitosanase from Bacillus thuringiensis B-387 and its potential for preparation of antimicrobial chitooligomers - Gleb E. Aktuganov; Violetta R. Safina; Nailya F. Galimzianova; Elena A. Gilvanova; Lyudmila Yu. Kuzmina; Alexander I. Melentiev; Andrei H. Baymiev; Sergey A. Lopatin (World Journal of Microbiology and Biotechnology, 2022)

A Population Pharmacokinetic Modelling Approach to Unravel the Complex Pharmacokinetics of Vincristine in Children - A. Laura Nijstad; Wan-Yu Chu; Evelien de Vos-Kerkhof; Catherine F. Enters-Weijnen; Mirjam E. van de Velde; Gertjan J. L. Kaspers; Shelby Barnett; Gareth J. Veal; Arief Lalmohamed; C. Michel Zwaan; Alwin D. R. Huitema (Pharmaceutical Research, 2022)
Background Vincristine, a chemotherapeutic agent that extensively binds to β-tubulin, is commonly dosed at 1.4–2.0 mg/m 2 capped at 2 mg. For infants, doses vary from 0.025–0.05 mg/kg or 50–80% of the mg/m 2 dose. However, evidence for lower doses in infants compared to older children is lacking. This study was conducted to unravel the complex pharmacokinetics of vincristine, including the effects of age, to assist optimal dosing in this population. Methods 206 patients (0.04–33.9 years; 25 patients < 1 years), receiving vincristine, with 1297 plasma concentrations were included. Semi-mechanistic population pharmacokinetic analyses were performed using non-linear mixed effects modelling. Results A three-compartment model, with one saturable compartment resembling saturable binding to β-tubulin and thus, saturable distribution, best described vincristine pharmacokinetics. Body weight and age were covariates significantly influencing the maximal binding capacity to β-tubulin, which increased with increasing body weight and decreased with increasing age. Vincristine clearance (CL) was estimated as 30.6 L/h (95% confidence interval (CI) 27.6–33.0), intercompartmental CL (Q) as 63.2 L/h (95%CI 57.2–70.1), volume of distribution of the central compartment as 5.39 L (95%CI 4.23–6.46) and of the peripheral compartment as 400 L (95%CI 357–463) (all parameters correspond to a patient of 70 kg). The maximal binding capacity was 0.525 mg (95%CI 0.479–0.602) (for an 18 year old patient of 70 kg), with a high association rate constant, fixed at 1300 /h and a dissociation constant of 11.5 /h. Interpretation A decrease of vincristine β-tubulin binding capacity with increasing age suggests that young children tolerate higher doses of vincristine.

Plant Growth Stimulating Bacteria and Filter Mud Cake Enhance Soil Quality and Productivity of Mango (Mangifera indica L.) - Yu Ge; Arwa Abdulkreem AL-Huqail; Zhaoxi Zhou; Esmat F. Ali; Adel M. Ghoneim; Mamdouh Eissa; Mahmoud S. El-Sharkawy; Zheli Ding (Journal of Soil Science and Plant Nutrition, 2022)

A fungal mycelium elicitor efficiently improved ginsenoside synthesis during adventitious root culture of Panax ginseng - X. L. An; Y. Yu; M. Z. Fan; X. H. Wu; X. F. Li; X. C. Piao; M. L. Lian (Journal of Plant Biochemistry and Biotechnology, 2022)

Control strategy of an all-electric cruise ship based on cycle life mode of lithium battery pack - R. Chen; W. Yu; C.-F. Yang (International Journal of Environmental Science and Technology, 2022)

Timing of Toenail Collection and Concentrations of Metals in Pancreatic Cancer. Evidence Against Disease Progression Bias - José Pumarega; Judit Camargo; Magda Gasull; Andrew F. Olshan; Amr Soliman; Yu Chen; David Richardson; Juan Alguacil; Charles Poole; Leonardo Trasande; Miquel Porta (Exposure and Health, 2022)

A Portable Optical Device for Assessing Platelet Aggregation Activity - Yu. D. Liushnevskaya; F. A. Gubarev; D. S. Slizevich (Biomedical Engineering, 2022)

Perinatal Metal and Metalloid Exposures and Offspring Cardiovascular Health Risk - Gyeyoon Yim; Lorena Reynaga; Velia Nunez; Caitlin G. Howe; Megan E. Romano; Yu Chen; Margaret R. Karagas; Claudia Toledo-Corral; Shohreh F. Farzan (Current Environmental Health Reports, 2022)

Rapamycin Enhanced Sensitivity of HT-29 Cells to 5-Fluororacil by Promoting Autophagy - S. Chen; J. Yang; F. Wang; X. Gao; Qiang Liu; Qian Liu; Y. Zhang; Y. Yu (Bulletin of Experimental Biology and Medicine, 2022)

NMR and dynamic light scattering give different diffusion information for short-living protein oligomers. Human serum albumin in water solutions of metal ions - A. M. Kusova; A. K. Iskhakova; Yu. F. Zuev (European Biophysics Journal, 2022)

Expression and Functional Role of Olfactory, Taste, and Phototransduction Signal Proteins in β Cells in Islets of Langerhans - Yu. A. Kovalitskaya; N. P. Kovalenko; M. F. Bystrova (Neuroscience and Behavioral Physiology, 2022)

A20 attenuates pyroptosis and apoptosis in nucleus pulposus cells via promoting mitophagy and stabilizing mitochondrial dynamics - Xin Peng; Cong Zhang; Zhi-Min Zhou; Kun Wang; Jia-Wei Gao; Zhan-Yang Qian; Jun-Ping Bao; Hang-Yu Ji; V. L. F. Cabral; Xiao-Tao Wu (Inflammation Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Search for New Target Genes of MicroRNA for Differential Diagnosis of Benign and Malignant Neoplasms of the Thyroid Gland by In Silico Methods - V. V. Kononchuk; E. V. Kopeikina; T. S. Kalinina; O. V. Saik; E. Yu. Alekseenok; M. K. Kolyagina; V. A. Matashova; S. P. Shevchenko; L. F. Gulyaeva; N. E. Kushlinskii (Bulletin of Experimental Biology and Medicine, 2022)

Low-field nuclear magnetic resonance detection of changes in the water distribution in citric acid biosludge during dewatering - Y. F. Liu; L. M. Dong; G. N. Cui; X. Y. Hu; Z. Q. Yu; S. Liang (International Journal of Environmental Science and Technology, 2022)

Waste rocks from the industrial mining process: hazard metals stabilization behavior evaluating and reusing as construction materials - E. Li; H. Chen; F. Huang; L. Zhou; Z. Yu (International Journal of Environmental Science and Technology, 2022)

LINC00839 Promotes the Progression of Gastric Cancer by Sponging miR-1236-3p - J. X. An; Z. S. Ma; W. J. Yu; B. J. Xie; F. S. Zhu; Y. X. Zhou; F. L. Cao (Bulletin of Experimental Biology and Medicine, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Alternative Splicing of the Lobster (Homarus americanus) Crustacean Hyperglycemic Hormone A and B Genes Produce 2 Protein Variants Involved in Vitellogenin Inhibition - Cheng Gui Wang; Wei Wang; Li Li Shi; Yu Chun Shen; Siuming F. Chan (Frontiers in Marine Science, 2022)
Current BLASTP search analysis results suggested that the lobster ( Homarus americanus ) HaCHH-A and HaCHH-B may be derived from two different four-exon genes. Repeated tissue expression studies have revealed much different expression patterns of these two genes from those reported in the past. With RT-PCR, rapid amplification of complementary DNA (cDNA) ends (RACE), and genomic DNA cloning, we confirmed that the HaCHH-A and HaCHH-B transcripts were derived from two different four-exon CHH genes. By an alternative splicing mechanism, each gene can produce different but larger transcript variants (i.e., sHaCHH-A and sHaCHH-B ) mainly in different non-eyestalk tissues of the females. The larger and unspliced transcripts can be detected in the hepatopancreas, gill, heart, nerve cord, brain, ovary, and thoracic ganglion of the reproductive females. The expression patterns of sHaCHH-A and sHaCHH-B in other non-eyestalk tissues suggest that these transcripts have a wide spectrum of expressions during the female reproductive cycle. An in vitro organ explant culture system was developed to investigate the reproductive function of these cDNAs. The results showed that the recombinant proteins for sHaCHH-A and sHaCHH-B inhibited the gene expression of vitellogenin, whereas the double-stranded RNA (dsRNA) for sHaCHH-A and sHaCHH-B stimulated the expression of the vitellogenin gene in vitro . The results of the study may provide insights for the development of techniques to induce gonad development without using eyestalk ablation operation. This is the first in-depth report of the characterization of two four-exon CHH genes in a crustacean.

Method development and evaluation for the determination of perfluoroalkyl and polyfluoroalkyl substances in multiple food matrices - Dorothea F. K. Rawn; Cathie Ménard; Sherry Yu Feng (Food Additives & Contaminants: Part A, 2022)

Capabilities on Remote Microwave Technologies to Assess the State of Water Systems - C. A. Varotsos; F. A. Mkrtchyan; V. Yu. Soldatov; Y. Xue (Water, Air, & Soil Pollution, 2022)

Environmental Regulation of Photosynthetically Produced Dissolved Organic Carbon by Phytoplankton Along a Subtropical Estuarine Bay - Jianhua Kang; Zhaohe Luo; Hala. F. Mohamed; Yili Lin; Shuhong Huang; Yu Wang; Wenlu Lan (Frontiers in Marine Science, 2022)
Photosynthetically produced dissolved organic carbon (PDOC) released by marine phytoplankton has an important significance on the marine carbon cycle and on the growth of heterotopic bacteria (HB). However, PDOC is often neglected in the estimation of global marine primary productivity and carbon sequestration capacity. This work studied the issue of PDOC and its environmental regulation mechanism through field investigation and lab experiments in an estuarine bay during southwest and northeast monsoon. We used the percentage of extracellular release (PER) as a key indicator to evaluate the contribution of PDOC to total primary productivity (TPP). We also compared PER among different seasons and sectors and then analyzed the inter-relationship between PDOC and bacterial carbon demand (BCD), size-fractionated phytoplankton, bacterial production (BP), and TPP. We finally discussed the impact factors of PDOC productivity. The results showed that the average contribution of PDOC to TPP in Qinzhou bay could reach 15% during two seasons, which satisfies about 25% of the carbon requirement by HB in the bay. Multiple factors contribute to the seasonal (SW monsoon 13% < NE monsoon 18%) and sectoral variation (outer bay 26% > middle bay 17% > inner bay 7%) in PER, the most significant of which are salinity and nitrogen to phosphorus ratios. PER is also related to phytoplankton community structure and nutrient limitation, the higher PER in the outer bay is attributed to the dual effect of picophytoplankton being the predominant species and a severe imbalance in the nitrogen to phosphorus ratio, both of which lead to increased phytoplankton PDOC release. On the other hand, the lower PER in the inner bay was mainly due to the dominance of microphytoplankton and nitrogen to phosphorus ratio which is close to the redfield ratio. There is still a non-uniform conclusion on the relationship between PER and TPP, suggesting that this relationship needs to be evaluated not only in a horizontal-independent way but also through seasonal and vertical dimensions. The non-linear relationship between PDOC and BCD found in this study potentially indicated weak coupling between phytoplankton exudation and bacterial metabolism. In addition to phytoplankton exudate, HB is still dependent on other sources of DOC to meet their carbon requirements.

Fast antibiotic susceptibility testing of urine microflora using a microbiological analyzer based on coherent fluctuation nephelometry - Alexander S Gur’ev; Margus Tigasson; Olga Yu Shalatova; Stanislav F Rastopov; Anastasia Bilozor; Marina Ivanova; Alexey Yu Volkov (Brazilian Journal of Microbiology, 2022)

Gene expression regulating the cell cycle and gene of antioxidant protection system in toxic hepatitis - Y. V. Valova; M. M. Ziatdinova; G. F. Mukhammadieva; D. O. Karimov; A. S. Fazlyeva; N. Yu. Khusnutdinova; T. G. Yakupova; E. F. Repina (Toxicology and Environmental Health Sciences, 2022)

The premature decay of rifting processes in the northern South China Sea (38–33.9 Ma): insight from 3D seismic and its interpretation of the Lufeng Sag of the Pearl River Mouth Basin - B. S. Ma; J. W. Ge; G. H. Wu; J. F. Qi; F. Yu; S. Chen; W. G. He (Australian Journal of Earth Sciences, 2022)

Correlation between Structural Transformations in Mesenteric Lymph Nodes and the Levels MicroRNA during Polychemotherapy of Breast Cancer - A. V. Kabakov; O. V. Kazakov; A. F. Poveshchenko; A. P. Lykov; T. V. Raiter; D. N. Strunkin; L. F. Gulyaeva; V. I. Konenkov; A. Yu. Letyagin (Bulletin of Experimental Biology and Medicine, 2022)

Keqinzhangia aquatica gen. et sp. nov. and Pseudocoronospora hainanense gen. et sp. nov., isolated from freshwater in southern China - Hua Zheng; Min Qiao; Jishu Guo; Rafael F. Castañeda-Ruiz; Jie Peng; Zefen Yu (Antonie van Leeuwenhoek, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Reparative and Immunomodulatory Potential of Low-Molecular-Weight Fractions of Secondary Metabolites of Bacillus sp. - L. F. Kalenova; S. A. Petrov; Yu. G. Sukhovei (Bulletin of Experimental Biology and Medicine, 2022)

Formation and track of tropical cyclones Eline (2000) and Bonita (1996) - Chaibo Jose Armando; Zhao Yu; Alberto F. Mavume; Victor Ongoma; Aston Matwayi Nyongesa (Meteorology and Atmospheric Physics, 2021)

Multilayer adsorption of organic dyes on coal tar-based porous carbon with ultra-high specific surface area - X. Wang; F. Huang; M. Yu; C. Zhang; F. Ding; L. Chen; H. Chen (International Journal of Environmental Science and Technology, 2021)

Cure of Mice with Advanced Ovarian Adenocarcinoma CaO1 by the Serum Blood Proteins - F. V. Donenko; S. M. Sitdikova; Yu. I. Dolzhikova; Yu. S. Lebedin (Bulletin of Experimental Biology and Medicine, 2021)

Simultaneous Administration of NOD-2 (MDP) and TLP-4 (LPS) Ligands to Bone Marrow Donors 24 h before Transplantation Increases the Content of Multipotent Stromal Cells (MSCs) in Bone Marrow Grafts in CBA Mice Compared to the Total Result of Their Isolated Administration - Yu. F. Gorskaya; E. N. Semenova; E. V. Nagurskaya; V. A. Bekhalo; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2021)

Association of Gasdermin B Gene GSDMB Polymorphisms with Risk of Allergic Diseases - Alexandra S. Karunas; Yuliya Yu. Fedorova; Galiya F. Gimalova; Esfir I. Etkina; Elza K. Khusnutdinova (Biochemical Genetics, 2021)

Age-Related Features of the Viscosity of Plasma and Mitochondrial Membranes of Hepatocytes in Liver Cirrhosis - E. G. Skurikhin; S. A. Afanas’ev; M. A. Zhukova; T. Yu. Rebrova; E. F. Muslimova; E. S. Pan; N. N. Ermakova; O. V. Pershina; A. V. Pakhomova; O. D. Putrova; L. A. Sandrikina; L. V. Kogai; et al. (Bulletin of Experimental Biology and Medicine, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Assessment of the Time Characteristics of Walking Techniques Using a Mobile Information and Measurement System - V. V. Alekseev; N. E. Ivanova; A. Yu. Ivanov; P. G. Korolev; F. M. Sokolova; A. V. Tsareva (Biomedical Engineering, 2021)

Water safety attitudes, risk perception, experiences, and education for households impacted by the 2018 Camp Fire, California - Tolulope O. Odimayomi; Caitlin R. Proctor; Qi Erica Wang; Arman Sabbaghi; Kimberly S. Peterson; David J. Yu; Juneseok Lee; Amisha D. Shah; Christian J. Ley; Yoorae Noh; Charlotte D. Smith; Jackson P. Webster; et al. (Natural Hazards, 2021)

Single-cell biology to decode the immune cellular composition of kidney inflammation - Yu Zhao; Ulf Panzer; Stefan Bonn; Christian F. Krebs (Cell and Tissue Research, 2021)
Single-cell biology is transforming the ability of researchers to understand cellular signaling and identity across medical and biological disciplines. Especially for immune-mediated diseases, a single-cell look at immune cell subtypes, signaling, and activity might yield fundamental insights into the disease etiology, mechanisms, and potential therapeutic interventions. In this review, we highlight recent advances in the field of single-cell RNA profiling and their application to understand renal function in health and disease. With a focus on the immune system, in particular on T cells, we propose some key directions of understanding renal inflammation using single-cell approaches. We detail the benefits and shortcomings of the various technological approaches outlined and give advice on potential pitfalls and challenges in experimental setup and computational analysis. Finally, we conclude with a brief outlook into a promising future for single-cell technologies to elucidate kidney function.

Age-Related Characteristics of Sleep Impairments in a Model of the Preclinical Stage of Parkinson’s Disease in Rats - I. V. Ekimova; M. A. Guzeev; V. V. Simonova; Yu. F. Pastukhov (Neuroscience and Behavioral Physiology, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

In vitro Inhibition of Clinical Isolates of Otitis Media Pathogens by the Probiotic Streptococcus salivarius BLIS K12 - Tzu Yu Chen; John D. F. Hale; John R. Tagg; Rohit Jain; Abigail L. Voss; Nikki Mills; Emma J. Best; Duncan S. Stevenson; Philip A. Bird; Tony Walls (Probiotics and Antimicrobial Proteins, 2021)

Cranial Anatomy of the Desert Dormouse, Selevinia betpakdalaensis (Rodentia, Gliridae), revealed by Micro-Computed Tomography - Jesse J. Hennekam; James W. F. Sadler; Fedor N. Golenishchev; Lyudmila Yu. Kryuchkova; Dmitry Korost; Olga Nanova; Philip G. Cox (Journal of Mammalian Evolution, 2021)

Global patterns and drivers of alpine plant species richness - Riccardo Testolin; Fabio Attorre; Peter Borchardt; Robert F. Brand; Helge Bruelheide; Milan Chytrý; Michele De Sanctis; Jiri Dolezal; Manfred Finckh; Sylvia Haider; Andreas Hemp; Ute Jandt; et al. (Global Ecology and Biogeography, 2021)
Aim Alpine ecosystems differ in area, macroenvironment and biogeographical history across the Earth, but the relationship between these factors and plant species richness is still unexplored. Here, we assess the global patterns of plant species richness in alpine ecosystems and their association with environmental, geographical and historical factors at regional and community scales. Location Global. Time period Data collected between 1923 and 2019. Major taxa studied Vascular plants. Methods We used a dataset representative of global alpine vegetation, consisting of 8,928 plots sampled within 26 ecoregions and six biogeographical realms, to estimate regional richness using sample‐based rarefaction and extrapolation. Then, we evaluated latitudinal patterns of regional and community richness with generalized additive models. Using environmental, geographical and historical predictors from global raster layers, we modelled regional and community richness in a mixed‐effect modelling framework. Results The latitudinal pattern of regional richness peaked around the equator and at mid‐latitudes, in response to current and past alpine area, isolation and the variation in soil pH among regions. At the community level, species richness peaked at mid‐latitudes of the Northern Hemisphere, despite a considerable within‐region variation. Community richness was related to macroclimate and historical predictors, with strong effects of other spatially structured factors. Main conclusions In contrast to the well‐known latitudinal diversity gradient, the alpine plant species richness of some temperate regions in Eurasia was comparable to that of hyperdiverse tropical ecosystems, such as the páramo. The species richness of these putative hotspot regions is explained mainly by the extent of alpine area and their glacial history, whereas community richness depends on local environmental factors. Our results highlight hotspots of species richness at mid‐latitudes, indicating that the diversity of alpine plants is linked to regional idiosyncrasies and to the historical prevalence of alpine ecosystems, rather than current macroclimatic gradients.

A new primer set for Clade I nosZ that recovers genes from a broader range of taxa - Bangzhou Zhang; C. Ryan Penton; Zhenhua Yu; Chao Xue; Qiongyun Chen; Zhangran Chen; Changsheng Yan; Qiang Zhang; Mengxin Zhao; John F. Quensen; James M. Tiedje (Biology and Fertility of Soils, 2021)

Synthesis and cytotoxicity of the conjugates of diterpenoid isosteviol and N -acetyl-D-glucosamine - Bulat F. Garifullin; Irina Yu. Strobykina; Leysan R. Khabibulina; Anastasiya S. Sapunova; Aleksandra D. Voloshina; Radmila R. Sharipova; Bulat I. Khairutdinov; Yuriy F. Zuev; Vladimir E. Kataev (Natural Product Research, 2021)

Cognitive benefits of exercise interventions: an fMRI activation likelihood estimation meta-analysis - Qian Yu; Fabian Herold; Benjamin Becker; Ben Klugah-Brown; Yanjie Zhang; Stephane Perrey; Nicola Veronese; Notger G. Müller; Arthur F. Kramer; Liye Zou (Brain Structure and Function, 2021)

Cambrian reefs in the lower Poleta Formation: a new occurrence of a thick archaeocyathan reef near Gold Point, Nevada, USA - Sara B. Pruss; Martha L. Slaymaker; Emily F. Smith; Andrey Yu. Zhuravlev; David A. Fike (Facies, 2021)

Combination of Muramylpeptides from Gram-Negative Bacteria Corrects Cyclophosphamide-Induced Disorders of Hematopoiesis and Spleen Cell Composition in Mice with B16 Melanoma - M. V. Kiselevskii; N. Yu. Anisimova; S. M. Sitdikova; F. V. Donenko; V. L. L’vov; O. V. Kalyuzhin; A. Yu. Nurtazina; A. V. Karaulov (Bulletin of Experimental Biology and Medicine, 2021)

The influence of the association of barley plants with petroleum degrading bacteria on the hormone content, growth and photosynthesis of barley plants grown in the oil-contaminated soil - Lidiya B. Vysotskaya; Guzel R. Kudoyarova; Tatyana N. Arkhipova; Elena V. Kuzina; Gulnaz F. Rafikova; Zarina A. Akhtyamova; Ruslan S. Ivanov; Sergey P. Chetverikov; Darya V. Chetverikova; Margarita D. Bakaeva; Tatyana Yu. Korshunova; Oleg N. Loginov (Acta Physiologiae Plantarum, 2021)

Connecting high‐throughput biodiversity inventories: Opportunities for a site‐based genomic framework for global integration and synthesis - Paula Arribas; Carmelo Andújar; Martin I. Bidartondo; Kristine Bohmann; Éric Coissac; Simon Creer; Jeremy R. deWaard; Vasco Elbrecht; Gentile F. Ficetola; Marta Goberna; Susan Kennedy; Henrik Krehenwinkel; et al. (Molecular Ecology, 2021)
High‐throughput sequencing (HTS) is increasingly being used for the characterization and monitoring of biodiversity. If applied in a structured way, across broad geographical scales, it offers the potential for a much deeper understanding of global biodiversity through the integration of massive quantities of molecular inventory data generated independently at local, regional and global scales. The universality, reliability and efficiency of HTS data can potentially facilitate the seamless linking of data among species assemblages from different sites, at different hierarchical levels of diversity, for any taxonomic group and regardless of prior taxonomic knowledge. However, collective international efforts are required to optimally exploit the potential of site‐based HTS data for global integration and synthesis, efforts that at present are limited to the microbial domain. To contribute to the development of an analogous strategy for the nonmicrobial terrestrial domain, an international symposium entitled “Next Generation Biodiversity Monitoring” was held in November 2019 in Nicosia (Cyprus). The symposium brought together evolutionary geneticists, ecologists and biodiversity scientists involved in diverse regional and global initiatives using HTS as a core tool for biodiversity assessment. In this review, we summarize the consensus that emerged from the 3‐day symposium. We converged on the opinion that an effective terrestrial Genomic Observatories network for global biodiversity integration and synthesis should be spatially led and strategically united under the umbrella of the metabarcoding approach. Subsequently, we outline an HTS‐based strategy to collectively build an integrative framework for site‐based biodiversity data generation.

In vitro plant regeneration from mature embryos of amphidiploid spelt Triticum spelta L. - A.V. Kyriienko; N. L. Shcherbak; M. V. Kuchuk; M. F. Parii; Yu V. Symonenko (In Vitro Cellular & Developmental Biology - Plant, 2021)

Diagnosis of early Alzheimer’s disease based on dynamic high order networks - Baiying Lei; Shuangzhi Yu; Xin Zhao; Alejandro F Frangi; Ee-Leng Tan; Ahmed Elazab; Tianfu Wang; Shuqiang Wang (Brain Imaging and Behavior, 2021)

Kamiohnoyneosides A and B, two new polyacetylene glycosides from flowers of edible Chrysanthemum "Kamiohno" - Shin-ichiro Kurimoto; Hiroki Fujita; Satomi Kawaguchi; Yu F. Sasaki; Takanori Nakamura; Takaaki Kubota (Journal of Natural Medicines, 2021)

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Effects of Peptides ACTH6–9 PGP and ACTH4–7-PGP on Anxiety Levels in Rats in Punished and Unpunished Behavior - S. A. Dodonova; I. I. Bobyntsev; A. E. Belykh; I. A. Telegina; Yu. A. Muzaleva; L. A. Andreeva; N. F. Myasoedov (Neuroscience and Behavioral Physiology, 2020)

Study on crack propagation and shear behavior of weak muddy intercalations submitted to wetting-drying cycles - L. P. He; J. Y. Yu; Q. J. Hu; Q. J. Cai; M. F. Qu; T. J. He (Bulletin of Engineering Geology and the Environment, 2020)

Assessment of the Chemosensitivity of Uveal Melanoma Cells Ex Vivo - S. V. Saakyan; А. Yu. Tsygankov; N. I. Moiseeva; А. F. Karamysheva; D. D. Garri (Bulletin of Experimental Biology and Medicine, 2020)

Measurement of Whole Blood Coagulation Time by Laser Speckle Pattern Correlation - Yu. D. Liushnevskaya; F. A. Gubarev; L. Li; A. V. Nosarev; V. S. Gusakova (Biomedical Engineering, 2020)

Rhabdoborite-(V), rhabdoborite-(Mo) and rhabdoborite-(W): a new group of borate minerals with the general formula $${{\text{Mg}}_{12}} {M_{1\nicefrac{1}{3}}} {{\text{O}}_{6}}$$[(BO3)6–x(PO4)xF2–x] (M = V5+, Mo6+ or W6+ and x < 1) - Igor V. Pekov; Natalia V. Zubkova; Natalia N. Koshlyakova; Dmitry I. Belakovskiy; Atali A. Agakhanov; Marina F. Vigasina; Sergey N. Britvin; Evgeny G. Sidorov; Dmitry Yu. Pushcharovsky (Physics and Chemistry of Minerals, 2020)

Thromboelastographic Research of Arginine-, Leucine and Lysine-Containing Peptides - E. Ya. Rogozinskaya; L. A. Lyapina; T. A. Shubina; N. F. Myasoedov; M. E. Grigorieva; T. Yu. Obergan; L. A. Andreeva (Bulletin of Experimental Biology and Medicine, 2020)

Patterns of Functional Connectivity in the Brain in Temporal and Frontal Epilepsy - I. S. Samotaeva; A. M. Teplyshova; F. K. Rider; Yu. V. Solomatin; R. V. Luzin; N. N. Lebedeva; A. B. Guekht (Neuroscience and Behavioral Physiology, 2020)

Process integration for emerging challenges: optimal allocation of antivirals under resource constraints - C. L. Sy; K. B. Aviso; C. D. Cayamanda; A. S. F. Chiu; R. I. G. Lucas; M. A. B. Promentilla; L. F. Razon; R. R. Tan; J. F. D. Tapia; A. R. Torneo; A. T. Ubando; D. E. C. Yu (Clean Technologies and Environmental Policy, 2020)

Peculiarities of Cell Seeding on Electroformed Polycaprolactone Scaffolds Modified with Surface-Active Agents Triton X-100 and Polyvinylpyrrolidone - S. A. Afanasiev; E. F. Muslimova; Yu. A. Nashchekina; P. O. Nikonov; Yu. V. Rogovskaya; T. Kh. Tenchurin; E. V. Nesterenko; E. V. Grakova; K. V. Kopeva; S. D. Akhmedov (Bulletin of Experimental Biology and Medicine, 2020)

Peculiarities of the Functional State of Mitochondria of Peripheral Blood Leukocytes in Patients with Acute Myocardial Infarction - S. А. Afanas’ev; E. F. Muslimova; Т. Yu. Rebrova; L. P. Tsapko; М. А. Kercheva; М. V. Golubenko (Bulletin of Experimental Biology and Medicine, 2020)

The Role of Glutamate in the Pathogenesis of Multiple Sclerosis - U. Sh. Kuzmina; L. F. Zainullina; V. A. Vakhitov; K. Z. Bakhtiyarova; Yu. V. Vakhitova (Neuroscience and Behavioral Physiology, 2020)

Development of In Vivo Model of Intraocular Retinoblastoma - S. V. Saakyan; А. Yu. Tsygankov; I. P. Khoroshilova-Maslova; N. I. Moiseeva; А. F. Karamysheva; M. G. Zhil’tsova; A. G. Amiryan; S. S. Tadevosyan (Bulletin of Experimental Biology and Medicine, 2020)

Composition of Colon Microbiota in Rats Treated with ACTH(4-7)-PGP Peptide (Semax) under Conditions of Restraint Stress - M. V. Svishcheva; A. Yu. Mukhina; O. A. Medvedeva; A. V. Shevchenko; I. I. Bobyntsev; P. V. Kalutskii; L. A. Andreeva; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2020)

Effect of Neuropeptide Cyclo-L-Prolylglycine on Cell Proliferative Activity - L. F. Zainullina; T. V. Ivanova; T. A. Gudasheva; Yu. V. Vakhitova; S. B. Seredenin (Bulletin of Experimental Biology and Medicine, 2020)

Morphological Changes in the Large Intestine of Rats Subjected to Chronic Restraint Stress and Treated with Selank - A. Yu. Mukhina; E. S. Mishina; I. I. Bobyntsev; O. A. Medvedeva; M. V. Svishcheva; P. V. Kalutskii; L. A. Andreeva; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2020)

Impairment to Cognitive Functions in Wistar Rats in a Model of the Preclinical Stage of Parkinson’s Disease - N. N. Abdurasulova; I. V. Ekimova; M. V. Chernyshev; A. V. Matsulevich; Yu. F. Pastukhov (Neuroscience and Behavioral Physiology, 2020)

Botanical acaricides and repellents in tick control: current status and future directions - Chuks F. Nwanade; Min Wang; Tianhong Wang; Zhijun Yu; Jingze Liu (Experimental and Applied Acarology, 2020)

Brain Network Connectivity and the Choice Motor Reaction in Combatants with Mild Traumatic Brain Injuries - N. B. Filimonova; M. Yu. Makarchuk; I. G. Zyma; V. V. Kal’nysh; A. F. Cheburkova (Neurophysiology, 2020)

Processing of ECG Waveforms to Increase the Diagnostic Accuracy of the ECG Stress Test for Transient Myocardial Ischemia - M. N. Kramm; F. Yu. Kopylov; P. Sh. Chomakhidze; N. O. Strelkov; A. I. Chernikov (Biomedical Engineering, 2020)

Repression of the transcriptional activity of ERRα with sequence-specific DNA-binding polyamides - Chien-yu Chen; Yang Li; Tiezheng Jia; Lina He; Alissa A. Hare; Amanda Silberstein; John Gallagher; Thomas F. Martinez; Joseph W. Stiles; Bogdan Olenyuk; Peter B. Dervan; Bangyan L. Stiles (Medicinal Chemistry Research, 2020)

De novo variants in the Helicase-C domain of CHD8 are associated with severe phenotypes including autism, language disability and overgrowth - Yu An; Linna Zhang; Wenwen Liu; Yunyun Jiang; Xue Chen; Xiaoping Lan; Gan Li; Qiang Hang; Jian Wang; James F. Gusella; Yasong Du; Yiping Shen (Human Genetics, 2020)

Expression of Metalloproteinases and Type I and III Collagens during Healing of Excisional Skin Wound on the Abdomen and Back in Rats - E. Yu. Kananykhina; T. V. Shmakova; G. B. Bolshakova; F. S. Rusanov; A. V. Elchaninov; M. P. Nikitina; A. V. Lokhonina; A. V. Makarov; T. Kh. Fatkhudinov (Bulletin of Experimental Biology and Medicine, 2020)

Combined Administration of TLR4 (LPS) and TLR3 (Poly I:C) Ligands to CBA Mice Elevates the Content of Osteogenic MSC by 1.6 Times and Increases Content of Bone Marrow MSC to Intermediate Level between Values Attained by Their Individual Administration - Yu. F. Gorskaya; A. I. Tukhvatulin; A. Sh. Dzharullaeva; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2020)

A new mineral borisenkoite, Cu3[(V,As)O4]2, and the isomorphous series borisenkoite–lammerite-β in fumarolic exhalations of the Tolbachik volcano, Kamchatka, Russia - Igor V. Pekov; Natalia V. Zubkova; Vasiliy O. Yapaskurt; Yury S. Polekhovsky; Marina F. Vigasina; Sergey N. Britvin; Anna G. Turchkova; Evgeny G. Sidorov; Dmitry Yu. Pushcharovsky (Physics and Chemistry of Minerals, 2020)

Systemic Administrations of Water-Dispersible Single-Walled Carbon Nanotubes: Activation of NOS in Spontaneously Hypertensive Rats - L. M. Shapoval; O. V. Dmytrenko; V. F. Sagach; S. V. Prylutska; S. V. Khrapatiy; D. O. Zavodovskyi; Yu. I. Prylutskyy; N. Tsierkezos; U. Ritter (Neurophysiology, 2020)

Effects of Catechin on Activity of Angiotensin-Converting Enzyme and Generation of Reactive Oxygen Species in Rat Aorta - V. A. Anikina; Yu. A. Kim; A. F. Korystova; M. Kh. Levitman; V. V. Shaposhnikova; Yu. N. Korystov (Bulletin of Experimental Biology and Medicine, 2020)

Identification of pyrrolo-pyridine derivatives as novel class of antibacterials - Mark S. Veselov; Yan A. Ivanenkov; Renat S. Yamidanov; Ilya A. Osterman; Petr V. Sergiev; Vladimir A. Aladinskiy; Anastasia V. Aladinskaya; Victor A. Terentiev; Andrey A. Ayginin; Dmitry A. Skvortsov; Katerina S. Komarova; Alexey V. Chemeris; et al. (Molecular Diversity, 2020)

Correlation of the Levels of microRNA with Cell Composition of Axillary Lymph Node in Wistar Rats with Breast Cancer - A. V. Kabakov; A. P. Lykov; O. V. Kazakov; A. F. Poveshchenko; O. V. Poveshchenko; I. I. Kim; N. A. Bondarenko; D. N. Strunkin; A. Yu. Letyagin; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2020)

Correlation Analysis of Morphological Changes of Structural and Functional Areas of Mesenteric Lymph Nodes with Cytokines of Lymph of Thoracic Lymphatic Duct in Experimental Breast Cancer - O. V. Kazakov; T. V. Raiter; A. F. Poveshchenko; N. B. Orlov; O. V. Poveshchenko; A. V. Kabakov; I. I. Kim; N. A. Bondarenko; D. N. Strunkin; A. P. Lykov; A. Yu. Letyagin; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2020)

Involvement of Bone Marrow Multipotent Stromal Cells in the Processes Presumably Provoking Vascular Calcification - Yu. F. Gorskaya; E. N. Semenova; E. V. Nagurskaya; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2020)

Founder effects, post-introduction evolution and phenotypic plasticity contribute to invasion success of a genetically impoverished invader - Zhi-Yong Liao; J. F. Scheepens; Qiao-Ming Li; Wei-Bin Wang; Yu-Long Feng; Yu-Long Zheng (Oecologia, 2020)

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Associations of mtDNA haplotypes with productive traits in pigs - Maria A. Kolosova; Lubov V. Getmantseva; Siroj Yu. Bakoev; Anatoly Yu. Kolosov; Nekruz F. Bakoev; Varvara S. Shevtsova; Elena N. Lyashenko; Olga V. Kostyunina (Rendiconti Lincei. Scienze Fisiche e Naturali, 2019)

Effect of a New Synthetic Peptide Preparation AСTH15-18PGP on the Hemostasis System in Rats - T. A. Shubina; T. Yu. Obergan; L. A. Lyapina; M. E. Grigorieva; N. F. Myasoedov; L. A. Andreeva (Bulletin of Experimental Biology and Medicine, 2019)

Antibacterial Activity of Hybrid Polymeric Scaffold for Reconstruction of Tubular Bone Defects - N. Yu. Anisimova; D. Yu. Zalepugin; I. V. Chernyshova; A. V. Maksimkin; M. V. Kiselevskii; F. S. Senatov; T. S. Spirina; S. M. Sitdikova; A. V. Karaulov (Bulletin of Experimental Biology and Medicine, 2019)

Hip Fracture Discrimination Based on Statistical Multi-parametric Modeling (SMPM) - Julio Carballido-Gamio; Aihong Yu; Ling Wang; Yongbin Su; Andrew J. Burghardt; Thomas F. Lang; Xiaoguang Cheng (Annals of Biomedical Engineering, 2019)

Correction to: Can Neonatal Systemic Inflammation and Hypoxia Yield a Cerebral Palsy-Like Phenotype in Periadolescent Mice? - Adamantia F. Fragopoulou; Yu Qian; Rochellys Diaz Heijtz; Hans Forssberg (Molecular Neurobiology, 2019)

Can Neonatal Systemic Inflammation and Hypoxia Yield a Cerebral Palsy-Like Phenotype in Periadolescent Mice? - Adamantia F. Fragopoulou; Yu Qian; Rochellys Diaz Heijtz; Hans Forssberg (Molecular Neurobiology, 2019)

First molecular phylogenetic insights into the evolution of Eriocaulon (Eriocaulaceae, Poales) - Isabel Larridon; Norio Tanaka; Yuxi Liang; Sylvia M. Phillips; Anders S. Barfod; Seong-Hyun Cho; Stephan W. Gale; Richard W. Jobson; Young-Dong Kim; Jie Li; A. Muthama Muasya; John A. N. Parnell; et al. (Journal of Plant Research, 2019)

Evolving the Physical Global Ocean Observing System for Research and Application Services Through International Coordination - Bernadette M. Sloyan; John Wilkin; Katherine Louise Hill; Maria Paz Chidichimo; Meghan F. Cronin; Johnny A. Johannessen; Johannes Karstensen; Marjolaine Krug; Tong Lee; Eitarou Oka; Matthew D. Palmer; Benjamin Rabe; et al. (Frontiers in Marine Science, 2019)

Air-Sea Fluxes With a Focus on Heat and Momentum - Meghan F. Cronin; Chelle L. Gentemann; James Edson; Iwao Ueki; Mark Bourassa; Shannon Brown; Carol Anne Clayson; Chris W. Fairall; J. Thomas Farrar; Sarah T. Gille; Sergey Gulev; Simon A. Josey; et al. (Frontiers in Marine Science, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

A Combination of Muramylpeptides from Gram-Negative Bacteria Corrects Hematological and Immunological Disorders Induced by Cyclophosphamide - M. V. Kiselevskii; N. Yu. Anisimova; S. M. Sitdikova; F. V. Donenko; S. F. Popilyuk; V. L. L’vov; O. V. Kalyuzhin (Bulletin of Experimental Biology and Medicine, 2019)

Effect of Cell-Penetrating Arginine Peptide on Interaction of Photosensitizer Chlorin e6 Incorporated into Phospholipid Nanoparticles with Tumor Cells - L. V. Kostryukova; E. I. Korotkevich; G. E. Morozevich; E. F. Kolesanova; M. V. Mel’nikova; Yu. V. Filatova; T. I. Torkhovskaya; V. N. Prozorovskii; E. G. Tikhonova; O. M. Ipatova (Bulletin of Experimental Biology and Medicine, 2019)

New Principles in the Operation of Neural Emulators in Medical Diagnosis - V. A. Khromushin; V. F. Pyatin; V. V. Eskov; L. K. Ilyashenko; Yu. V. Vokhmina (Biomedical Engineering, 2019)

Microwave Radiometry in the Diagnosis of Various Urological Diseases - A. D. Kaprin; A. A. Kostin; M. I. Andryukhin; K. V. Ivanenko; S. V. Popov; P. V. Shegai; D. P. Kruglov; F. Sh. Mangutov; V. Yu. Leushin; S. V. Agasieva (Biomedical Engineering, 2019)

Slow-Wave Sleep and Anxiety Levels in Rats in Chronic Deficiency of Chaperone Hsp70i in the Preoptic Area of the Hypothalamus - V. V. Simonova; M. V. Chernyshev; M. A. Guzeev; Yu. F. Pastukhov (Neuroscience and Behavioral Physiology, 2019)

Effectiveness of Computerized Cognitive Training in Patients with Poststroke Cognitive Impairments - S. V. Prokopenko; A. F. Bezdenezhnykh; E. Yu. Mozheyko; E. M. Zubrickaya (Neuroscience and Behavioral Physiology, 2019)

State of Colon Microbiota in Rats during Chronic Restraint Stress and Selank Treatment - A. Yu. Mukhina; O. A. Medvedeva; M. V. Svishcheva; A. V. Shevchenko; N. N. Efremova; I. I. Bobyntsev; P. V. Kalutskii; L. A. Andreeva; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Preparation and Testing of Cells Expressing Fluorescent Proteins for Intravital Imaging of Tumor Microenvironment - S. S. Vodopyanov; M. A. Kunin; A. S. Garanina; N. F. Grinenko; K. Yu. Vlasova; P. A. Mel’nikov; V. P. Chekhonin; K. K. Sukhinich; A. V. Makarov; V. A. Naumenko; M. A. Abakumov; A. G. Majouga (Bulletin of Experimental Biology and Medicine, 2019)

Effect of Non-Thermal Plasma on Proliferative Activity and Adhesion of Multipotent Stromal Cells to Scaffolds Developed for Tissue-Engineered Constructs - R. K. Chailakhyan; A. G. Grosheva; Yu. V. Gerasimov; N. N. Vorob’eva; S. A. Ermolaeva; E. V. Sysolyatina; M. V. Kazakova; Yu. S. Akishev; A. V. Petryakov; K. V. Sidoruk; V. F. Burdukovskii; P. S. Timashev (Bulletin of Experimental Biology and Medicine, 2019)

Relationships between urban green land cover and human health at different spatial resolutions - Wei-Lun Tsai; Yu-Fai Leung; Melissa R. McHale; Myron F. Floyd; Brian J. Reich (Urban Ecosystems, 2019)

Erratum to: Dissolved organic carbon in permafrost regions: A review - Qiang Ma; Huijun Jin; Congrong Yu; Victor F. Bense (Science China Earth Sciences, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Cannabinoidergic Regulation of the Functional State of the Heart. The Role of the Autonomic Nervous System - A. V. Krylatov; L. N. Maslov; I. F. Nam; Yu. V. Bushov (Neuroscience and Behavioral Physiology, 2019)

Purification and characterization of exo-β-1,4-glucosaminidase produced by chitosan-degrading fungus, Penicillium sp. IB-37-2A - Gleb E. Aktuganov; Nailya F. Galimzianova; Elena A. Gilvanova; Elena A. Pudova; Lyudmila Yu. Kuzmina; Alexander I. Melentiev; Violetta R. Safina (World Journal of Microbiology and Biotechnology, 2019)

Dissolved organic carbon in permafrost regions: A review - Qiang Ma; Huijun Jin; Congrong Yu; Victor F. Bense (Science China Earth Sciences, 2019)

Treatment of Speech Development Disorders in Preschool Children - V. F. Shalimov; N. Yu. Suvorinova; Yu. E. Nesterovsky (Neuroscience and Behavioral Physiology, 2019)

Preparation and optimization of multifunctional electrospun polyurethane/chitosan nanofibers for air pollution control applications - M. H. Mohraz; F. Golbabaei; I. J. Yu; M. A. Mansournia; A. S. Zadeh; S. F. Dehghan (International Journal of Environmental Science and Technology, 2019)

Drug with Neuroprotective Properties Noopept Does Not Stimulate Cell Proliferation - L. F. Zainullina; T. V. Ivanova; R. U. Ostrovskaya; T. A. Gudasheva; Yu. V. Vakhitova; S. B. Seredenin (Bulletin of Experimental Biology and Medicine, 2019)

Ligands of NOD2 (Muramyl Dipeptide) and TLR4 (LPS) in 24 h after Combined In Vivo Administration Produce a Synergistic Increase in the Content of Multipotent Stromal Cells in the Bone Marrow and Peritoneal Exudate of CBA Mice - Yu. F. Gorskaya; A. I. Tukhvatulin; A. Sh. Dzharullaeva; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2019)

Geochemistry and petrology of superpure quartzites from East Sayan Mountains, Russia - A. M. Fedorov; V. A. Makrygina; A. I. Nepomnyaschikh; A. P. Zhaboedov; A. V. Parshin; V. F. Posokhov; Yu. V. Sokolnikova (Acta Geochimica, 2019)

Controls of faulting on synrift infill patterns in the Eocene PY4 Sag, Pearl River Mouth Basin, South China Sea - J. Ge; X. Zhu; F. Yu; B. G. Jones; W. Tao (Australian Journal of Earth Sciences, 2019)

Implications of eutrophication for biogeochemical processes in the Three Gorges Reservoir, China - Xiangbin Ran; Alexander F. Bouwman; Zhigang Yu; Jun Liu (Regional Environmental Change, 2019)

Efficacy of Reslip (doxylamine) in Acute Insomnia: A Multicenter, Open, Comparative, Randomized Trial - A. Yu. Mel’nikov; S. Yu. Lavrik; L. F. Bikbulatova; I. G. Raginene; Ya. A. Ivanova; A. V. Zakharov (Neuroscience and Behavioral Physiology, 2019)

Effect of Activated Immunocompetent Cells on the Number of Multipotent Stromal Cells in Bone Marrow Transplants of CBA and CBA/N Mice in a Short Time after Polyvinylpyrrolidone Administration to Animals - Yu. F. Gorskaya; A. I. Tukhvatulin; A. Sh. Dzharullaeva; E. N. Semenova; E. V. Nagurskaya; V. A. Bekhalo; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2019)

Mitochondria-Associated Matrix Metalloproteinases 2 and 9 in Acute Renal Pathologies - I. B. Pevzner; L. D. Zorova; F. A. Galkin; E. Yu. Plotnikov; D. B. Zorov (Bulletin of Experimental Biology and Medicine, 2019)

An Improved Rock Mass Characterization Method Using a Quantified Geological Strength Index and Synthetic Rock Mass Model - Yabing Zhang; F. Y. Ren; T. H. Yang; S. Y. Wang; W. F. Zhang; M. X. Yu (Rock Mechanics and Rock Engineering, 2018)

Use of a BCI-Exoskeleton Simulator with Multichannel Biofeedback in a Multidisciplinary Rehabilitation Program in Poststroke Patients - G. E. Ivanova; Yu. V. Bushkova; A. Yu. Suvorov; L. V. Stahovskaya; I. Z. Dzhalagoniya; N. A. Varako; M. S. Kovyazina; F. A. Bushkov (Neuroscience and Behavioral Physiology, 2018)

The history and future of the biological resources of the Caspian and the Aral Seas - N. V. Aladin; T. Chida; Yu. S. Chuikov; Z. K. Ermakhanov; Y. Kawabata; J. Kubota; P. Micklin; I. S. Plotnikov; A. O. Smurov; V. F. Zaitzev (Journal of Oceanology and Limnology, 2018)

Blood Pressure Changes After Exposures Increasing Angiotensin-Converting Enzyme Activity and After Its Normalization with Dihydroquercetin in Male Wistar Rats - A. F. Korystova; L. N. Kublik; M. Kh. Levitman; V. V. Shaposhnikova; Yu. A. Kim; G. A. Slashcheva; A. V. Lobanov; E. A. Tukhovskaya; Yu. N. Korystov (Bulletin of Experimental Biology and Medicine, 2018)

The Effect of Pulsed Electric Field on the Generation of Charge in Flow-Based Medical and Diagnostic Systems - Y. D. Ivanov; A. F. Kozlov; R. A. Galiullin; V. Yu. Tatur; V. S. Ziborov; N. D. Ivanova; V. G. Nikitaev; E. A. Druzhinina; T. O. Pleshakova (Biomedical Engineering, 2018)

Association between Genes for Inflammatory Factors and Neuroticism, Anxiety, and Depression in Men with Ischemic Heart Disease - V. E. Golimbet; B. A. Volel’; G. I. Korovaitseva; S. V. Kasparov; N. V. Kondrat’ev; F. Yu. Kopylov (Neuroscience and Behavioral Physiology, 2018)

Numerical modelling of hydro-mechanical behaviour of ground settlement due to rising water table in loess - Yanrong Xu; C. F. Leung; Jian Yu; Wenwu Chen (Natural Hazards, 2018)

Considering evolutionary processes in cycad conservation: identification of evolutionarily significant units within Dioon sonorense (Zamiaceae) in northwestern Mexico - José Said Gutiérrez-Ortega; Karen Jiménez-Cedillo; Miguel Angel Pérez-Farrera; Andrew P. Vovides; José F. Martínez; Francisco Molina-Freaner; Ryosuke Imai; Yoshiaki Tsuda; Yu Matsuki; Yoshihisa Suyama; Yasuyuki Watano; Tadashi Kajita (Conservation Genetics, 2018)

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Interferon β-1a Formulations for S.C. Administration in Patients with Remitting Multiple Sclerosis: First-Year Results - A. N. Boiko; L. P. Bosenko; V. V. Vasilovskii; L. I. Volkova; M. N. Zakharova; S. V. Kotov; E. V. Lekomtseva; T. I. Negrich; E. V. Parshina; O. P. Patrusheva; S. V. Prokopenko; D. V. Sazonov; et al. (Neuroscience and Behavioral Physiology, 2018)

Expression of microRNA Potentially Regulated by AhR and CAR in Malignant Tumors of the Endometrium - D. S. Ushakov; A. S. Dorozhkova; E. V. Babayants; V. Yu. Ovchinnikov; D. N. Kushlinskii; L. V. Adamyan; L. F. Gulyaeva; N. E. Kushlinskii (Bulletin of Experimental Biology and Medicine, 2018)

Effects of Semax on the Default Mode Network of the Brain - I. S. Lebedeva; Ya. R. Panikratova; O. Yu. Sokolov; D. A. Kupriyanov; A. D. Rumshiskaya; N. V. Kost; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2018)

Targeting therapeutics to endothelium: are we there yet? - Raisa Yu. Kiseleva; Patrick M. Glassman; Colin F. Greineder; Elizabeth D. Hood; Vladimir V. Shuvaev; Vladimir R. Muzykantov (Drug Delivery and Translational Research, 2018)

Molecular Docking of Phenylethylamine and CGP54626 to an Extracellular Domain of the GABAB-Receptor - A. M. Naumenko; L. M. Shapoval; T. L. Davydovska; I. S. Voiteshenko; A. Yu. Nyporko; O. V. Tsymbalyuk; V. F. Sagach (Neurophysiology, 2018)

Prediction of enteric methane production, yield, and intensity in dairy cattle using an intercontinental database - Mutian Niu; Ermias Kebreab; Alexander N. Hristov; Joonpyo Oh; Claudia Arndt; André Bannink; Ali R. Bayat; André F. Brito; Tommy Boland; David Casper; Les A. Crompton; Jan Dijkstra; et al. (Global Change Biology, 2018)
Enteric methane ( CH 4 ) production from cattle contributes to global greenhouse gas emissions. Measurement of enteric CH 4 is complex, expensive, and impractical at large scales; therefore, models are commonly used to predict CH 4 production. However, building robust prediction models requires extensive data from animals under different management systems worldwide. The objectives of this study were to (1) collate a global database of enteric CH 4 production from individual lactating dairy cattle; (2) determine the availability of key variables for predicting enteric CH 4 production (g/day per cow), yield [g/kg dry matter intake ( DMI )], and intensity (g/kg energy corrected milk) and their respective relationships; (3) develop intercontinental and regional models and cross‐validate their performance; and (4) assess the trade‐off between availability of on‐farm inputs and CH 4 prediction accuracy. The intercontinental database covered Europe ( EU ), the United States ( US ), and Australia ( AU ). A sequential approach was taken by incrementally adding key variables to develop models with increasing complexity. Methane emissions were predicted by fitting linear mixed models. Within model categories, an intercontinental model with the most available independent variables performed best with root mean square prediction error ( RMSPE ) as a percentage of mean observed value of 16.6%, 14.7%, and 19.8% for intercontinental, EU , and United States regions, respectively. Less complex models requiring only DMI had predictive ability comparable to complex models. Enteric CH 4 production, yield, and intensity prediction models developed on an intercontinental basis had similar performance across regions, however, intercepts and slopes were different with implications for prediction. Revised CH 4 emission conversion factors for specific regions are required to improve CH 4 production estimates in national inventories. In conclusion, information on DMI is required for good prediction, and other factors such as dietary neutral detergent fiber ( NDF ) concentration, improve the prediction. For enteric CH 4 yield and intensity prediction, information on milk yield and composition is required for better estimation.

Racial differences in the relationship between tobacco, alcohol, and the risk of head and neck cancer: pooled analysis of US studies in the INHANCE Consortium - Kristin J. Voltzke; Yuan-Chin Amy Lee; Zuo-Feng Zhang; Jose P. Zevallos; Guo-Pei Yu; Deborah M. Winn; Thomas L. Vaughan; Erich M. Sturgis; Elaine Smith; Stephen M. Schwartz; Stimson Schantz; Joshua Muscat; et al. (Cancer Causes & Control, 2018)

Dihydroquercetin and Fucoidin Inhibit the Increase of Angiotensin-Converting Enzyme Activity in the Rat Aorta after Irradiation - A. F. Korystova; L. N. Kublik; Yu. A. Kim; M. Kh. Levitman; V. V. Shaposhnikova; Yu. N. Korystov (Bulletin of Experimental Biology and Medicine, 2018)

A Hardware−Software System for Mechanotherapy of Lower Limbs - A. G. Gudkov; V. Yu. Leushin; A. F. Bobrikhin; S. V. Agasieva; E. N. Gorlacheva; V. N. Lemondzhava; A. V. Markin; S. V. Chizhikov; N. A. Vetrova (Biomedical Engineering, 2018)

Long-Term Trends of Carbon Monoxide Total Columnar Amount in Urban Areas and Background Regions: Ground- and Satellite-based Spectroscopic Measurements - Pucai Wang; N. F. Elansky; Yu. M. Timofeev; Gengchen Wang; G. S. Golitsyn; M. V. Makarova; V. S. Rakitin; Yu. Shtabkin; A. I. Skorokhod; E. I. Grechko; E. V. Fokeeva; A. N. Safronov; et al. (Advances in Atmospheric Sciences, 2018)

First identification of the nervous necrosis virus isolated from cultured golden pompano ( Trachinotus ovatus ) in Guangxi, China - P Li; Q Yu; F Li; X Qin; D Dong; B Chen; Q Qin (Journal of Fish Diseases, 2018)

Focusing quorum sensing signalling by nano‐magnetic assembly - Yongguang Guan; Chen‐Yu Tsao; David N. Quan; Ying Li; Lei Mei; Yingying Song; Boce Zhang; Yi Liu; Gregory F. Payne; William E. Bentley; Qin Wang (Environmental Microbiology, 2018)
Summary Quorum sensing (QS) exists widely among bacteria, enabling a transition to multicellular behaviour after bacterial populations reach a particular density. The coordination of multicellularity enables biotechnological application, dissolution of biofilms, coordination of virulence, and so forth. Here, a method to elicit and subsequently disperse multicellular behaviour among QS‐negative cells is developed using magnetic nanoparticle assembly. We fabricated magnetic nanoparticles (MNPs, ∼5 nm) that electrostatically collect wild‐type (WT) Escherichia coli BL21 cells and brings them into proximity of bioengineered E. coli [CT104 (W3110 lsrFG − luxS − pCT6 + pET‐DsRed)] reporter cells that exhibit a QS response after receiving autoinducer‐2 (AI‐2). By shortening the distance between WT and reporter cells (e.g., increasing local available AI‐2 concentrations), the QS response signalling was amplified four‐fold compared to that in native conditions without assembly. This study suggests potential applications in facilitating intercellular communication and modulating multicellular behaviours based on user‐specified designs.

Dynamic Characteristics of Green Sandstone Subjected to Repetitive Impact Loading: Phenomena and Mechanisms - S. H. Li; W. C. Zhu; L. L. Niu; M. Yu; C. F. Chen (Rock Mechanics and Rock Engineering, 2018)

Comparison of endosperm amyloplast development and degradation in waxy and non-waxy wheat - H. Yu; Y. Yang; X.Y. Chen; G.X. Lin; J.Y. Sheng; J.Y. Nie; Q.J. Wang; E.J. Zhang; X.R. Yu; Z. Wang; F. Xiong (Cereal Research Communications, 2018)

Ionizing Radiation Enhances Activity of Angiotensin-Converting Enzyme in Rat Aorta - A. F. Korystova; L. N. Kublik; M. Kh. Levitman; T. V. Samokhvalova; V. V. Shaposhnikova; Yu. N. Korystov (Bulletin of Experimental Biology and Medicine, 2018)

NMDA Receptors Regulate Genes Responsible for Major Immune Functions of Mononuclears in Human Peripheral Blood - U. Sh. Kuzmina; L. F. Zainullina; S. V. Sadovnikov; V. A. Vakhitov; Yu. V. Vakhitova (Bulletin of Experimental Biology and Medicine, 2018)

Breeding system of Anemone shikokiana and the influential factors of fruit-setting ratio in different habitats - F. H. Bian; P. Chen; W. Y. Yu (Plant Biosystems, 2018)

Analysis of Blood Plasma Protein Composition in Patients with Cerebral Ischemia - Yu. S. Kisrieva; N. A. Petushkova; N. F. Samenkova; G. P. Kuznetsova; O. V. Larina; N. B. Teryaeva; V. G. Zgoda; I. I. Karuzina; D. U. Usachev; A. Yu. Belyaev (Bulletin of Experimental Biology and Medicine, 2018)

Retinoblastoma Cell Culturing and Evaluation of Their Drug Resistance - S. V. Saakyan; А. Yu. Tsygankov; N. I. Moiseeva; А. F. Karamysheva; M. G. Zhil’tsova; S. S. Tadevosyan (Bulletin of Experimental Biology and Medicine, 2018)

GDF9 gene polymorphism and its association with litter size in two Russian sheep breeds - Ivan F. Gorlov; Yuri A. Kolosov; Nadezhda V. Shirokova; Lyubov V. Getmantseva; Marina I. Slozhenkina; Natali I. Mosolova; Nekruz F. Bakoev; Maria A. Leonova; Anatoli Yu. Kolosov; Elena Yu. Zlobina (Rendiconti Lincei. Scienze Fisiche e Naturali, 2018)

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Glatiramer Acetate 20 mg in Patients with Remitting Multiple Sclerosis: First-Year Study Results - A. N. Boiko; N. Yu. Lashch; S. N. Sharanova; M. N. Zakharova; O. V. Trifonova; T. O. Simaniv; E. V. Lysogorskaya; O. E. Gur’yanova; S. V. Kotov; T. I. Yakushina; V. Yu. Lizhdvoi; Yu. A. Belova; et al. (Neuroscience and Behavioral Physiology, 2018)

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

Modulation of GABA- and Glycine-Activated Ionic Currents with Semax in Isolated Cerebral Neurons - I. N. Sharonova; Yu. V. Bukanova; N. F. Myasoedov; V. G. Skrebitskii (Bulletin of Experimental Biology and Medicine, 2018)

Effect of Various Treatment Modes of Experimental Mammary Gland Tumor on Structure of Anterior Mediastinal Lymph Nodes - O. V. Kazakov; A. V. Kabakov; A. F. Poveshchenko; T. V. Raiter; D. N. Strunkin; S. S. Bogachev; I. Yu. Ishchenko; A. P. Lykov; S. V. Michurina; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2018)

Nootropic Activity of a Novel (-)-Cytisine Derivative (3aR,4S,8S,12R, 12aS,12bR)-10-Methyl-2-Phenyloctahydro-1H-4,12a-Etheno-8,12-Methanopyrrolo[3’,4’:3,4]Pyrido[1,2-a] [1,5]Diazocine-1,3,5(4H)-Trione - N. S. Makara; T. A. Sapozhnikova; R. Yu. Khisamutdinova; I. P. Tsypysheva; S. S. Borisevich; A. V. Kovalskaya; P. R. Petrova; C L. Khursan; F. S. Zarudii (Bulletin of Experimental Biology and Medicine, 2018)

Effects of Melatonin on the Behavioral Indices and Structural Characteristics of Cerebral and Spinal Neurons of Rats with Experimental Hemiparkinsonism - I. F. Labunets; Yu. B. Chaikovsky; S. I. Savosko; G. M. Butenko; V. F. Sagach; B. S. Kop’yak (Neurophysiology, 2018)

Fish invasion in the river systems of Guangdong Province, South China: Possible indicators of their success - D. E. Gu; Y. C. Hu; M. Xu; H. Wei; D. Luo; Y. X. Yang; F. D. Yu; X. D. Mu (Fisheries Management and Ecology, 2018)
Although a large number of fish species have been introduced into Guangdong Province in Southern China, a few species, such as tilapia ( Tilapia spp.), North African catfish Clarias gariepinus Burchell, mrigal carp, Cirrhinus mrigala (Bloch) and the sucker mouth catfish ( Hypostomus sp.), have established natural populations and can be considered “successful invaders” in large rivers. The specific mechanisms underlying these contrasting results among different introduced fish species remain understudied. The relationship between multiple abiotic–biotic factors and the success of four invasive species was investigated using survey data for the Guangdong Province river ecosystem. In contrast to previous studies that have considered species‐specific traits, the focus was on economic, ecological and anthropogenic factors to predict invasion success. Four main predictive indicators were found: (1) successful invaders were of low or no commercial value; (2) successful invaders tolerated a wide range of environmental conditions, including poor water quality; (3) biodiversity loss accelerated the growth of non‐native populations; (4) human disturbance facilitated population growth and spread of invasive fish species. To lessen the impacts of invasive fish species, the selection of breeding species and breeding areas, maintenance of water quality and reduction in water pollution, protection of the diversity of fish species and reduction of human interference should be addressed.

A novel Chromatiales bacterium is a potential sulfide oxidizer in multiple orders of marine sponges - Adi Lavy; Ray Keren; Ke Yu; Brian C. Thomas; Lisa Alvarez‐Cohen; Jillian F. Banfield; Micha Ilan (Environmental Microbiology, 2018)
Summary Sponges are benthic filter feeders that play pivotal roles in coupling benthic‐pelagic processes in the oceans that involve transformation of dissolved and particulate organic carbon and nitrogen into biomass. While the contribution of sponge holobionts to the nitrogen cycle has been recognized in past years, their importance in the sulfur cycle, both oceanic and physiological, has only recently gained attention. Sponges in general, and Theonella swinhoei in particular, harbour a multitude of associated microorganisms that could affect sulfur cycling within the holobiont. We reconstructed the genome of a Chromatiales (class Gammaproteobacteria) bacterium from a metagenomic sequence dataset of a T. swinhoei ‐associated microbial community. This relatively abundant bacterium has the metabolic capability to oxidize sulfide yet displays reduced metabolic potential suggestive of its lifestyle as an obligatory symbiont. This bacterium was detected in multiple sponge orders, according to similarities in key genes such as 16S rRNA and polyketide synthase genes. Due to its sulfide oxidation metabolism and occurrence in many members of the Porifera phylum, we suggest naming the newly described taxon Candidatus Porisulfidus .

Neurological Complications in Patients with Type 1 Diabetes Mellitus with Different Methods of Insulin Therapy - N. F. Shimkina; Yu. G. Nad’; E. R. Barantsevich (Neuroscience and Behavioral Physiology, 2018)

Effects of Single Injections of Brain-Derived Neurotrophic Factors into the Midline Ventral Tegmental Area on the Reinforcing Properties of Morphine - D. I. Peregud; M. Yu. Stepanichev; N. A. Lazareva; L. F. Panchenko; N. V. Gulyaeva (Neuroscience and Behavioral Physiology, 2018)

Detection and Sizing of Ti-Containing Particles in Recreational Waters Using Single Particle ICP-MS - Arjun K. Venkatesan; Robert B. Reed; Sungyun Lee; Xiangyu Bi; David Hanigan; Yu Yang; James F. Ranville; Pierre Herckes; Paul Westerhoff (Bulletin of Environmental Contamination and Toxicology, 2018)

Apolipoprotein A-I Stimulates Cell Proliferation in Bone Marrow Cell Culture - I. F. Usynin; A. N. Dudarev; A. Yu. Gorodetskaya; S. M. Miroshnichenko; T. A. Tkachenko; V. I. Tkachenko (Bulletin of Experimental Biology and Medicine, 2018)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Both structure and function of human monoclonal antibodies contribute to enhancement of Zika virus infectivity in vitro - Min Li; Xin Wang; Qihui Wang; Lei Yu; Lanfeng Wang; Jinghua Yan; Fuchun Zhang; Linqi Zhang; George F. Gao; Xia Jin (Science China Life Sciences, 2017)

Anterior Mediastinal Lymph Nodes in Chemically Induced Breast Cancer - O. V. Kazakov; A. V. Kabakov; A. F. Poveshchenko; T. V. Raiter; D. N. Strunkin; I. Yu. Ishchenko; A. P. Lykov; S. V. Michurina; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2017)

Peculiarities of Cell Seeding on Polylactic Acid-Based Scaffolds Fabricated Using Electrospinning and Solution Blow Spinning Technologies - S. A. Afanasiev; E. F. Muslimova; Yu. A. Nashchekina; P. O. Nikonov; Yu. V. Rogovskaya; E. N. Bolbasov; S. I. Tverdokhlebov (Bulletin of Experimental Biology and Medicine, 2017)

Effect of Native and Modified Apolipoprotein A-I on DNA Synthesis in Cultures of Different Cells - I. F. Usynin; A. N. Dudarev; S. M. Miroshnichenko; T. A. Tkachenko; A. Yu. Gorodetskaya (Bulletin of Experimental Biology and Medicine, 2017)

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Automated Reticulocyte Counting in Peripheral Blood Smears - D. Yu. Sosnin; L. S. Onjanova; B. F. Falkov; O. G. Kubarev; N. V. Pozdin (Biomedical Engineering, 2017)

Effect of auxin producing and phosphate solubilizing bacteria on mobility of soil phosphorus, growth rate, and P acquisition by wheat plants - Guzel R. Kudoyarova; Lidiya B. Vysotskaya; Tatiana N. Arkhipova; Ludmila Yu. Kuzmina; Nailya F. Galimsyanova; Ludmila V. Sidorova; Ilusa M. Gabbasova; Alexander I. Melentiev; Stanislav Yu. Veselov (Acta Physiologiae Plantarum, 2017)

Interannual variability of ecosystem carbon exchange: From observation to prediction - Shuli Niu; Zheng Fu; Yiqi Luo; Paul C. Stoy; Trevor F. Keenan; Benjamin Poulter; Leiming Zhang; Shilong Piao; Xuhui Zhou; Han Zheng; Jiayin Han; Qiufeng Wang; et al. (Global Ecology and Biogeography, 2017)
Aim Terrestrial ecosystems have sequestered, on average, the equivalent of 30% of anthropogenic carbon (C) emissions during the past decades, but annual sequestration varies from year to year. For effective C management, it is imperative to develop a predictive understanding of the interannual variability (IAV) of terrestrial net ecosystem C exchange (NEE). Location Global terrestrial ecosystems. Methods We conducted a comprehensive review to examine the IAV of NEE at global, regional and ecosystem scales. Then we outlined a conceptual framework for understanding how anomalies in climate factors impact ecological processes of C cycling and thus influence the IAV of NEE through biogeochemical regulation. Results The phenomenon of IAV in land NEE has been ubiquitously observed at global, regional and ecosystem scales. Global IAV is often attributable to either tropical or semi‐arid regions, or to some combination thereof, which is still under debate. Previous studies focus on identifying climate factors as driving forces of IAV, whereas biological mechanisms underlying the IAV of ecosystem NEE are less clear. We found that climate anomalies affect the IAV of NEE primarily through their differential impacts on ecosystem C uptake and respiration. Moreover, recent studies suggest that the carbon uptake period makes less contribution than the carbon uptake amplitude to IAV in NEE. Although land models incorporate most processes underlying IAV, their efficacy to predict the IAV in NEE remains low. Main conclusions To improve our ability to predict future IAV of the terrestrial C cycle, we have to understand biological mechanisms through which anomalies in climate factors cause the IAV of NEE. Future research needs to pay more attention not only to the differential effects of climate anomalies on photosynthesis and respiration but also to the relative importance of the C uptake period and amplitude in causing the IAV of NEE. Ultimately, we need multiple independent approaches, such as benchmark analysis, data assimilation and time‐series statistics, to integrate data, modelling frameworks and theory to improve our ability to predict future IAV in the terrestrial C cycle.

Tectono-stratigraphic evolution and hydrocarbon exploration in the Eocene Southern Lufeng Depression, Pearl River Mouth Basin, South China Sea - J. W. Ge; X. M. Zhu; X. T. Zhang; B. G. Jones; F. S. Yu; Z. C. Niu; M. Li (Australian Journal of Earth Sciences, 2017)

Selected Organochlorines in Human Blood and Urine in the South of the Russian Far East - Vasiliy Yu. Tsygankov; Nadezhda K. Khristoforova; Olga N. Lukyanova; Margarita D. Boyarova; Pavel F. Kiku; Marina V. Yarygina (Bulletin of Environmental Contamination and Toxicology, 2017)

Pretreatment with Antiviral Preparation Kagocel Normalizes the Content of Bone Marrow Multipotent Stromal Cells and TNFα in Blood Serum of CBA Mice Disturbed by Administration of S. typhimurium Antigen Complex In Vivo and Maintains High Concentration of IL-10 and Th1 Cytokines - Yu. F. Gorskaya; A. P. Suslov; E. N. Semenova; M. V. Konopleva; V. G. Nesternko (Bulletin of Experimental Biology and Medicine, 2017)

Effect of Lipid Surface Composition on the Formation and Structure of Fibrin Clots - D. R. Bakirova; D. A. Faizullin; Yu. A. Valiullina; V. V. Salnikov; Yu. F. Zuev (Bulletin of Experimental Biology and Medicine, 2017)

Studying the Toxic Effects of Some Biologically Active Peptides on the Model of Mouse Embryonic Stem Cells - A. G. Kobylyanskii; Yu. A. Zolotarev; L. A. Andreeva; I. A. Grivennikov; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2017)

Morphometric Characteristics of the Dorsal Nuclei of Clarke in the Rostral Segments of the Lumbar Part of the Spinal Cord on Cats - N. S. Merkul’eva; A. A. Veshchitskii; P. Yu. Shkorbatova; B. S. Shenkman; P. E. Musienko; F. N. Makarov (Neuroscience and Behavioral Physiology, 2017)

Soil pH, organic matter, and nutrient content change with the continuous cropping of Cunninghamia lanceolata plantations in South China - Yuanchun Yu; Jingyu Yang; Shucai Zeng; Daoming Wu; Douglass F. Jacobs; Joshua L. Sloan (Journal of Soils and Sediments, 2017)

The Question of the End Effector of Ischemic Preconditioning of the Heart - S. Yu. Tsibul’nikov; L. N. Maslov; A. V. Tsepokina; M. V. Khutornaya; A. G. Kutikhin; M. R. Tsibul’nikova; I. F. Nam (Neuroscience and Behavioral Physiology, 2017)

Lipoxygenase Inhibitors Nordihydroguaiaretic Acid and Fungus Lecanicillum lecanii Extract Induce Death of Lymphoid Leukemia Cells - M. V. Bibikova; N. A. Spiridonova; A. F. Korystova; L. N. Kublik; M. Kh. Levitman; V. V. Shaposhnikova; Yu. N. Korystov (Bulletin of Experimental Biology and Medicine, 2017)

NLR2 and TLR3, TLR4, TLR5 Ligands, Injected In Vivo, Improve after 1 h the Efficiency of Cloning and Proliferative Activity of Bone Marrow Multipotent Stromal Cells and Reduce the Content of Osteogenic Multipotent Stromal Cells in CBA Mice - Yu. F. Gorskaya; A. I. Tukhvatulin; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2017)

Counts of MSC in the Bone Marrow of Young and Old CBA Mice after a Single Exposure to Osteogenic Stimuli (Curettage, BMP-2 Injection) or Antigens (S. typhimurium Antigenic Complex) and in Heterotopic Bone Marrow Transplants - Yu. F. Gorskaya; A. Sh. Dzharullaeva; D. S. Onsina; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2017)

Compact Self-contained Cryosurgical Devices - A. F. Bobrikhin; A. G. Gudkov; D. I. Tsyganov; S. V. Agasieva; E. N. Gorlacheva; V. Yu. Leushin; V. D. Shashurin (Biomedical Engineering, 2017)

Characteristics of Mel Ibr Melanoma Line Subclone after Treatment with Chicken Embryo Extract - N. M. Suraeva; L. F. Morozova; O. O. Ryabaya; Yu. A. Khochenkova; A. V. Samoilov; O. S. Burova; N. V. Golubtsova; A. E. Barmashov; M. A. Baryshnikova (Bulletin of Experimental Biology and Medicine, 2017)

Natural resource landscapes of a marine bacterium reveal distinct fitness‐determining genes across the genome - Alison F. Takemura; Christopher H. Corzett; Fatima Hussain; Philip Arevalo; Manoshi Datta; Xiaoqian Yu; Frederique Le Roux; Martin F. Polz (Environmental Microbiology, 2017)
Summary Heterotrophic bacteria exploit diverse microhabitats in the ocean, from particles to transient gradients. Yet the degree to which genes and pathways can contribute to an organism's fitness on such complex and variable natural resource landscapes remains poorly understood. Here, we determine the gene‐by‐gene fitness of a generalist saprophytic marine bacterium ( Vibrio sp. F13 9CS106) on complex resources derived from its natural habitats – copepods ( Apocyclops royi ) and brown algae ( Fucus vesiculosus ) – and as reference substrates, glucose and the polysaccharide alginate, derived from brown algal cell walls. We find that resource complexity strongly buffers fitness costs of mutations, and that anabolic rather than catabolic pathways are more stringently required, likely due to functional redundancy in the latter. Moreover, while carbohydrate‐rich algae requires several synthesis pathways, protein‐rich Apocyclops does not, suggesting this ancestral habitat for Vibrios is a replete medium with metabolically redundant substrates. We also identify a candidate fitness trade‐off for algal colonization: deletion of mshA increases mutant fitness. Our results demonstrate that gene fitness depends on habitat composition, and suggest that this generalist uses distinct resources in different natural habitats. The results further indicate that substrate replete conditions may lead to relatively relaxed selection on catabolic genes.

The Role of Free Radical Oxidation in the Development of Experimental Urate Nephropathy - V. Yu. Perfil’ev; Ya. F. Zverev; A. Yu. Zharikov; V. M. Bryukhanov (Bulletin of Experimental Biology and Medicine, 2017)

The Content of Multipotent Stromal Cells in 3-4.5-Month Heterotopic Bone Marrow Transplants of CBA Mice Subjected to a Single Exposure to Osteogenic Stimuli (Curettage, BMP-2) or Antigens (S. typhimurium antigenic complex, LPS) - Yu. F. Gorskaya; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2017)

Development of regional pollution export coefficients based on artificial rainfall experiments and its application in North China - R. Liu; W. Yu; J. Shi; J. Wang; F. Xu; Z. Shen (International Journal of Environmental Science and Technology, 2017)

Erratum to: Computer Simulation of Molecular Interaction between Baclofen and the GABAB Receptor - A. M. Naumenko; L. M. Shapoval; A. Yu. Nyporko; I. S. Voiteshenko; O. V. Tsymbalyuk; V. F. Sagach; T. L. Davydovska (Neurophysiology, 2017)

Electrical Stimulation of the Vagus Nerve Modulates the Development of Oxygen Epilepsy in Rabbits - S. Yu. Zhilyaev; A. N. Moskvin; T. F. Platonova; I. T. Demchenko (Neuroscience and Behavioral Physiology, 2017)

Effect of Differential Light Quality on Morphology, Photosynthesis, and Antioxidant Enzyme Activity in Camptotheca acuminata Seedlings - Weiwu Yu; Yang Liu; Lili Song; Douglass F. Jacobs; Xuhua Du; Yeqing Ying; Qingsong Shao; Jiasheng Wu (Journal of Plant Growth Regulation, 2017)

Assessment of ecological instream flow requirements under climate change Pseudorasbora parva - Q. Liu; H. Yu; L. Liang; F. Ping; X. Xia; X. Mou; J. Liang (International Journal of Environmental Science and Technology, 2017)

Changes in the Structure of the Thymus under Conditions of Various Treatments for Experimental Mammary Tumor - O. V. Kazakov; A. V. Kabakov; A. F. Poveshchenko; I. Yu. Ishchenko; O. V. Poveshchenko; D. N. Strunkin; T. V. Raiter; S. V. Michurina; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2017)

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

Multistage amphiboles from the Galinge iron skarn deposit in Qiman Tagh, western China: evidence of igneous rocks replacement - M. Yu; C. -Y. Feng; Y. -F. Zhu; J. -W. Mao; Y. -M. Zhao; D. -X. Li (Mineralogy and Petrology, 2017)

Computer Simulation of Molecular Interaction Between Baclofen and the GABAB Receptor - A. M. Naumenko; L. M. Shapoval; A. Yu. Nyporko; M. I. Voiteshenko; A. V. Tsymbalyuk; V. F. Sagach; T. L. Davydovska (Neurophysiology, 2017)

The Thymus in Experimental Mammary Carcinogenesis and Polychemotherapy - O. V. Kazakov; A. V. Kabakov; I. Yu. Ishchenko; A. F. Poveshchenko; T. V. Raiter; D. N. Strunkin; S. V. Michurina; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2017)

Experience in the Use of the β-Interferon-1a Biosimilars CinnoVex and Genfaxon-44 at the Moscow City Multiple Sclerosis Center - O. G. Borets; M. V. Davydovskaya; T. L. Demina; N. Yu. Lashch; N. F. Popova; E. V. Popova; N. V. Khachanova; M. V. Khasaeva; S. G. Shchur; A. N. Boiko (Neuroscience and Behavioral Physiology, 2017)

Chromium-induced depression of 15N content and nitrate reductase activity in rice seedlings - X.-Z. Yu; F.-F. Zhang; W. Liu (International Journal of Environmental Science and Technology, 2017)

Effect of Hypotensive Drugs on Dynamics of Nitroxide-Producing Renal Function in Rats with Nephrogenic Hypertension - E. V. Eliseeva; E. F. Romanchenko; I. V. Dyuizen; A. V. Tyrtyshnikova; Yu. I. Pigolkin (Bulletin of Experimental Biology and Medicine, 2017)

A Device for Storage of Platelet-Containing Transfusion Media - A. G. Gudkov; V. Yu. Leushin; S. V. Agasieva; A. F. Bobrikhin; E. N. Gorlacheva; V. N. Lemondzhava; A. N. Aparnikov (Biomedical Engineering, 2017)

Effects of Arm Prosthesis Socket Design on Pressure Distribution on the Inner Surface of the Socket - Yu. I. Zamilatskii; S. F. Kurdibaylo; R. R. Gainullina (Biomedical Engineering, 2017)

Modeling of Processes of Storage of Containers with Platelet-Containing Media in Platelet Incubators - A. G. Gudkov; S. V. Agasieva; A. F. Bobrikhin; E. N. Gorlacheva; M. S. Zelenov; V. N. Lemondzhava; V. Yu. Leushin; A. V. Chernyshev; M. A. Levchuk; S. V. Chizhikov (Biomedical Engineering, 2017)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

Effect of Natural and 24-h Illumination on Mesenchymal Stem Cells - A. P. Lykov; N. A. Bondarenko; M. A. Surovtseva; I. I. Kim; O. V. Poveshchenko; I. Yu. Ishchenko; A. V. Kabakov; O. V. Kazakov; A. F. Poveshchenko; E. L. Zav’yalov; S. V. Michurina; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2016)

Evaluation of Hemodynamic Significance of Stenosis in Multiple Involvement of the Coronary Vessels by Mathematical Simulation - S. S. Simakov; T. M. Gamilov; F. Yu. Kopylov; Yu. V. Vasilevskii (Bulletin of Experimental Biology and Medicine, 2016)

The Concept of Ecthyma Gangrenosum Illustrated by a Fusarium oxysporum Infection in an Immunocompetent Individual - Yanping Jiang; Abdullah M. S. Al-Hatmi; Yining Xiang; Yu Cao; Albert H. G. Gerrits van den Ende; Ilse Curfs-Breuker; Jacques F. Meis; Hongguang Lu; G. Sybren de Hoog (Mycopathologia, 2016)

Measuring Nutrition Literacy in Breast Cancer Patients: Development of a Novel Instrument - Heather D. Gibbs; Edward F. Ellerbeck; Christie Befort; Byron Gajewski; Amy R. Kennett; Qing Yu; Danielle Christifano; Debra K. Sullivan (Journal of Cancer Education, 2016)

Dihydroquercetin Does Not Affect Age-Dependent Increase in Blood Pressure and Angiotensin-Converting Enzyme Activity in the Aorta of Hypertensive Rats - G. A. Slashcheva; V. A. Rykov; A. V. Lobanov; A. N. Murashev; Yu. A. Kim; T. V. Arutyunyan; A. F. Korystova; L. N. Kublik; M. Kh. Levitman; V. V. Shaposhnikona; Yu. N. Korystov (Bulletin of Experimental Biology and Medicine, 2016)

Modeling Processes of Storage of Platelet-Containing Transfusion Media in Polymer Containers - A. G. Gudkov; A. F. Bobrikhin; M. S. Zelenov; V. Yu. Leushin; V. N. Lemondzhava; I. N. Marzhanovsky; A. V. Chernyshev (Biomedical Engineering, 2016)

A System for Automated Distraction with Electrical Stimulation of Osteogenesis - F. Yu. Blynskiy; K. S. Brazovskii (Biomedical Engineering, 2016)

Ground-based phase wind-up and its application in yaw angle determination - M. Cai; W. Chen; D. Dong; C. Yu; Z. Zheng; F. Zhou; M. Wang; W. Yue (Journal of Geodesy, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Evaluating Induced Fractures Between a Large Artificial Lake and an Aquifer-Coal Seam System: A Case Study in Tangshan Coal Mine, China - Donglin Dong; Gang Lin; Yu-Feng F. Lin; Mingdong Zhao; Kai Li (Mine Water and the Environment, 2016)

Evaluation of Oxidative Metabolism in Leukocytes during Phagocytosis of Escherichia coli Carrying Genetic Constructs soxS::lux or katG::lux - I. F. Karimov; D. G. Deryabin; D. N. Karimova; T. Yu. Subbotina; I. V. Manukhov (Bulletin of Experimental Biology and Medicine, 2016)

Hybridization of downregulated-COMT transgenic switchgrass lines with field-selected switchgrass for improved biomass traits - Holly L. Baxter; Lisa W. Alexander; Mitra Mazarei; Ellen Haynes; Geoffrey B. Turner; Robert W. Sykes; Stephen R. Decker; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (Euphytica, 2016)

Ketamine-Midazolam Anesthesia Induces Total Inhibition of Cortical Activity in the Brain of Newborn Rats - Yu. A. Lebedeva; A. V. Zakharova; G. F. Sitdikova; A. L. Zefirov; R. N. Khazipov (Bulletin of Experimental Biology and Medicine, 2016)

Effect of Proline-Containing Oligopeptides PGP and RGP on Proliferative and Protein-Synthesizing Activity of Cultured Pulmonary Fibroblasts under Conditions of Oxidative Stress - I. V. Tolstenok; M. Yu. Fleishman; E. N. Sazonova; O. A. Lebed’ko; I. M. Maltseva; N. F. Myasoedov; S. S. Timoshin (Bulletin of Experimental Biology and Medicine, 2016)

Effect of Hematocrit and Erythrocyte Density on Intraoperative Blood Loss in Hemophilia A Patients During Total Knee Arthroplasty - E. S. Shurkhina; T. Yu. Polyanskaya; V. Yu. Zorenko; M. Kh. Azimova; V. M. Nesterenko; F. I. Ataullakhanov (Bulletin of Experimental Biology and Medicine, 2016)

Measurements of hydrogen, oxygen and carbon isotope variability in Sphagnum moss along a micro‐topographical gradient in a southern Patagonian peatland - N. J. Loader; F. A. Street‐Perrott; D. Mauquoy; T. P. Roland; S. van Bellen; T. J. Daley; D. Davies; P. D. M. Hughes; V. O. Pancotto; G. H. F. Young; M. J. Amesbury; D. J. Charman; et al. (Journal of Quaternary Science, 2016)
Peat archives offer a diverse range of physical and chemical proxies from which it is possible to study past environmental and ecological changes. Direct numerical calibration and verification is difficult so process‐based and mechanistic studies are therefore required to establish and quantify links between environmental changes and their associated proxy‐responses. Traditional ‘space‐for‐time’ calibrations provide a solution to this calibration problem, but are often unable to isolate a single environmental variable from other potentially confounding variables. In this study, we explored the potential of a site‐specific ‘space‐for‐time’ approach applied to a hummock‐hollow transect on an ombrotrophic raised bog in Patagonia, southern Chile. Coupled stable carbon, oxygen and hydrogen isotopic measurements were made on individual samples of Sphagnum moss cellulose and compared with plant‐associated waters, local hydrology, temperature and relative humidity, sampled at the same points along the study transect. Results reveal a range of environmental responses, which were supported by plant‐physiological models in the case of carbon and oxygen isotopes. For hydrogen isotopes, the results obtained from cellulose indicated a need for further research into hydrogen isotope fractionation in Sphagnum . We recommend conducting site‐specific characterization of plant response to support the development of peat‐based isotope records for palaeoenvironmental research, and where logistically possible, that monitoring is conducted over timescales appropriate to the time‐integrative nature of the Sphagnum record.

Strong and stable geographic differentiation of swamp buffalo maternal and paternal lineages indicates domestication in the China/Indochina border region - Yi Zhang; Yongfang Lu; Marnoch Yindee; Kuan‐Yi Li; Hsiao‐Yun Kuo; Yu‐Ten Ju; Shaohui Ye; Md Omar Faruque; Qiang Li; Yachun Wang; Vu Chi Cuong; Lan Doan Pham; et al. (Molecular Ecology, 2016)
The swamp type of the Asian water buffalo is assumed to have been domesticated by about 4000 years BP , following the introduction of rice cultivation. Previous localizations of the domestication site were based on mitochondrial DNA (mt DNA ) variation within China, accounting only for the maternal lineage. We carried out a comprehensive sampling of China, Taiwan, Vietnam, Laos, Thailand, Nepal and Bangladesh and sequenced the mt DNA Cytochrome b gene and control region and the Y‐chromosomal ZFY , SRY and DBY sequences. Swamp buffalo has a higher diversity of both maternal and paternal lineages than river buffalo, with also a remarkable contrast between a weak phylogeographic structure of river buffalo and a strong geographic differentiation of swamp buffalo. The highest diversity of the swamp buffalo maternal lineages was found in south China and north Indochina on both banks of the Mekong River, while the highest diversity in paternal lineages was in the China/Indochina border region. We propose that domestication in this region was later followed by introgressive capture of wild cows west of the Mekong. Migration to the north followed the Yangtze valley as well as a more eastern route, but also involved translocations of both cows and bulls over large distances with a minor influence of river buffaloes in recent decades. Bayesian analyses of various migration models also supported domestication in the China/Indochina border region. Coalescence analysis yielded consistent estimates for the expansion of the major swamp buffalo haplogroups with a credibility interval of 900 to 3900 years BP . The spatial differentiation of mt DNA and Y‐chromosomal haplotype distributions indicates a lack of gene flow between established populations that is unprecedented in livestock.

On Creating Global Gridded Terrestrial Water Budget Estimates from Satellite Remote Sensing - Yu Zhang; Ming Pan; Eric F. Wood (Surveys in Geophysics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Taxifolin and Fucoidin Abolish the Irradiation-Induced Increase in the Production of Reactive Oxygen Species in Rat Aorta - T. V. Arutyunyan; A. F. Korystova; L. N. Kublik; M. Kh. Levitman; V. V. Shaposhnikova; Yu. N. Korystov (Bulletin of Experimental Biology and Medicine, 2016)

Development and Implantation of a Biocompatible Auricular Prosthesis - V. A. Kasyanov; F. D. A. S. Pereira; V. A. Parfenov; E. V. Kudan; E. A. Bulanova; Yu. D. Khesuani; V. A. Mironov (Biomedical Engineering, 2016)

Critical conditions for tight oil charging and delineation of effective oil source rocks in Lucaogou Formation, Jimusar Sag, Junggar Basin, northwest China - L. Zhou; X. Pang; L. Wu; L. Kuang; F. Jiang; H. Pang; J. Peng; R. Yu (Australian Journal of Earth Sciences, 2016)

Stress-Induced Increases in Levels of Caspases in the Prefrontal Cortex in a Rat Model of PTSD - J. H. Zhang; M. Li; F. Han; Yu X. Shi (Neurophysiology, 2016)

Effect of Vascular Endothelial Growth Factor and Erythropoietin on Functional Activity of Fibroblasts and Multipotent Mesenchymal Stromal Cells - N. A. Bondarenko; Yu. V. Nikonorova; M. A. Surovtseva; A. P. Lykov; O. V. Poveshchenko; A. F. Poveshchenko; E. A. Pokushalov; A. B. Romanov; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2016)

Antioxidant Effect of Erythropoietin during Experimental Chronic Renal Failure - M. V. Osikov; L. F. Telesheva; Yu. I. Ageev (Bulletin of Experimental Biology and Medicine, 2015)

Successive Administration of Streptococcus Type 5 Group A Antigens and S. typhimurium Antigenic Complex Corrects Elevation of Serum Cytokine Concentration and Number of Bone Marrow Stromal Pluripotent Cells in CBA Mice Induced by Each Antigen Separately - Yu. F. Gorskaya; T. A. Danilova; V. I. Grabko; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2015)

Zinc Chloride and Zinc Acetate Injected into the Neostriatum Produce Opposite Effect on Locomotor Behavior of Rats - A. F. Yakimovskii; S. Yu. Kryzhanovskaya (Bulletin of Experimental Biology and Medicine, 2015)

Use of food waste as fish feeds: effects of prebiotic fibers (inulin and mannanoligosaccharide) on growth and non-specific immunity of grass carp (Ctenopharyngodon idella) - Wing Y. Mo; Zhang Cheng; Wai M. Choi; Clare H. I. Lun; Yu B. Man; James T. F. Wong; Xun W. Chen; Stanley C. K. Lau; Ming H. Wong (Environmental Science and Pollution Research, 2015)

The effect of a multi-gob, pier-type roof structure on coal pillar load-bearing capacity and stress distribution - J. X. Yang; C. Y. Liu; B. Yu; F. F. Wu (Bulletin of Engineering Geology and the Environment, 2015)

Morphological Criteria of Cell Differentiation Stages in Experimental Hepatocarcinoma and Evaluation of Antitumor Drug Efficiency - N. P. Bgatova; L. V. Omel’yanchuk; A. A. Pozhidaeva; V. F. Semeshin; A. P. Lykov; O. V. Poveshchenko; O. P. Makarova; L. N. Rachkovskaya; Yu. I. Borodin; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2015)

Global diversity and taxonomy of the Auricularia auricula-judae complex (Auriculariales, Basidiomycota) - Fang Wu; Yuan Yuan; Shuang-Hui He; Asanka R. Bandara; Kevin D. Hyde; Vera F. Malysheva; De-Wei Li; Yu-Cheng Dai (Mycological Progress, 2015)

Activation of P-450-Dependent Monooxygenases Modulates the Diuretic Effect of Histochrome in Rats - O. S. Talalaeva; V. M. Bryukhanov; Ya. F. Zverev; V. V. Lampatov; A. Yu. Zharikov; N. P. Mischenko; I. I. Sheremet’eva (Bulletin of Experimental Biology and Medicine, 2015)

Atrokylindriopsis, a new genus of hyphomycetes from Hainan, China, with relationship to Chaetothyriales - Ying-Rui Ma; Ji-Wen Xia; Jian-Mei Gao; Xiang-Yu Li; Rafael F. Castañeda Ruíz; Xiu-Guo Zhang; Zhuang Li (Mycological Progress, 2015)

Modernizing Pharmaceutical Manufacturing: from Batch to Continuous Production - Sau L. Lee; Thomas F. O’Connor; Xiaochuan Yang; Celia N. Cruz; Sharmista Chatterjee; Rapti D. Madurawe; Christine M. V. Moore; Lawrence X. Yu; Janet Woodcock (Journal of Pharmaceutical Innovation, 2015)

Hexachlorocyclohexane (HCH) in human blood in the south of the Russian Far East - Vasiliy Yu. Tsygankov; Margarita D. Boyarova; Pavel F. Kiku; Marina V. Yarygina (Environmental Science and Pollution Research, 2015)

Composition of primary kimberlite magma: constraints from melting and diamond dissolution experiments - A. G. Sokol; A. F. Khokhryakov; Yu. N. Palyanov (Contributions to Mineralogy and Petrology, 2015)

Modeling of the redox state dynamics in photosystem II of Chlorella pyrenoidosa Chick cells and leaves of spinach and Arabidopsis thaliana from single flash-induced fluorescence quantum yield changes on the 100 ns–10 s time scale - N. E. Belyaeva; F.-J. Schmitt; V. Z. Paschenko; G. Yu. Riznichenko; A. B. Rubin (Photosynthesis Research, 2015)

Molecular phylogeny and taxonomic revision of the genus Bolbitius (Bolbitiaceae, Agaricales) in Russia - Ekaterina F. Malysheva; Vera F. Malysheva; Tatiana Yu. Svetasheva (Mycological Progress, 2015)

Associations between diabetes medication use and risk of second breast cancer events and mortality - Gregory S. Calip; Onchee Yu; Kent F. Hoskins; Denise M. Boudreau (Cancer Causes & Control, 2015)

Changes in the Morphological and Immunological Characteristics of Mel Ibr Melanoma Cells in Response to Chicken Embryo Extract - N. M. Suraeva; L. F. Morozova; A. V. Samoilov; O. S. Burova; V. A. Golubeva; M. A. Baryshnikova; A. Yu. Baryshnikov (Bulletin of Experimental Biology and Medicine, 2015)

Proliferation, Migration, and Production of Nitric Oxide by Bone Marrow Multipotent Mesenchymal Stromal Cells from Wistar Rats in Hypoxia and Hyperglycemia - A. P. Lykov; Yu. V. Nikonorova; N. A. Bondarenko; O. V. Poveshchenko; I. I. Kim; A. F. Poveshchenko; V. I. Konenkov (Bulletin of Experimental Biology and Medicine, 2015)

Effects of Glyprolines on DNA Synthesis and Free Radical Oxidation in Mouse Gastric Mucosa Under Physiological Conditions and During Therapy with Oral Non-Steroid Anti-Inflammatory Drugs - M. Yu. Fleishman; I. V. Tolstenok; O. A. Lebed’ko; L. A. Andreeva; N. F. Myasoedov; S. S. Timoshin (Bulletin of Experimental Biology and Medicine, 2015)

Effect of Erythropoietin on Lymphocytes Apoptosis in Experimental Chronic Renal Failure - M. V. Osikov; L. F. Telesheva; Yu. I. Ageev (Bulletin of Experimental Biology and Medicine, 2015)

Erratum to: Coherent Fluctuation Nephelometry: A Rapid Method for Urine Screening for Bacterial Contamination - A. S. Gur’ev; A. Yu. Volkov; I. I. Dolgushin; A. V. Pospelova; S. F. Rastopov; A. Yu. Savochkina; V. I. Sergienko (Bulletin of Experimental Biology and Medicine, 2015)

Comparison of Structural Development and Biochemical Accumulation of Waxy and Non-waxy Wheat Caryopses - X.R. Yu; L. Zhou; J. Zhang; H. Yu; D.R. Gao; B.Q. Zhang; F. Xiong; Y.J. Gu; Z. Wang (Cereal Research Communications, 2015)

Effects of Kagocel® on the Counts of Multipotent Stromal Cells, Expression of Cytokine Genes in Primary Cultures of Bone Marrow Stromal Cells, and Serum Cytokine Concentrations in CBA Mice - Yu. F. Gorskaya; V. I. Grabko; M. V. Konopleva; A. P. Suslov; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2015)

Expression of Pattern Recognition Receptors by Nociceptive Metasympathetic Neurons - L. V. Filippova; E. Yu. Bystrova; F. S. Malyshev; O. N. Platonova; A. D. Nozdrachev (Bulletin of Experimental Biology and Medicine, 2015)

Online monitoring of the nanoscale zero-valent iron process for trichloroethylene wastewater treatment - R.-F. Yu; F.-H. Chi; W.-P. Cheng; M.-H. Wang (International Journal of Environmental Science and Technology, 2015)

Coherent Fluctuation Nephelometry: A Rapid Method for Urine Screening for Bacterial Contamination - A. S. Gur’ev; A. Yu. Volkov; I. I. Dolgushin; A. V. Pospelova; S. F. Rastopov; A. Yu. Savochkina; V. I. Sergienko (Bulletin of Experimental Biology and Medicine, 2015)

Environmental lead exposure is associated with visit-to-visit systolic blood pressure variability in the US adults - Mohammed F. Faramawi; Robert Delongchamp; Yu-Sheng Lin; Youcheng Liu; Saly Abouelenien; Lori Fischbach; Supriya Jadhav (International Archives of Occupational and Environmental Health, 2015)

Eco-geographic units, population hierarchy, and a two-level conservation strategy with reference to a critically endangered salmonid, Sakhalin taimen Parahucho perryi - Lev A. Zhivotovsky; Andrey A. Yurchenko; Vitaly D. Nikitin; Sergei N. Safronov; Marina V. Shitova; Sergei F. Zolotukhin; Sergei S. Makeev; Steven Weiss; Peter S. Rand; Anatoly Yu. Semenchenko (Conservation Genetics, 2015)

Do phosphoinositides regulate membrane water permeability of tobacco protoplasts by enhancing the aquaporin pathway? - Xiaohong Ma; Arava Shatil-Cohen; Shifra Ben-Dor; Noa Wigoda; Imara Y. Perera; Yang Ju Im; Sofia Diminshtein; Ling Yu; Wendy F. Boss; Menachem Moshelion; Nava Moran (Planta, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Effects of Acoustic and EHF Impulses on Multipotent Stromal Cells during Formation of Bone Marrow Containing Heterotopic Organs in Tissue Engineered Constructions - R. K. Chaikhalyan; V. I. Yusupov; Yu. F. Gorskaya; A. I. Kuralesova; Yu. V. Gerasimov; A. P. Sviridov; A. Kh. Tambiev; N. N. Vorob’eva; A. G. Grosheva, V. V. Shishkova; I. L. Moskvina; V. N. Bagratashvili (Bulletin of Experimental Biology and Medicine, 2015)

Differently Directed Influences of Semax on the Formation and Functional Impairments of an Active Avoidance Reaction in Rats - A. N. Inozemtsev; A. E. Agapitova; S. B. Bokieva; N. Yu. Glazova; N. G. Levitskaya; A. A. Kamenskii; N. F. Myasoedov (Neuroscience and Behavioral Physiology, 2015)

Estimation of flood damage functions for river basin planning: a case study in Bangladesh - Y. C. Ethan Yang; Patrick A. Ray; Casey M. Brown; Abedalrazq F. Khalil; Winston H. Yu (Natural Hazards, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Effects of Neural Crest-Derived Multipotent Stem Cells on Regeneration of an Injured Peripheral Nerve in Mice - R. G. Vasyliev; A. E. Rodnichenko; S. N. Shamalo; A. S. Demidchouk; I. F. Labunets; Yu. B. Chaikovskii; G. M. Butenko (Neurophysiology, 2015)

Effects of Combined Treatment with Complex S. typhimurium Antigens and Factors Stimulating Osteogenesis (Curettage, BMP-2) on Multipotent Bone Marrow Stromal Cells and Serum Concentration of Cytokines in CBA Mice - Yu. F. Gorskaya; T. A. Danilova; A. S. Karyagina; V. G. Lunin; V. I. Grabko; M. S. Bartov; A. V. Gromov; T. M. Grunina; L. A. Soboleva; I. M. Shapoval; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2015)

The Effects of Oxidative Stress on the Compressive Damage Thresholds of C2C12 Mouse Myoblasts: Implications for Deep Tissue Injury - Yifei Yao; Zhitao Xiao; Singwan Wong; Yu-Chun Hsu; Truman Cheng; Chih-Chieh Chang; Liming Bian; Arthur F. T. Mak (Annals of Biomedical Engineering, 2015)

The B″ regulatory subunit of protein phosphatase 2A mediates the dephosphorylation of rice retinoblastoma-related protein-1 - Edit Ábrahám; Ping Yu; Ilona Farkas; Zsuzsanna Darula; Erzsébet Varga; Noémi Lukács; Ferhan Ayaydin; Katalin F. Medzihradszky; Viktor Dombrádi; Dénes Dudits; Gábor V. Horváth (Plant Molecular Biology, 2015)

Erratum to: On-line evaluating the SS removals for chemical coagulation using digital image analysis and artificial neural networks - R.-F. Yu; W. Wang; W.-P. Cheng; M.-M. Chen (International Journal of Environmental Science and Technology, 2015)

Migratory history of African longfinned eel Anguilla mossambica from Maningory River, Madagascar: discovery of a unique pattern in otolith Sr:Ca ratios - Yu-Jia Lin; Brian M. Jessop; Olaf L. F. Weyl; Yoshiyuki Iizuka; Shih-Huan Lin; Wann-Nian Tzeng (Environmental Biology of Fishes, 2015)

Erratum to: Prenatal exposure to escitalopram and/or stress in rats - Chase H. Bourke; Catherine F. Capello; Swati M. Rogers; Megan L. Yu; Katherine A. Boss-Williams; Jay M. Weiss; Zachary N. Stowe; Michael J. Owens (Psychopharmacology, 2014)

Camel Thorn Extract Reduces Activity of Angiotensin-Converting Enzyme in Rat Aorta Increased during Aging and Treatment with NO-Synthase Inhibitor - T. V. Arutyunyan; A. F. Korystova; L. N. Kublik; M. Kh. Levitman; V. V. Shaposhnikova; N. O. Appazov; R. A. Narmanova; S. Zh. Ibadullayeva; Yu. N. Korystov (Bulletin of Experimental Biology and Medicine, 2014)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Soft perforation of cardiolipin-containing planar lipid bilayer membrane by cytochrome c and H2O2 - V. F. Antonov; M. N. Puchkov; E. A. Korepanova; O. Yu. Nemchenko; V. Borodulin (European Biophysics Journal, 2014)

Proteolysis of Pro-Gly-Pro-Leu in the Hippocampus, Cerebellum, and Cerebral Cortex in Rats after Intravenous Injection - K. V. Shevchenko; T. V. V’yunova; L. A. Andreeva; I. Yu. Nagaev; V. P. Shevchenko; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2014)

Hypoglycemic and Anticoagulant Effects of Tetrapeptide Pro-Gly-Pro-Leu in Hypercholesterolemia - T. A. Shubina; M. E. Grigor’eva; L. A. Lyapina; T. Yu. Obergan; N. F. Myasoedov; L. A. Andreeva (Bulletin of Experimental Biology and Medicine, 2014)

Studies of the Involvement of CO-Chaperone Hdj1 in Modulating Sleep and Behavior Using in Vivo Microrna Technology - Yu. F. Pastukhov; I. V. Ekimova; D. A. Meshalkina; M. A. Guzeev; M. V. Chernyshev; K. V. Lapshina; E. A. Lukina; V. F. Lazarev; K. A. Khudik; I. V. Guzhova (Neuroscience and Behavioral Physiology, 2014)

Changes in the Transcription Profile of the Hippocampus in Response to Administration of the Tuftsin Analog Selank - T. A. Kolomin; T. Yu. Agapova; Ya. V. Agniullin; S. I. Shram; M. I. Shadrina; P. A. Slominskii; S. A. Limborskaya; N. F. Myasoedov (Neuroscience and Behavioral Physiology, 2014)

On-line evaluating the SS removals for chemical coagulation using digital image analysis and artificial neural networks - R.-F. Yu (International Journal of Environmental Science and Technology, 2014)

Correlation of HER-2/Neu Protein Expression and HER2 Gene Amplification with Clinical Morphological Parameters of Nonsmall Cell Lung Cancer - D. S. Kobyakov; A. M. Avdalyan; I. P. Bobrov; E. Yu. Bychkova; A. F. Lazarev; E. L. Lushnikova; L. M. Nepomnyashchikh (Bulletin of Experimental Biology and Medicine, 2014)

Profile of MicroRNA Expression in Brain Tumors of Different Malignancy - F. A. Koshkin; D. A. Chistyakov; A. G. Nikitin; A. N. Konovalov; A. A. Potapov; D. Yu. Usachyov; D. I. Pitskhelauri; G. L. Kobyakov; L. V. Shishkina; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2014)

Neurotensin-Like Peptides as Potential Antipsychotics: Modulation of the Serotonin System - N. V. Kost; V. K. Meshavkin; E. Yu. Khashaba; O. Yu. Sokolov; M. E. Voevodina; Yu. A. Zolotarev; L. A. Andreeva; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2014)

Development of endosperm cells and starch granules in common wheat - Y.P. Jing; D.T. Liu; X.R. Yu; F. Xiong; D.L. Li; Y.K. Zheng; Y.F. Hao; Y.J. Gu; Z. Wang (Cereal Research Communications, 2014)

Argyrophilic Proteins of Nucleolar Organizer Regions and Proliferative Activity of Cells in Squamous Cell Carcinoma of the Lung - D. S. Kobyakov; V. V. Klimachev; A. M. Avdalyan; I. P. Bobrov; E. Yu. Bychkova; N. M. Kruglova; A. F. Lazarev; E. L. Lushnikova; L. M. Nepomnyashchikh (Bulletin of Experimental Biology and Medicine, 2014)

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

Three Heat Shock Protein Genes from Bactrocera (Tetradacus) minax Enderlein: Gene Cloning, Characterization, and Association with Diapause - Z C Lü; L H Wang; G F Zhang; F H Wan; J Y Guo; H Yu; J B Wang (Neotropical Entomology, 2014)

Mathematical Simulation of p53–Mdm2 Protein Biological System Regulation - O. F. Voropaeva; Yu. I. Shokin; L. M. Nepomnyashchikh; S. R. Senchukova (Bulletin of Experimental Biology and Medicine, 2014)

Expression of VEGF, GFAP, and BDNF Genes in the Brain of Rats after Fractionated γ-Irradiation According to Different Protocols - Ya. A. Zorkina; G. M. Yusubalieva; F. A. Koshkin; A. Yu. Chamorsov; A. V. Kistenev; G. E. Gorlachev; A. V. Golanov; A. A. Potapov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Comparison of complete genome sequences of dog rabies viruses isolated from China and Mexico reveals key amino acid changes that may be associated with virus replication and virulence - Fulai Yu; Guoqing Zhang; Xiangfu Zhong; Na Han; Yunfeng Song; Ling Zhao; Min Cui; Simon Rayner; Zhen F. Fu (Archives of Virology, 2014)

Mathematical Modeling of Functioning of the p53–Mdm2 Protein System - O. F. Voropaeva; Yu. I. Shokin; L. M. Nepomnyashchikh; S. R. Senchukova (Bulletin of Experimental Biology and Medicine, 2014)

Emergence of NDM-producing non-baumannii Acinetobacter spp. isolated from China - R. Zhang; Y.-Y. Hu; X.-F. Yang; D.-X. Gu; H.-W. Zhou; Q.-F. Hu; K. Zhao; S.-F. Yu; G.-X. Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Comparison of the Efficiency of Transplantation of Bone Marrow Multipotent Mesenchymal Stromal Cells Cultured under Normoxic and Hypoxic Conditions and Their Conditioned Media on the Model of Acute Lung Injury - R. K. Chailakhyan; A. V. Aver’yanov; F. G. Zabozlaev; P. A. Sobolev; A. V. Sorokina; D. A. Akul’shin; Yu. V. Gerasimov (Bulletin of Experimental Biology and Medicine, 2014)

Analysis of the Effects of Blue Light on Morphofunctional Status of In Vitro Cultured Blastocysts from Mice Carrying Gene of Enhanced Green Fluorescent Protein (EGFP) - N. Yu. Sakharova; L. M. Mezhevikina; A. A. Smirnov; E. F. Vikhlyantseva (Bulletin of Experimental Biology and Medicine, 2014)

Cognitive Deficits In Friedreich Ataxia Correlate with Micro-structural Changes in Dentatorubral Tract - Hamed Akhlaghi; Johnson Yu; Louise Corben; Nellie Georgiou-Karistianis; John L. Bradshaw; Elsdon Storey; Martin B. Delatycki; Gary F. Egan (The Cerebellum, 2014)

Effects of High-Salt Diet on the Activity of Angiotensin-Converting Enzyme and Generation of Reactive Oxygen Species in Rat Aorta - T. V. Arutyunyan; A. F. Korystova; L. N. Kublik; M. Kh. Levitman; V. V. Shaposhnikova; Yu. N. Korystov (Bulletin of Experimental Biology and Medicine, 2014)

Convergence of a Hydraulic Solver with Pressure-Dependent Demands - Yu. Kovalenko; N. B. Gorev; I. F. Kodzhespirova; E. Prokhorov; G. Trapaga (Water Resources Management, 2014)

The Effect of Glutathione as Chain Transfer Agent in PNIPAAm-Based Thermo-responsive Hydrogels for Controlled Release of Proteins - Pawel W. Drapala; Bin Jiang; Yu-Chieh Chiu; William F. Mieler; Eric M. Brey; Jennifer J. Kang-Mieler; Victor H. Pérez-Luna (Pharmaceutical Research, 2014)

Microspectroscopic Study of Liposome-to-cell Interaction Revealed by Förster Resonance Energy Transfer - Svetlana L. Yefimova; Irina Yu. Kurilchenko; Tatyana N. Tkacheva; Nataliya S. Kavok; Igor N. Todor; Nataliya Yu. Lukianova; Vasyl F. Chekhun; Yuriy V. Malyukin (Journal of Fluorescence, 2014)

Accumulation of heavy metals in leaf vegetables from agricultural soils and associated potential health risks in the Pearl River Delta, South China - C. Y. Chang; H. Y. Yu; J. J. Chen; F. B. Li; H. H. Zhang; C. P. Liu (Environmental Monitoring and Assessment, 2014)

Age structure of massive Porites lutea corals at Luhuitou fringing reef (northern South China Sea) indicates recovery following severe anthropogenic disturbance - M. X. Zhao; K. F. Yu; Q. M. Zhang; Q. Shi; G. Roff (Coral Reefs, 2014)

Effects of Fullerene C60 on Proteomic Profile of Danio Rerio Fish Embryos - G. P. Kuznetsova; O. V. Larina; N. A. Petushkova; Yu. S. Kisrieva; N. F. Samenkova; O. P. Trifonova; I. I. Karuzina; O. M. Ipatova; K. V. Zolotaryov; Yu. A. Romashova; A. V. Lisitsa (Bulletin of Experimental Biology and Medicine, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Ultrastructure and functional activity of chloroplasts in wheat leaves under root chilling - Yu. V. Venzhik; A. F. Titov; V. V. Talanova; E. A. Miroslavov (Acta Physiologiae Plantarum, 2014)

Gamma Oscillations in the Somatosensory Cortex of Newborn Rats - E. V. Gerasimova; A. V. Zakharov; Yu. A. Lebedeva; A. R. Inacio; M. G. Minlebaev; G. F. Sitdikova; R. N. Khazipov (Bulletin of Experimental Biology and Medicine, 2014)

Expression of Genes Encoding Serotonin Receptors and SERT in Various Brain Structures of Stressed Rats after Chronic Exposure to Ultrasound - A. Yu. Morozova; E. A. Zubkov; F. A. Koshkin; Z. I. Storozheva; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2014)

Flood frequency under changing climate in the upper Kafue River basin, southern Africa: a large scale hydrological model application - Cosmo Ngongondo; Lu Li; Lebing Gong; Chong-Yu Xu; Berhanu F. Alemaw (Stochastic Environmental Research and Risk Assessment, 2013)

Surveying the Down syndrome mouse model resource identifies critical regions responsible for chronic otitis media - Mahmood F. Bhutta; Michael T. Cheeseman; Yann Herault; Yuejin E. Yu; Steve D. M. Brown (Mammalian Genome, 2013)

Recruitment limitation of dominant tree species with varying seed masses in a subtropical evergreen broad-leaved forest - Y. Luo; F. He; S. Yu (Community Ecology, 2013)

Role of Cytochrome b5 and α-Tocopherol to Microsomal and Mitochondrial Oxidation - Z. S. Agadzhanyan; A. D. Doroshchuk; Yu. K. Shiryaeva; L. F. Dmitriev (Bulletin of Experimental Biology and Medicine, 2013)

Relationship between the Argyrophilic Proteins of the Nucleolar Organizer Region and Stage of Squamous-Cell Carcinoma of the Lung - D. S. Kobyakov; V. V. Klimachev; A. M. Avdalyan; I. P. Bobrov; E. Yu. Bychkova; A. F. Lazarev; E. L. Lushnikova; L. M. Nepomnyashchikh (Bulletin of Experimental Biology and Medicine, 2013)

STIM1 and Orai1 mediate CRAC channel activity and are essential for human glioblastoma invasion - Rajender K. Motiani; María C. Hyzinski-García; Xuexin Zhang; Matthew M. Henkel; Iskandar F. Abdullaev; Yu-Hung Kuo; Khalid Matrougui; Alexander A. Mongin; Mohamed Trebak (Pflügers Archiv - European Journal of Physiology, 2013)

Coral communities of the remote atoll reefs in the Nansha Islands, southern South China Sea - M. X. Zhao; K. F. Yu; Q. Shi; T. R. Chen; H. L. Zhang; T. G. Chen (Environmental Monitoring and Assessment, 2013)

Effect of BMP-2 Protein on the Count and Osteogenic Properties of Multipotent Stromal Cells and Expression of Cytokine Genes in Primary Cultures of Bone Marrow and Spleen Cells from CBA Mice Immunized with Bacterial Antigens - Yu. F. Gorskaya; T. A. Danilova; M. V. Mezentseva; I. M. Shapoval; T. M. Grunina; M. S. Bartov; A. S. Karyagina; V. G. Lunin; R. K. Chailakhyan; A. I. Kuralesova; Yu. V. Gerasimov; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2013)

Structural and physiological characterization during wheat pericarp development - F. Xiong; X. R. Yu; L. Zhou; F. Wang; A. S. Xiong (Plant Cell Reports, 2013)

Plastic Efficiency of Different Implants Used for Repair of Soft and Bone Tissue Defects - Yu. M. Iriyanov; V. F. Chernov; S. A. Radchenko; A. V. Chernov (Bulletin of Experimental Biology and Medicine, 2013)

New Features in the Subsurface Structure Model of El Hierro Island (Canaries) from Low-Frequency Microseismic Sounding: An Insight into the 2011 Seismo-Volcanic Crisis - A. V. Gorbatikov; F. G. Montesinos; J. Arnoso; M. Yu Stepanova; M. Benavent; A. A. Tsukanov (Surveys in Geophysics, 2013)

Prenatal exposure to escitalopram and/or stress in rats - Chase H. Bourke; Catherine F. Capello; Swati M. Rogers; Megan L. Yu; Katherine A. Boss-Williams; Jay M. Weiss; Zachary N. Stowe; Michael J. Owens (Psychopharmacology, 2013)

Effects of Thermal Preconditioning on Convulsive Activity in Rats with an Inherited Form of Epilepsy - K. A. Khudik; Yu. F. Pastukhov; I. V. Guzhova (Neuroscience and Behavioral Physiology, 2013)

“Finnish” Mutations in LDL Receptor Gene: A Rare Cause of Familial Hypercholesterolemia in St. Petersburg and Petrozavodsk - T. Yu. Komarova; A. S. Golovina; N. A. Grudinina; F. M. Zakharova; V. A. Korneva; B. M. Lipovetskii; M. P. Serebrenitskaya; V. O. Konstantinov; V. B. Vasilyev; M. Yu. Mandelshtam (Bulletin of Experimental Biology and Medicine, 2013)

Effects of Transplantation of Human Cord Blood Mononuclear Cells Expressing the Recombinant VEGF and FGF2 Genes into Spinal Cord Traumatic Injury Sites in Rats - G. F. Shaimardanova; Ya. O. Mukhamedshina; A. A. Rizvanov; I. I. Salafutdinov; Yu. A. Chelyshev (Neuroscience and Behavioral Physiology, 2013)

Efficacy and Tolerance of Glatiramer Acid (Copaxone) on Long-Term Use: 10 Years of Experience at the Moscow City Multiple Sclerosis Center - A. N. Boiko; M. V. Davydovskaya; T. L. Demina; N. Yu. Lashch; V. V. Ovcharov; E. V. Popova; N. F. Popova; A. V. Romashkin; O. V. Boiko; N. V. Khachanova; S. N. Sharanova; S. G. Shchur; et al. (Neuroscience and Behavioral Physiology, 2013)

The organization of digit contact timing during grasping - L. F. Schettino; A. Pallottie; C. Borland; S. Nessa; A. Nawroj; Y.-C. Yu (Experimental Brain Research, 2013)

Reversal of ATP-binding cassette drug transporter activity to modulate chemoresistance: why has it failed to provide clinical benefit? - Man Yu; Alberto Ocana; Ian F. Tannock (Cancer and Metastasis Reviews, 2013)

Levels, seasonal variations, and health risks assessment of ambient air pollutants in the residential areas - W. C. Zhao; J. P. Cheng; Z. Y. Yu; Q. L. Tang; F. Cheng; Y. W. Yin; W. H. Wang (International Journal of Environmental Science and Technology, 2013)

Diurnal Variations of Carbon Dioxide, Methane, and Nitrous Oxide Vertical Fluxes in a Subtropical Estuarine Marsh on Neap and Spring Tide Days - Chuan Tong; Jia F. Huang; Zhi Q. Hu; Yu F. Jin (Estuaries and Coasts, 2013)

Tonoplast of Beta vulgaris L. contains detergent-resistant membrane microdomains - Natalia V. Ozolina; Irina S. Nesterkina; Ekaterina V. Kolesnikova; Ryurik K. Salyaev; Vadim N. Nurminsky; Alexander L. Rakevich; Evgueni F. Martynovich; Michael Yu. Chernyshov (Planta, 2013)

Chaperone Hsp70 Content in Dopaminergic Neurons of the Substantia Nigra Increases in Proteasome Dysfunction - Yu. F. Pastukhov; I. V. Ekimova; I. V. Guzhova; I. V. Romanova; Z. E. Artyukhina (Neuroscience and Behavioral Physiology, 2013)

Impact of recent coastal development and human activities on Nha Trang Bay, Vietnam: evidence from a Porites lutea geochemical record - A. D. Nguyen; J-x Zhao; Y-x Feng; W-p Hu; K-f Yu; M. Gasparon; T. B. Pham; T. R. Clark (Coral Reefs, 2013)

Content of Vitamins B1 and B2 in Germinating Grain - Yu. R. Rahmatullina; A. F. Doronin; O. A. Vrzhesinskaya; V. M. Kodentsova (Bulletin of Experimental Biology and Medicine, 2013)

Coherence and Phase Analysis of Theta Oscillations in the Septohippocampal System during Generation of Convulsive Activity - I. V. Kabanova; V. V. Sinelnikova; I. Yu. Popova; V. F. Kichigina; R. R. Aliev (Neuroscience and Behavioral Physiology, 2013)

Network Effects of Glutamate on Neuronal Activity in the Medial Septum/Diagonal Band Complex In Vitro - I. Yu. Popova; E. N. Karavaev; V. F. Kitchigina (Neuroscience and Behavioral Physiology, 2013)

Glial Satellite Cells as a Source of Supplementary Energy Supply for Neurons during Spike Activity at Elevated Frequency - N. V. Pasikova; Yu. S. Mednikova; D. N. Voronkov; R. M. Khudoerkov; F. V. Kopytova (Neuroscience and Behavioral Physiology, 2013)

Analysis of the Efficiency of Gene-Cell Therapy in Transgenic Mice with Amyotrophic Lateral Sclerosis Phenotype - M. A. Mukhamedyarov; A. A. Rizvanov; Z. Z. Safiullov; A. A. Izmailov; G. A. Sharifullina; V. V. Solovieva; V. Yu. Fedotova; I. I. Salafutdinov; E. E. Cherenkova; F. V. Bashirov; M. S. Kaligin; S. R. Abdulkhakov; et al. (Bulletin of Experimental Biology and Medicine, 2013)

Usage of Plasmid Vector Carrying vegf and fgf2 Genes after Spinal Cord Injury in Rats - G. F. Shaymardanova; Y. O. Mukhamedshina; I. I. Salafutdinov; A. A. Rizvanov; Yu. A. Chelyshev (Bulletin of Experimental Biology and Medicine, 2013)

Effects of inhibitors on ferricyanide uptake and assimilation by plants - X. Z. Yu; F. Z. Zhang; X. Y. Peng (International Journal of Environmental Science and Technology, 2013)

Erratum to: Simulating cold season snowpack: Impacts of snow albedo and multi-layer snow physics - D. Waliser; J. Kim; Y. Xue; Y. Chao; A. Eldering; R. Fovell; A. Hall; Q. Li; K. N. Liou; J. McWilliams; S. Kapnick; R. Vasic; et al. (Climatic Change, 2013)

Intraclonal diversity of the Pseudomonas aeruginosa cystic fibrosis airway isolates TBCF10839 and TBCF121838: distinct signatures of transcriptome, proteome, metabolome, adherence and pathogenicity despite an almost identical genome sequence - Jens Klockgether; Norbert Miethke; Peter Kubesch; Yu‐Sing Bohn; Inka Brockhausen; Nina Cramer; Leo Eberl; Joachim Greipel; Christian Herrmann; Susanne Herrmann; Sonja Horatzek; Meike Lingner; et al. (Environmental Microbiology, 2013)
Summary Microevolution of closely related Pseudomonas aeruginosa was compared in the clone TB strains TBCF10839 and TBCF121838 which had been isolated from two unrelated individuals with cystic fibrosis who had acquired clone TB during a local outbreak. Compared with the strain PAO1 reference sequence the two clone TB genomes shared 23 155 nucleotide exchanges, 32 out‐of‐frame indels in the coding region and another repertoire of replacement and genomic islands such as PAGI‐1, PAGI‐2, PAGI‐5, LESGI‐1 and LES‐prophage 4. Only TBCF121838 carried a genomic island known from Ralstonia pickettii . Six of the seven strain‐specific sequence variations in the core genome were detected in genes affecting motility, biofilm formation or virulence, i.e. non‐synonymous nucleotide substitutions in mexS, PA3729, PA5017, mifR, a frameshift mutation in pilF (TBCF121838) and an intragenic deletion in pilQ (TBCF10839). Despite their almost identical genome sequence the two strains differed strongly from each other in transcriptome and metabolome profiles, mucin adherence and phagocytosis assays. TBCF121838 was susceptible to killing by neutrophils, but TBCF10839 could grow in leucocytes. Microevolution in P. aeruginosa apparently can generate novel complex traits by few or even single mutations provided that predisposing mutational events had occurred before in the clonal lineage.

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Post-Traumatic Changes in the Spinal Cord in Rats after Transplantation of Mononuclear Cells from Human Umbilical Blood Modified with the vegf and fgf2 Genes - G. F. Shaimardanova; Ya. O. Mukhamedshina; S. S. Arkhipova; I. I. Salafutdinov; A. A. Rizvanov; Yu. A. Chelyshev (Neuroscience and Behavioral Physiology, 2012)

The Thermophysiology of Paradoxical Sleep - Yu. F. Pastukhov; I. V. Ekimova (Neuroscience and Behavioral Physiology, 2012)

Structure and variances of equatorial zonal circulation in a multimodel ensemble - B. Yu; F. W. Zwiers; G. J. Boer; M. F. Ting (Climate Dynamics, 2012)

Molecular Cloning, Characterization, and Expression Analysis of Genes Encoding Gibberellin 20-Oxidase in Dasypyrum villosum Dwarf Mutant - P. Cai; H. Long; G. B. Deng; Z. F. Pan; Z. S. Peng; M. Q. Yu (Plant Molecular Biology Reporter, 2012)

Content of mRNA for NMDA Glutamate Receptor Subunits in the Frontal Cortex and Striatum of Rats after Morphine Withdrawal Is Related to the Degree of Abstinence - D. I. Peregud; A. A. Yakovlev; M. Yu. Stepanichev; M. V. Onufriev; L. F. Panchenko; N. V. Gulyaeva (Bulletin of Experimental Biology and Medicine, 2012)

Can Summary Nitrite+Nitrate Content Serve as an Indicator of NO Synthesis Intensity in Body Tissues? - V. Yu. Titov; A. V. Ivanova; V. A. Petrov; V. A. Serezhenkov; V. D. Mikoyan; A. F. Vanin; A. N. Osipov (Bulletin of Experimental Biology and Medicine, 2012)

Genome characterization of Salem virus reveals its evolutionary intermediate status in the subfamily Paramyxovirinae - D. E. Anderson; E. J. Dubovi; M. Yu; L.-F. Wang; R. W. Renshaw (Archives of Virology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Expression of Renal Crystallization Inhibitors in Experimental Nephrolithiasis - A. Yu. Zharikov; Yu. G. Motin; Ya. F. Zverev; V. V. Lampatov; V. M. Bryukhanov; O. S. Talalaeva (Bulletin of Experimental Biology and Medicine, 2012)

Changes in Sleep during Degeneration of Neurons in the Substantia Nigra Induced by the Proteasome Inhibitor Lactacystin - Yu. F. Pastukhov; A. Yu. Chesnokova; A. A. Yakimchuk; I. V. Ekimova; I. V. Romanova; K. A. Khudik (Neuroscience and Behavioral Physiology, 2012)

Hypoxic Preconditioning – a Phenomenon Increasing the Tolerance of Cardiomyocytes to Hypoxia/Reoxygenation - L. N. Maslov; Yu. B. Lishmanov; F. Kolar; A. G. Portnichenko; Yu. K. Podoksenov; I. G. Khaliulin; H. Wang; J. M. Pei (Neuroscience and Behavioral Physiology, 2012)

Experiments on Alcocytes Containing Enzyme Nanoparticles for Reducing Toxic Blood Concentration of Ethanol - Yu. G. Kaminsky; E. A. Kosenko; Yu. G. Alexandrovich; F. I. Ataullakhanov (Bulletin of Experimental Biology and Medicine, 2012)

Effect of Antibodies to Glutamate on the Content of Neurotransmitter Amino Acids in Brain Structures of Rats with Ischemic Damage to the Prefrontal Cortex - G. A. Romanova; Yu. N. Kvashennikova; F. M. Shakova; T. V. Davydova (Bulletin of Experimental Biology and Medicine, 2012)

Polyphyllin D induces apoptosis in human erythrocytes through Ca2+ rise and membrane permeabilization - Minghui Gao; K. L. Cheung; Irene P. Lau; W. S. Yu; K. P. Fung; Biao Yu; J. F. Loo; S. K. Kong (Archives of Toxicology, 2012)

Genotypic diversity enhances invasive ability of Spartina alterniflora - X. Y. WANG; D. W. SHEN; J. JIAO; N. N. XU; S. YU; X. F. ZHOU; M. M. SHI; X. Y. CHEN (Molecular Ecology, 2012)
Although genetic diversity is very important for alien species, which have to cope with new environments, little is known about the role that genetic diversity plays in their invasive success. In this study, we set up a manipulation experiment including three levels of genotypic diversity to test whether genotypic diversity can enhance the invasive ability of alien species, in our case the invasive Spartina alterniflora in China, and to infer the underlying mechanisms. There was no significant relationship between genotypic diversity and parameters of performance in the first year; however, from the summer of the second year onwards, genotypic diversity enhanced four of the six parameters of performance. After two growing seasons, there were significant positive relationships between genotypic diversity and maximum spread distance, patch size, shoot number per patch, and aboveground biomass. Moreover, abundance of the native dominant species Scirpus mariqueter was marginally significantly decreased with genotypic diversity of S. alterniflora , suggesting that enhanced invasive ability of S. alterniflora may have depressed the growth of the native species. There was no significant difference in most measures of performance among six genotypes, but we observed a transgressive over performance in four measures in multiple‐genotype patches. At the end of the experiment, there were significant nonadditive effects of genotypic diversity according to Monte Carlo permutations, in six‐genotype, but not three‐genotype plots. Our results indicated that both additive and nonadditive effects played roles in the positive relationship between genetic diversity and invasion success, and nonadditive effects were stronger as duration increased.

Effects of pH on ferri-cyanide uptake and assimilation by several plants - X. Z. Yu; F. Li; K. Li (International Journal of Environmental Science and Technology, 2012)

Lack of ceruloplasmin expression alters aspects of copper transport to the fetus and newborn, as determined in mice - Yu-Ling Chu; Eric N. Sauble; Anthony Cabrera; Aleeza Roth; M. Leigh Ackland; Julian F. B. Mercer; Maria C. Linder (BioMetals, 2012)

The Nootropic and Analgesic Effects of Semax Given via Different Routes - D. M. Manchenko; N. Yu. Glazova; N. G. Levitskaya; L. A. Andreeva; A. A. Kamenskii; N. F. Myasoedov (Neuroscience and Behavioral Physiology, 2012)

Treatment of Exacerbations of Multiple Sclerosis without the Use of Corticosteroids: The Role of Metabolic and Antioxidant Therapy - G. N. Bisaga; M. M. Odinak; A. N. Boiko; Yu. B. Melnik; N. F. Popova (Neuroscience and Behavioral Physiology, 2012)

Fungus-growing Allomerus ants are associated with antibiotic-producing actinobacteria - Ryan F. Seipke; Jörg Barke; Mario X. Ruiz-Gonzalez; Jérôme Orivel; Douglas W. Yu; Matthew I. Hutchings (Antonie van Leeuwenhoek, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

A preliminary study on the molecular evolution of the two routes of intrauterine transmission of HBV - H. Sun; X. Tang; B. Wang; J. Zhang; H. Cheng; H. Su; F. Li; K. Men; S. Wang; L. Zhao; J. Xu; X. Yu; et al. (Archives of Virology, 2012)

A New Method of Producing Monoclinic Paracetamol Suitable for Direct Compression - Andrey G. Ogienko; Elena V. Boldyreva; Andrey Yu Manakov; Vladimir V. Boldyrev; Alexander S. Yunoshev; Anna A. Ogienko; Svetlana A. Myz; Alexei I. Ancharov; Andrey F. Achkasov; Tatiana N. Drebushchak (Pharmaceutical Research, 2011)

Simulating cold season snowpack: Impacts of snow albedo and multi-layer snow physics - D. Waliser; J. Kim; Y. Xue; Y. Chao; A. Eldering; R. Fovell; A. Hall; Q. Li; K. N. Liou; J. McWilliams; S. Kapnick; R. Vasic; et al. (Climatic Change, 2011)

Changes in the Levels of Inhibitory and Excitatory Amino Acids in the Brain Structures of Female Rats with Cobalt Epileptogenic Focus during Different Phases of the Estrous Cycle - Yu. B. Filatova; T. A. Voronina; P. M. Klodt; V. S. Kudrin; L. N. Nerobkova; F. K. Rider; G. N. Avakyan (Bulletin of Experimental Biology and Medicine, 2011)

The Effect of Semax and Its C-End Peptide PGP on the Morphology and Proliferative Activity of Rat Brain Cells During Experimental Ischemia: A Pilot Study - Vasily V. Stavchansky; Vadim V. Yuzhakov; Alexandra Yu. Botsina; Veronika I. Skvortsova; Lyubov N. Bondurko; Marina G. Tsyganova; Svetlana A. Limborska; Nikolay F. Myasoedov; Lyudmila V. Dergunova (Journal of Molecular Neuroscience, 2011)

Long-term changes of heavy metal and sulphur concentrations in ecosystems of the Taymyr Peninsula (Russian Federation) North of the Norilsk Industrial Complex - Alexander V. Zhulidov; Richard D. Robarts; Dmitry F. Pavlov; J. Kämäri; Tatiana Yu. Gurtovaya; J. J. Meriläinen; Igor N. Pospelov (Environmental Monitoring and Assessment, 2011)

Effects of Quercetin on the Severity of Chemically Induced Convulsions and 70-kDal Heat Shock Protein Content in Brain Structures in Rats - L. E. Nitsinskaya; I. V. Ekimova; I. V. Guzhova; B. A. Feizulaev; Yu. F. Pastukhov (Neuroscience and Behavioral Physiology, 2011)

Effects of Immunization with Group A Streptococcal Antigens on the Transplantability of Mouse Bone Marrow Stromal Stem Cells, Counts of Stromal Precursor Cells, and Their Osteogenic Characteristics - Yu. F. Gorskaya; T. A. Danilova; O. V. Lebedinskaya; V. G. Lunin; V. I. Grabko; N. E. Sharapova; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2011)

Four new species of Orbiliaceae from Yunnan, China - H. Y. Su; Y. Zhang; H. O. Baral; X. Y. Yang; M. H. Mo; Y. H. Cao; M. H. Chen; Z. F. Yu (Mycological Progress, 2011)

A novel rice calmodulin-like gene, OsMSR2, enhances drought and salt tolerance and increases ABA sensitivity in Arabidopsis - Guo-Yun Xu; Pedro S. C. F. Rocha; Man-Ling Wang; Meng-Liang Xu; Yan-Chun Cui; Luo-Ye Li; Yu-Xing Zhu; Xinjie Xia (Planta, 2011)

Blockade of Type 5 Metabotropic Glutamate Receptors Prevents Impairment of Motor Behavior Evoked by Intrastriatal Administration of Picrotoxin in Rats - A. F. Yakimovskii; Yu. A. Redka; A. L. Yakubenko (Neuroscience and Behavioral Physiology, 2011)

Effects of Permafrost Microorganisms on the Quality and Duration of Life of Laboratory Animals - L. F. Kalenova; Yu. G. Sukhovei; A. V. Brushkov; V. P. Melnikov; T. A. Fisher; I. M. Besedin; M. A. Novikova; Yu. A. Efimova (Neuroscience and Behavioral Physiology, 2011)

Facilitation associated with three contrasting shrub species in heavily grazed pastures on the eastern Tibetan Plateau - P. Li; B. Krüsi; S. Li; X. Cai; F. Yu (Community Ecology, 2011)

Rice Gene OsDSR-1 Promotes Lateral Root Development in Arabidopsis Under High-Potassium Conditions - Xu Ming Yin; Pedro S. C. F. Rocha; Man Ling Wang; Yu Xin Zhu; Luo Ye Li; Shu Feng Song; Xinjie Xia (Journal of Plant Biology, 2011)

Age-Associated Reduction of the Count and Functional Activity of Stromal Precursor Cells Can Be Caused by Both True Reduction (Exhaustion) of Cell Pool and Regulatory Effects of the Organism - Yu. F. Gorskaya; T. A. Danilova; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2011)

Count of Splenic Stromal Precursor Cells in Mice and Expression of Cytokine Genes in These Cells in Primary Cultures during Different Periods after Immunization of Animals with S. typhimurium Antigens - Yu. F. Gorskaya; T. A. Danilova; M. V. Mezentseva; I. M. Shapoval; A. N. Narovlyanskii; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2011)

Association of Cold Receptor TRPM8 Gene Polymorphism with Blood Lipid Indices and Anthropometric Parameters in Shorians - T. A. Potapova; N. S. Yudin; I. V. Pilipenko; V. F. Kobsev; A. G. Romashchenko; E. V. Shakhtshneider; M. Yu. Ogarkov; M. I. Voevoda (Bulletin of Experimental Biology and Medicine, 2011)

Potential of Preventive Treatment of Alzheimer’s Disease: Results of a Three-Year Prospective Open Comparative Trial of the Efficacy and Safety of Courses of Treatment with Cerebrolysin and Cavinton in Elderly Patients with Mild Cognitive Impairment Syndrome - S. I. Gavrilova; I. V. Kolykhalov; Ya. B. Fedorova; N. D. Selezneva; Ya. B. Kalyn; I. F. Roshchina; M. M. Odinak; A. Yu. Emelin; A. V. Kashin; A. V. Gustov; E. A. Antipenko; Yu. A. Korshunova; et al. (Neuroscience and Behavioral Physiology, 2011)

Degradation of fluoranthene by a newly isolated strain of Herbaspirillum chlorophenolicum from activated sludge - Hong X. Xu; Hai Y. Wu; Yu P. Qiu; Xiao Q. Shi; Gen H. He; Jing F. Zhang; Ji C. Wu (Biodegradation, 2011)

Gene Expression Profile in Rat Dorsal Root Ganglion Following Sciatic Nerve Injury and Systemic Neurotrophin-3 Administration - Lu-Ting Kuo; Shao-Yu Tsai; Michael J. Groves; Shu F. An; Francesco Scaravilli (Journal of Molecular Neuroscience, 2011)

Clinical and microbiological characteristics of urine culture-confirmed genitourinary tuberculosis at medical centers in Taiwan from 1995 to 2007 - H.-L. Hsu; C.-C. Lai; M.-C. Yu; F.-L. Yu; J.-C. Lee; C.-H. Chou; C.-K. Tan; P.-C. Yang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Covariability of SST and surface heat fluxes in reanalyses and CMIP3 climate models - Bin Yu; G. J. Boer; F. W. Zwiers; W. J. Merryfield (Climate Dynamics, 2011)

Pilot in vitro study of the parameters of artificial niche for osteogenic differentiation of human stromal stem cell pool - I. A. Khlusov; M. Yu. Khlusova; K. V. Zaitsev; T. D. Kolokol’tsova; Yu. P. Sharkeev; V. F. Pichugin; E. V. Legostaeva; I. E. Trofi mova; A. S. Klimov; A. I. Zhdanova (Bulletin of Experimental Biology and Medicine, 2011)

Analysis of characteristics of paratyphoid A in 157 Chinese inpatients between 1998 and 2009 - F. Yu; S. Fan; X. Fan; P. Dong; X. Wang; Y. Chen; J. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Spontaneous Activity of Cortical Neurons in Vitro and Its Regulation by Acetylcholine - Yu. S. Mednikova; F. V. Kopytova; M. N. Zhadin (Neuroscience and Behavioral Physiology, 2010)

Effects of Human Defensin-α1 on Trypanosoma cruzi Trypomastigotes in Vitro - Yu. E. Kleschenko; L. P. Karpenko; F. Villalta (Bulletin of Experimental Biology and Medicine, 2010)

Variation of cytosine methylation in 57 sweet orange cultivars - J-G. Fang; C-N. Song; J-L. Qian; X–Y. Zhang; L-F. Shangguan; H-P. Yu; X-C. Wang (Acta Physiologiae Plantarum, 2010)

Study of the Efficiency of Transplantation of Human Neural Stem Cells to Rats with Spinal Trauma: the Use of Functional Load Tests and BBB Test - S. V. Lebedev; A. V. Karasev; V. P. Chekhonin; E. A. Savchenko; I. V. Viktorov; Yu. A. Chelyshev; G. F. Shaimardanova (Bulletin of Experimental Biology and Medicine, 2010)

Effect of Antibodies to Glutamate on Retention of Conditioned Passive Avoidance Response in Rats with Ischemic Injury of the Prefrontal Cortex - G. A. Romanova; F. M. Shakova; V. Yu. Gorbatov; Yu. N. Kvashennikova; T. V. Davydova (Bulletin of Experimental Biology and Medicine, 2010)

Dietary intake of arsenic by children and adults from Jinhu area of China - P. Liu; C.-N. Wang; X.-Y. Song; Y.-F. Yu; Y.-N. Wu (Food Additives & Contaminants: Part A, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

A comparative study of farm nutrient budgets and nutrient flows of certified organic and non-organic farms in China, Brazil and Egypt - Myles Oelofse; Henning Høgh-Jensen; Lucimar S. Abreu; Gustavo F. Almeida; Ahmed El-Araby; Qiao Yu Hui; Andreas de Neergaard (Nutrient Cycling in Agroecosystems, 2010)

Reaction of Oligoglia to Spinal Cord Injury in Rats and Transplantation of Human Olfactory Ensheathing Cells - G. A. Masgutova; E. A. Savchenko; I. V. Viktorov; R. F. Masgutov; Yu. A. Chelyshev (Bulletin of Experimental Biology and Medicine, 2010)

Invasion history, distribution, and relative abundances of Dreissena bugensis in the old world: a synthesis of data - A. V. Zhulidov; A. V. Kozhara; G. H. Scherbina; T. F. Nalepa; A. Protasov; S. A. Afanasiev; E. G. Pryanichnikova; D. A. Zhulidov; T. Yu. Gurtovaya; D. F. Pavlov (Biological Invasions, 2010)

Electrooculogram Detection of Eye Movements on Gaze Displacement - D. P. Belov; S. Yu. Eram; S. F. Kolodyazhnyi; I. E. Kanunikov; O. V. Getmanenko (Neuroscience and Behavioral Physiology, 2010)

Floral development in Impatiens chishuiensis (Balsaminaceae): formation of two well-developed anterolateral sepals and four carpels - S. X. Yu; X.-R. Zhou; G.-F. Xu; L. Meng; H.-Y. Bi (Plant Systematics and Evolution, 2010)

Determinants of the geographical extent of invasive plants in China: effects of biogeographical origin, life cycle and time since introduction - Qiao Q. Huang; Chen Qian; Yu Wang; Xin Jia; Xin F. Dai; Hao Zhang; Fei He; Shao L. Peng; Gen X. Wang (Biodiversity and Conservation, 2010)

Non-Pharmacological Correction of Impaired Microcirculation in Children with Diabetic Polyneuropathy - N. V. Nikolaeva; N. V. Bolotova; V. F. Luk’yanov; Yu. M. Raigorodskii; E. N. Tkacheva (Neuroscience and Behavioral Physiology, 2010)

Information policy and management framework for environmental protection organization with ecosystem conception - H. W. Chen; R. F. Yu; S. L. Liaw; W. C. Huang (International Journal of Environmental Science and Technology, 2010)

Berberis phyllody is a phytoplasma-associated disease - Z. N. Li; J. G. Song; C. P. Zhang; X. Q. Yu; K. K. Wu; W. J. Wu; Y. F. Wu; Y. Xiang (Phytoparasitica, 2010)

Historical biogeography of the genus Chamaecyparis (Cupressaceae, Coniferales) based on its fossil record - (Christopher) Yu-Sheng Liu; Barbara A. R. Mohr; James F. Basinger (Palaeobiodiversity and Palaeoenvironments, 2009)

The Role of Cell Fusion in Physiological and Reparative Regeneration of the Cerebral Cortex - A. A. Pal’tsyn; N. B. Konstantinova; G. A. Romanova; F. M. Shakova; Yu. N. Kvashennikova; A. A. Kubatiev (Bulletin of Experimental Biology and Medicine, 2009)

Genetic variation and pathogenicity of highly virulent porcine reproductive and respiratory syndrome virus emerging in China - J. Wu; J. Li; F. Tian; S. Ren; M. Yu; J. Chen; Z. Lan; X. Zhang; Dongwan Yoo; Jinbao Wang (Archives of Virology, 2009)

Perchlorate Exposure Induces Hypothyroidism and Affects Thyroid-Responsive Genes in Liver But Not Brain of Quail Chicks - Yu Chen; F. M. Anne McNabb; Jill C. Sible (Archives of Environmental Contamination and Toxicology, 2009)

Correlational Relationships Between the Hippocampus and Medial Septal Area and Their Changes During Epileptogenesis - V. V. Sinel’nikova; I. Yu. Popova; V. F. Kichigina (Neuroscience and Behavioral Physiology, 2009)

Dosimetric and Mathematical Monitoring of the Effect of X-Ray Therapy of Cervical Cancer - R. V. Stavitskii; V. A. Titova; N. Yu. Dobrovol’skaya; O. N. Plautin; A. F. Teliyants; A. A. Kokontsev; A. L. Lebedev; A. G. Rerberg (Biomedical Engineering, 2009)

Selective reduction of alcohol drinking in Sardinian alcohol-preferring rats by a sigma-1 receptor antagonist - Valentina Sabino; Pietro Cottone; Yu Zhao; Luca Steardo; George F. Koob; Eric P. Zorrilla (Psychopharmacology, 2009)

Assessment of Cu (II)-Bearing Montmorillonite on Cd Adsorption - D. Y. Yu; W. H. Song; B. Zhou; W. F. Li (Biological Trace Element Research, 2009)

Molecular characterization of a distinct begomovirus infecting Allamanda cathartica in Guangdong, China - Z. F. He; M. J. Mao; H. Yu; H. P. Li; X. Chen (Archives of Virology, 2009)

aPCR-SSCP and DNA sequencing detecting two silent SNPs at KAP8.1 gene in the cashmere goat - M. Zhao; H. Chen; X. Wang; H. Yu; M. Wang; J. Wang; X. Y. Lan; C. F. Zhang; L. Z. Zhang; Y. K. Guo; B. Zhang; S. R. Hu (Molecular Biology Reports, 2009)

Mononuclear Leukocytes from Mice with Resected Tumor Induce Resistance to Transplantation of Tumor Cells to Animals - S. M. Sitdikova; M. V. Kiselevskii; V. Yu. Sel’chuk; B. S. Amandzholov; K. E. Voyushin; I. M. Luchenko; F. V. Donenko (Bulletin of Experimental Biology and Medicine, 2009)

Immunogenic Characteristics of Recombinant OMPF-Like Porin from Yersinia Pseudotuberculosis Outer Membrane - O. Yu. Portnyagina; O. V. Sidorova; V. A. Khomenko; O. D. Novikova; O. P. Vostrikova; T. F. Solovjeva (Bulletin of Experimental Biology and Medicine, 2009)

Levels of Spontaneous Activity and Spike Responses of Cortical Neurons to Local Administration of Excitatory Amino Acids to Their Dendrites and Bodies - Yu. S. Mednikova; F. V. Kopytova; M. N. Zhadin (Neuroscience and Behavioral Physiology, 2009)

Orexin A-induced extracellular calcium influx in prefrontal cortex neurons involves L-type calcium channels - J. X. Xia; S. Y. Fan; J. Yan; F. Chen; Y. Li; Z. P. Yu; Z. A. Hu (Journal of Physiology and Biochemistry, 2009)

Determination of synthetic drugs used to adulterate botanical dietary supplements using QTRAP LC-MS/MS - Y. Chen; L. Zhao; F. Lu; Y. Yu; Y. Chai; Y. Wu (Food Additives & Contaminants: Part A, 2009)

Posttraumatic Survival of Sensory Neurons during Allotransplantation of Rat Embryonic Tissues into the Nerve - R. F. Masgutov; G. A. Masgutova; I. S. Raginov; A. I. Malomuzh; M. V. Nigmetzyanova; Yu. A. Chelyshev (Bulletin of Experimental Biology and Medicine, 2009)

SP-D-Dependent Regulation of NO Metabolism in Lipopolysaccharide-Stimulated Peritoneal Macrophages - E. N. Atochina-Vasserman; E. V. Abramova; Y. Tomer; P. Scott; V. A. Nazarov; S. V. Kruglov; M. F. Beers; A. J. Gow; I. Yu. Malyshev (Bulletin of Experimental Biology and Medicine, 2009)

Microinjection of 70-kDal heat shock protein into the oral reticular nucleus of the pons suppresses rapid eye movement sleep in pigeons - E. A. Gusel’nikova; Yu. F. Pastukhov (Neuroscience and Behavioral Physiology, 2009)

In‐flight MTF measurement and compensation for the CBERS‐2 WFI - X. Y. Li; X. F. Gu; T. Yu (International Journal of Remote Sensing, 2009)

Evaluation of Immunotherapy Efficiency in Mouse CaO-1 Ovarian Carcinoma Treated by Vaccines Based on Dendritic Cells - S. M. Sitdikova; M. V. Kiselevskii; V. Yu. Sel’chuk; B. S. Amandzholov; E. A. Kurbatova; F. V. Donenko (Bulletin of Experimental Biology and Medicine, 2009)

Complete genome sequence of Nariva virus, a rodent paramyxovirus - L. S. Lambeth; M. Yu; D. E. Anderson; G. Crameri; B. T. Eaton; L.-F. Wang (Archives of Virology, 2009)

Morphofunctional Study of the Therapeutic Efficacy of Human Mesenchymal and Neural Stem Cells in Rats with Diffuse Brain Injury - A. F. Tsyb; V. V. Yuzhakov; L. M. Roshal’; G. T. Sukhikh; A. G. Konoplyannikov; G. N. Sushkevich; N. D. Yakovleva; I. E. Ingel’; L. N. Bandurko; L. E. Sevan’kaeva; L. N. Mikhina; N. K. Fomina; et al. (Bulletin of Experimental Biology and Medicine, 2009)

Canopy assessment of biochemical features by ground-based hyperspectral data for an invasive species, giant reed (Arundo donax) - Shaokui Ge; Raymond I. Carruthers; David F. Spencer; Qian Yu (Environmental Monitoring and Assessment, 2008)

Effects of Lead on Hepatic Antioxidant Status and Transcription of Superoxide Dismutase Gene in Pigs - D. Y. Yu; W. F. Li; B. Deng; X. F. Mao (Biological Trace Element Research, 2008)

Effect of Montmorillonite Superfine Composite on Growth Performance and Tissue Lead Level in Pigs - D. Y. Yu; X. L. Li; W. F. Li (Biological Trace Element Research, 2008)

Brain mu-opioid receptor binding: relationship to relapse to cocaine use after monitored abstinence - David A. Gorelick; Yu Kyeong Kim; Badreddine Bencherif; Susan J. Boyd; Richard Nelson; Marc L. Copersino; Robert F. Dannals; J. James Frost (Psychopharmacology, 2008)

Development of a Smart Nano-vehicle to Target Cerebrovascular Amyloid Deposits and Brain Parenchymal Plaques Observed in Alzheimer’s Disease and Cerebral Amyloid Angiopathy - Edward K. Agyare; Geoffry L. Curran; Muthu Ramakrishnan; Caroline C. Yu; Joseph F. Poduslo; Karunya K. Kandimalla (Pharmaceutical Research, 2008)

Changes in oscillatory activity of neurons in the medial septal area in animals with a model of chronic temporal epilepsy - A. E. Mal’kov; E. N. Karavaev; I. Yu. Popova; V. F. Kichigina (Neuroscience and Behavioral Physiology, 2008)

Comparisons of grey and neural network prediction of industrial park wastewater effluent using influent quality and online monitoring parameters - T. Y. Pai; S. H. Chuang; T. J. Wan; H. M. Lo; Y. P. Tsai; H. C. Su; L. F. Yu; H. C. Hu; P. J. Sung (Environmental Monitoring and Assessment, 2008)

Radiation Load Associated with Target-Oriented and Panoramic X-Ray Examination Using Portable X-Ray Apparatuses - N. N. Potrakhov; E. N. Potrakhov; A. Yu. Gryaznov; B. F. Vorob’ev (Biomedical Engineering, 2008)

PS II model-based simulations of single turnover flash-induced transients of fluorescence yield monitored within the time domain of 100 ns–10 s on dark-adapted Chlorella pyrenoidosa cells - N. E. Belyaeva; F.-J. Schmitt; R. Steffen; V. Z. Paschenko; G. Yu. Riznichenko; Yu. K. Chemeris; G. Renger; A. B. Rubin (Photosynthesis Research, 2008)

Primary light-energy conversion in tetrameric chlorophyll structure of photosystem II and bacterial reaction centers: II. Femto- and picosecond charge separation in PSII D1/D2/Cyt b559 complex - I. V. Shelaev; F. E. Gostev; V. A. Nadtochenko; A. Ya. Shkuropatov; A. A. Zabelin; M. D. Mamedov; A. Yu. Semenov; O. M. Sarkisov; V. A. Shuvalov (Photosynthesis Research, 2008)

Antioxidative activities and the total phenolic contents of tonic Chinese Medicinal Herbs - D.-J. Guo; H.-L. Cheng; S.-W. Chan; P. H.-F. Yu (Inflammopharmacology, 2008)

Molecular cloning, functional characterization and expression analysis of a novel monosaccharide transporter gene OsMST6 from rice (Oryza sativa L.) - Yongqin Wang; Yuguo Xiao; Yu Zhang; Chenglin Chai; Gang Wei; Xiaoli Wei; Honglin Xu; Mei Wang; Pieter B. F. Ouwerkerk; Zhen Zhu (Planta, 2008)

Studies of Benzothiazole and Benzoselenazole Squaraines as Fluorescent Probes for Albumins Detection - Kateryna D. Volkova; Vladyslava B. Kovalska; Mykhaylo Yu. Losytskyy; Artur Bento; Lucinda V. Reis; Paulo F. Santos; Paulo Almeida; Sergiy M. Yarmoluk (Journal of Fluorescence, 2008)

A study of NO trafficking from dinitrosyl–iron complexes to the recombinant E. coli transcriptional factor SoxR - Feng-Chun Lo; Chang-Li Chen; Chien-Ming Lee; Ming-Che Tsai; Tsai-Te Lu; Wen-Feng Liaw; Steve S.-F. Yu (JBIC Journal of Biological Inorganic Chemistry, 2008)

Antioxidant and endothelium-stabilizing effects of simvaglyzin on rabbits with experimental hypercholesterolemia - Yu. I. Ragino; V. A. Vavilin; N. F. Salakhutdinov; S. I. Makarova; E. M. Stakhneva; O. G. Safronova; V. V. Lyakhovich; Yu. P. Nikitin; G. A. Tolstikov (Bulletin of Experimental Biology and Medicine, 2008)

Gonadotoxic effect of polychlorobiphenyls - D. S. Gromenko; Sh. N. Galimov; Z. K. Amirova; A. Z. Abdullina; Yu. Yu. Gromenko; E. F. Galimova (Bulletin of Experimental Biology and Medicine, 2008)

Myocardial resistance to ischemic and reperfusion injuries under conditions of chronic administration of opioid receptor agonists and antagonists - Yu. B. Lishmanov; D. L. Stakheev; A. V. Krylatov; N. V. Naryzhnaya; L. N. Maslov; M. V. Ovchinnikov; F. Kolar (Bulletin of Experimental Biology and Medicine, 2008)

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

A sequential analysis method for the prediction of tropical hurricanes - Alexandr I. Sukov; Vladimir Yu. Soldatov; Vladimir F. Krapivin; Arthur P. Cracknell; Costas A. Varotsos (International Journal of Remote Sensing, 2008)

Comparative analysis of the locations of the NR1 and NR2 NMDA receptor subunits in honeybee (Apis mellifera) and fruit fly (Drosophila melanogaster, Canton-S wild-type) cerebral ganglia - T. G. Zachepilo; Yu. F. Il’inykh; N. G. Lopatina; D. A. Molotkov; A. V. Popov; E. V. Savvateeva-Popova; A. I. Vaido; E. G. Chesnokova (Neuroscience and Behavioral Physiology, 2008)

Purification and properties of Sandercyanin, a blue protein secreted in the mucus of blue forms of walleye, Sander vitreus - Chi-Li Yu; Daniel Ferraro; S. Ramaswamy; Mark H. Schmitz; Wayne F. Schaefer; David T. Gibson (Environmental Biology of Fishes, 2008)

Effect of stress adaptation on cyclic nucleotide content in myocardial tissue during acute ischemia/reperfusion - N. V. Naryzhnaya; L. N. Maslov; Yu. B. Lishmanov; F. Kolář (Bulletin of Experimental Biology and Medicine, 2008)

Analysis of metabolic flux in Escherichia coli expressing human-like collagen in fed-batch culture - Yan E. Luo; Dai D. Fan; Long A. Shang; Hui J. Shi; Xiao X. Ma; Yu Mi; Gui F. Zhao (Biotechnology Letters, 2008)

Effects of gram-positive microorganisms and their products on in vivo survival of hemopoietic clonogenic cells - S. Ya. Proskuryakov; A. G. Konoplyannikov; O. A. Konoplyannikova; A. F. Tsyb; D. Yu. Logunov; B. S. Naroditsky; A. L. Gintsburg (Bulletin of Experimental Biology and Medicine, 2008)

Role of ATP-sensitive K+-channels in antiarrhythmic and cardioprotective action of adaptation to intermittent hypobaric hypoxia - F. Kolar; J. Nekar; B. Ostadal; L. N. Maslov; D. L. Stakheev; A. S. Tayurskaya; Yu. B. Lishmanov (Bulletin of Experimental Biology and Medicine, 2008)

Review of methods of small‐footprint airborne laser scanning for extracting forest inventory data in boreal forests - J. Hyyppä; H. Hyyppä; D. Leckie; F. Gougeon; X. Yu; M. Maltamo (International Journal of Remote Sensing, 2008)

In situ analysis by microspectroscopy reveals triterpenoid compositional patterns within leaf cuticles of Prunus laurocerasus - Marcia M. L. Yu; Stanislav O. Konorov; H. Georg Schulze; Michael W. Blades; Robin F. B. Turner; Reinhard Jetter (Planta, 2008)

The nicotinic receptor blocker hexamethonium alters neuronal responses to glutamate in the medial septal area of the brain of the ground squirrel in vitro - E. N. Karavaev; I. Yu. Popova; V. F. Kichigina (Neuroscience and Behavioral Physiology, 2008)

Role of the cholinergic mechanisms of the ventrolateral preoptic area of the hypothalamus in regulating the state of sleep and waking in pigeons - T. G. Komarova; I. V. Ekimova; Yu. F. Pastukhov (Neuroscience and Behavioral Physiology, 2008)

Interbands behave as decompacted autonomous units in Drosophila melanogaster polytene chromosomes - Valery F. Semeshin; Sergey A. Demakov; Victor V. Shloma; Tatyana Yu. Vatolina; Andrey A. Gorchakov; Igor F. Zhimulev (Genetica, 2008)

Study of cholesterol-lowering effect and safety of simvaglisin on rabbit model of hypercholesterolemia - Yu. I. Ragino; V. A. Vavilin; N. F. Salakhutdinov; S. I. Makarova; E. M. Stakhneva; O. G. Safronova; Yu. P. Nikitin; G. A. Tolstikov (Bulletin of Experimental Biology and Medicine, 2008)

Choleretic activity of 2-demethoxycarbonyl-2-ethoxycarbonyl-11-deoxymisoprostol on the model of CCl4-induced hepatitis - T. A. Sapozhnikova; F. S. Zarudii; N. Zh. Baschenko; S. F. Gabdrahmanova; N. S. Makara; R. Yu. Khisamutdinova; N. A. Ivanova; V. S. Nazarov (Bulletin of Experimental Biology and Medicine, 2008)

Molecular cloning and expression analysis of a monosaccharide transporter gene OsMST4 from rice (Oryza sativa L.) - Yongqin Wang; Honglin Xu; Xiaoli Wei; Chenglin Chai; Yuguo Xiao; Yu Zhang; Bin Chen; Guifang Xiao; Pieter B. F. Ouwerkerk; Mei Wang; Zhen Zhu (Plant Molecular Biology, 2007)

The impact of combined ENSO and PDO on the PNA climate: a 1,000-year climate modeling study - B. Yu; F. W. Zwiers (Climate Dynamics, 2007)

Identification and characterization of RNA-dependent RNA polymerase activity in recombinant Japanese encephalitis virus NS5 protein - F. Yu; F. Hasebe; S. Inoue; E. G. M. Mathenge; K. Morita (Archives of Virology, 2007)

Mitochondrial anchoring of PKCα by PICK1 confers resistance to etoposide-induced apoptosis - Wei-Li Wang; Sheau-Farn Yeh; Eagle Yi-Kung Huang; Yu-Ling Lu; Chun-Fa Wang; Chi-Ying F. Huang; Wey-Jinq Lin (Apoptosis, 2007)

Transport of Intranasally Instilled Fine Fe2O3 Particles into the Brain: Micro-distribution, Chemical States, and Histopathological Observation - Bing Wang; Wei Y. Feng; Meng Wang; Jun W. Shi; Fang Zhang; Hong Ouyang; Yu L. Zhao; Zhi F. Chai; Yu Y. Huang; Ya N. Xie; Hai F. Wang; Jing Wang (Biological Trace Element Research, 2007)

Cytogenetic studies on two F1 hybrids of autotetraploid rice varieties showing extremely high level of heterosis - L. Luan; S. B. Tu; W. B. Long; X. Wang; Y. H. Liu; F. L. Kong; T. He; W. G. Yan; M. Q. Yu (Plant Systematics and Evolution, 2007)

Floral traits and isolation of three sympatric Aquilegia species in the Qinling Mountains, China - L.-L. Tang; Q. Yu; J.-F. Sun; S.-Q. Huang (Plant Systematics and Evolution, 2007)

Potentially Reduced Exposure Cigarettes Accelerate Atherosclerosis: Evidence for the Role of Nicotine - Daniel F. Catanzaro; Ying Zhou; Rong Chen; Fangmin Yu; Sarah E. Catanzaro; Mariana S. De Lorenzo; Kotha Subbaramaiah; Xi Kathy Zhou; Domenico Pratico; Andrew J. Dannenberg; Babette B. Weksler (Cardiovascular Toxicology, 2007)

Founder mutations in early-onset, familial and bilateral breast cancer patients from Russia - Anna P. Sokolenko; Maxim E. Rozanov; Natalia V. Mitiushkina; Natalia Yu. Sherina; Aglaya G. Iyevleva; Elena V. Chekmariova; Konstantin G. Buslov; Evgeny S. Shilov; Alexandr V. Togo; Elena M. Bit-Sava; Dmitry A. Voskresenskiy; Oleg L. Chagunava; et al. (Familial Cancer, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Chromosomal location and gene paucity of the male specific region on papaya Y chromosome - Qingyi Yu; Shaobin Hou; Roman Hobza; F. Alex Feltus; Xiue Wang; Weiwei Jin; Rachel L. Skelton; Andrea Blas; Cornelia Lemke; Jimmy H. Saw; Paul H. Moore; Maqsudul Alam; et al. (Molecular Genetics and Genomics, 2007)

Microsatellite markers associated with lint percentage trait in cotton, Gossypium hirsutum - I. Y. Abdurakhmonov; Z. T. Buriev; S. Saha; A. E. Pepper; J. A. Musaev; A. Almatov; S. E. Shermatov; F. N. Kushanov; G. T. Mavlonov; U. K. Reddy; J. Z. Yu; J. N. Jenkins; et al. (Euphytica, 2007)

High incidence of mutations in BRCA1 and BRCA2 genes in ovarian cancer - T. Yu. Smirnova; N. I. Pospekhova; L. N. Lyubchenko; S. A. Tjulandin; R. F. Gar’kavtseva; E. K. Ginter; A. V. Karpukhin (Bulletin of Experimental Biology and Medicine, 2007)

Full-length genome sequence and genetic relationship of two paramyxoviruses isolated from bat and pigs in the Americas - L.-F. Wang; E. Hansson; M. Yu; K. B. Chua; N. Mathe; G. Crameri; B. K. Rima; J. Moreno-López; B. T. Eaton (Archives of Virology, 2007)

Origination of stromal precursor cells replenishing the population of these cells in heterotopic mouse bone marrow transplants after curettage in recipients - Yu. F. Gorskaya; V. G. Nesterenko; E. V. Domracheva; E. A. Aseeva; N. M. Timofeeva (Bulletin of Experimental Biology and Medicine, 2007)

Evaluation of psychoemotional status of rats after brain injury and systemic transplantation of mesenchymal stem cells - A. F. Tsyb; L. M. Roshal; A. G. Konoplyannikov; G. N. Souchkevitch; Yu. G. Verkhovskii; A. S. Shevchuk; L. N. Pavlova; L. P. Zhavoronkov; J. B. Semenova; V. V. Yuzhakov; O. I. Kolganova; G. A. Lushnikova; et al. (Bulletin of Experimental Biology and Medicine, 2007)

Investigation of TXNIP (thioredoxin-interacting protein) and TRX (thioredoxin) genes for growth-related traits in pigs - Mei Yu; Becky Geiger; Nader Deeb; Max F. Rothschild (Mammalian Genome, 2007)

Impact of Pycnogenol® on cardiac extracellular matrix remodeling induced by l-NAME administration to old mice - Sherma Zibadi; Qianli Yu; Peter J. Rohdewald; Douglas F. Larson; Ronald Ross Watson (Cardiovascular Toxicology, 2007)

Effect of glialin on cardiac ventricular arrhythmias and myocardial conduction system in dogs - R. Yu. Khisamutdinova; F. S. Zarudii; S. F. Gabdrakhmanova; N. S. Makara; N. Zh. Baschenko; V. S. Nazarov (Bulletin of Experimental Biology and Medicine, 2007)

Characterization of formation and trace rhythm reproduction by rabbit hippocampal neurons during early and late ontogeny - F. V. Kopytova; Yu. S. Mednikova (Bulletin of Experimental Biology and Medicine, 2007)

Recovery of novel bacterial diversity from mangrove sediment - Jun-Bin Liang; Yue-Qin Chen; Chong-Yu Lan; Nora F. Y. Tam; Qi-Jie Zan; Li-Nan Huang (Marine Biology, 2007)

Oxidative stress in patients with chronic heart failure and type 2 diabetes mellitus - N. E. Arzamastseva; V. Z. Lankin; G. G. Konovalova; A. K. Tikhaze; F. T. Ageev; Yu. V. Lapina; O. Yu. Narusov; V. Yu. Mareev; Yu. N. Belenkov (Bulletin of Experimental Biology and Medicine, 2007)

Mechanisms of recognition of the outlines of “vanishing” optotypes - S. A. Koskin; É. V. Boiko; A. F. Sobolev; Yu. E. Shelepin (Neuroscience and Behavioral Physiology, 2007)

Effect of α-fetoprotein on the count of bone marrow and splenic stromal precursor cells and proliferation of their cultural descendants - Yu. F. Gorskaya; O. V. Lebedinskaya; V. G. Nesterenko; R. Kh. Chailakhyan; Yu. V. Gerasimov; N. V. Latsinik; A. I. Kuralesova; E. N. Genkina (Bulletin of Experimental Biology and Medicine, 2007)

Mechanism of adaptation of the vascular system to chronic changes in nitric oxide level in the organism - M. A. Vlasova; B. V. Smirin; D. A. Pokidyshev; S. Yu. Mashina; A. F. Vanin; I. Yu. Malyshev; E. B. Manukhina (Bulletin of Experimental Biology and Medicine, 2006)

Neuroprotective and antiamnesic effects of Semax during experimental ischemic infarction of the cerebral cortex - G. A. Romanova; D. N. Silachev; F. M. Shakova; Yu. N. Kvashennikova; I. V. Viktorov; S. I. Shram; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2006)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Objective measurement of human visual acuity by visual evoked potentials - A. K. Kharauzov; S. V. Pronin; A. F. Sobolev; S. A. Koskin; É. V. Boiko; Yu. E. Shelepin (Neuroscience and Behavioral Physiology, 2006)

Naloxone-blocked depriming effect of anxiolytic selank on apomorphine-induced behavioral manifestations of hyperfunction of dopamine system - V. K. Meshavkin; N. V. Kost; O. Yu. Sokolov; Yu. A. Zolotarev; N. F. Myasoedov; A. A. Zozulya (Bulletin of Experimental Biology and Medicine, 2006)

Changes in the structure of neuronal connections in the visual cortex of cats with experimentally induced bilateral strabismus - S. N. Toporova; P. Yu. Shkorbatova; S. V. Alekseenko; F. N. Makarov (Neuroscience and Behavioral Physiology, 2006)

Synthesis of highly tritium labeled steroids for evaluation of aromatase and steroidsulfatase activities in endometrial tumors - N. V. Bochkareva; I. V. Kondakova; L. A. Kolomiets; A. B. Muntyan; V. P. Shevchenko; I. Yu. Nagaev; K. V. Shevchenko; N. F. Myasoedov; N. N. Dorofeeva (Bulletin of Experimental Biology and Medicine, 2006)

Gastroprotective properties of 11-deoxymisoprostol (prostaglandin E1 analog) and its effect on the level of sialic acids in gastric tissue of rats with peptic ulcer - N. Zh. Baschenko; T. A. Sapozhnikova; S. F. Gabdrakhmanova; N. S. Makara; R. Yu. Khisamutdinova; F. S. Zarudii; N. A. Ivanova; V. S. Nazarov (Bulletin of Experimental Biology and Medicine, 2006)

Targeted lipidomics: Discovery of new fatty acyl amides - Bo Tan; Heather B. Bradshaw; Neta Rimmerman; Harini Srinivasan; Y. William Yu; Jocelyn F. Krey; M. Francesca Monn; Jay Shih-Chieh Chen; Sherry Shu-Jung Hu; Sarah R. Pickens; J. Michael Walker (The AAPS Journal, 2006)

The formation of a fouling community on artificial substrate in Lake Baikal - L. S. Kravtsova; I. V. Weinberg; I. V. Khanaev; D. Yu. Sherbakov; S. V. Semovsky; F. V. Adov; N. A. Rozhkova; G. V. Pomazkina; N. G. Shevelyova; I. A. Kaygorodova (Hydrobiologia, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Protein tyrosine phosphatase interacting protein 51 (PTPIP51) is a novel mitochondria protein with an N-terminal mitochondrial targeting sequence and induces apoptosis - B. F. Lv; C. F. Yu; Y. Y. Chen; Y. Lu; J. H. Guo; Q. S. Song; D. L. Ma; T. P. Shi; L. Wang (Apoptosis, 2006)

Analysis of MS2Bnap genomic DNA homologous to MS2 gene from Arabidopsis thaliana in two dominant digenic male sterile accessions of oilseed rape (Brassica napus L.) - S. W. Hu; Y. F. Fan; H. X. Zhao; X. L. Guo; C. Y. Yu; G. L. Sun; C. H. Dong; S. Y. Liu; H. Z. Wang (Theoretical and Applied Genetics, 2006)

Selection of Interspecific Hybrids for Anther Culture of Indica Rice - T. He; Y. Yang; S. B. Tu; M. Q. Yu; X. F. Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Adaptation to hypoxia prevents disturbances in cerebral blood flow during neurodegenerative process - S. Yu. Mashina; V. V. Aleksandrin; A. V. Goryacheva; M. A. Vlasova; A. F. Vanin; I. Yu. Malyshev; E. B. Manukhina (Bulletin of Experimental Biology and Medicine, 2006)

Morphofunctional study of the therapeutic effect of autologous mesenchymal stem cells in experimental diffuse brain injury in rats - A. F. Tsyb; L. M. Roshal’; V. V. Yuzhakov; A. G. Konoplyannikov; G. N. Sushkevich; L. N. Bandurko; I. E. Ingel’; Zh. B. Semenova; O. A. Konoplyannikova; L. A. Lepekhina; S. Sh. Kal’sina; Yu. G. Verkhovskii; et al. (Bulletin of Experimental Biology and Medicine, 2006)

Use of autologous bone marrow mesenchymal stem cells for healing of free full-thickness skin graft in a zone with pronounced hypoperfusion of soft tissues caused by arteriovenous shunting - A. V. Bystrov; Yu. A. Polyaev; M. A. Pogodina; M. F. Rasulov; M. E. Krasheninnikov; N. A. Onishchenko (Bulletin of Experimental Biology and Medicine, 2006)

Bacterial siderophores: the solution stoichiometry and coordination of the Fe(III) complexes of pyochelin and related compounds - Chiu-Fou Tseng; Alain Burger; Gaëtan L. A. Mislin; Isabelle J. Schalk; Steve S.-F. Yu; Sunney I. Chan; Mohamed A. Abdallah (JBIC Journal of Biological Inorganic Chemistry, 2006)

Basal induction of cytochrome P-450 1A1/1A2 in cells of the liver, small intestinal villi, and lymph nodes in rats - Yu. I. Borodin; I. V. Maiborodin; A. F. Safina; D. N. Strunkin (Bulletin of Experimental Biology and Medicine, 2006)

Peculiarities of hemoglobin interaction with serum proteins of mice with Ehrlich carcinoma - S. M. Sitdikova; B. S. Amandzholov; M. V. Serebryakova; M. Yu. Zhdanovich; M. V. Kiselevskii; F. V. Donenko (Bulletin of Experimental Biology and Medicine, 2006)

Caspase 3, periodically expressed and activated at G2/M transition, is required for nocodazole-induced mitotic checkpoint - S.-L. Hsu; C. -T. R. Yu; S. -C. Yin; M. -J. Tang; A. -C. Tien; Y. -M. Wu; C. -Y. F. Huang (Apoptosis, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Effect of “profetal” on differentiation and functional activity of human mononuclear leukocytes - O. V. Lebedinskaya; N. P. Velizheva; F. V. Donenko; V. A. Chereshnev; S. Yu. Rodionov; N. K. Akhmatova; I. Zh. Shubina; E. A. Lebedinskaya; M. V. Kiselevskii (Bulletin of Experimental Biology and Medicine, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Effects of semax against the background of dopaminergic receptor blockade with haloperidol - E. A. Sebentsova; N. G. Levitskaya; L. A. Andreeva; L. Yu. Alfeeva; A. A. Kamenskii; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2006)

Characterization of epitopes for neutralizing monoclonal antibodies to classical swine fever virus E2 and Erns using phage-displayed random peptide library - F. Zhang; M. Yu; E. Weiland; C. Morrissy; N. Zhang; H. Westbury; L.-F. Wang (Archives of Virology, 2006)

Use of Microbial Community to Evaluate Performance of a Wetland System in Treating Pb/Zn Mine Drainage - Yu H. YU; Wei S. Feng; Yun F. Shen; Zhi H. Ye; Ming H. Wong (Environmental Management, 2005)

Comparative study of macrophage response in mice after DNA immunization and infection with herpes simplex virus type 1 - E. V. Nagurskaya; L. G. Zaitseva; N. V. Kobets; I. V. Kireeva; V. A. Bekhalo; A. Yu. Kozlov; R. R. Klimova; S. V. Gur’yanova; T. M. Andronova; L. N. Shingarova; E. F. Boldyreva; O. V. Nekrasova (Bulletin of Experimental Biology and Medicine, 2005)

Specific and nonspecific reactions of mouse immune system under the effect of short-term exposure in warm and/or cold water - L. F. Kalenova; Yu. G. Sukhovei; T. A. Fisher (Bulletin of Experimental Biology and Medicine, 2005)

The Possibility of Cytochrome P450 1A1/1A2 Induction in Cells of Distant Lymph Nodes of Rats after Enteral Treatment with Benzo[a]pyrene - Yu. I. Borodin; I. V. Maiborodin; A. F. Safina; D. N. Strunkin (Bulletin of Experimental Biology and Medicine, 2005)

Role of Purinoceptors in Cardiac Function in Rats during Ontogeny - T. A. Anikina; F. G. Sitdikov; E. Yu. Khamzina; G. A. Bilalova (Bulletin of Experimental Biology and Medicine, 2005)

Dissolved Neutral Nonylphenol Ethoxylates Metabolites in the Haihe River and Bohai Bay, People's Republic of China - G. Shen; Z. Zhang; G. Yu; X. Li; H. Hu; F. Li (Bulletin of Environmental Contamination and Toxicology, 2005)

A population of red‐transparent, triploid Carassius auratus - Y. J. Hong; Z. J. Yu; L. Zhou; J. F. Gui (Journal of Fish Biology, 2005)
A red‐transparent population, distributed in Pingxiang of Jiangxi Province, was identified to be triploid Carassius auratus by DNA content measurement and chromosome analysis. Artificial propagation experiments indicated that the red‐transparent triploid Carassius auratus could reproduce by gynogenesis.

Studies of the Synaptic Plasticity of Field CA3 of the Hippocampus During Tetanization of the Perforant Path - V. F. Safiulina; A. M. Kas’yanov; V. A. Markevich; O. G. Bogdanova; A. Yu. Dvorzhak; V. A. Zosimovskii; V. L. Ezrokhi (Neuroscience and Behavioral Physiology, 2005)

Osteogenic Potential of Mesenchymal Stem Cells from Bone Marrow in Situ: Role of Physicochemical Properties of Artificial Surfaces - I. A. Khlusov; A. V. Karlov; Yu. P. Sharkeev; V. F. Pichugin; Yu. P. Kolobov; G. A. Shashkina; M. B. Ivanov; E. V. Legostaeva; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2005)

Use of Recombinant AdSV40-βGal Adenoviral Construction for Monitoring of Transplanted Cells - M. S. Dolgikh; A. Yu. Grigor'eva; A. O. Zhigulin; V. A. Zaidenov; M. F. Rasulov; I. V. Potapov; M. E. Krasheninnikov; N. A. Onishchenko (Bulletin of Experimental Biology and Medicine, 2005)

Counts of Stromal Precursor Cells in Heterotopic Bone Marrow Transplants in Mice Immunized with Group A Streptococcus Antigens - Yu. F. Gorskaya; T. A. Danilova; O. V. Lebedinskaya; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2005)

Oxidative Stress in Atherosclerosis and Diabetes - V. Z. Lankin; M. O. Lisina; N. E. Arzamastseva; G. G. Konovalova; L. V. Nedosugova; A. I. Kaminnyi; A. K. Tikhaze; F. T. Ageev; V. V. Kukharchuk; Yu. N. Belenkov (Bulletin of Experimental Biology and Medicine, 2005)

Survival and phenotypic characteristics of axotomized neurons in spinal ganglia - Yu. A. Chelyshev; I. S. Raginov; D. S. Guseva; R. F. Masgutov (Neuroscience and Behavioral Physiology, 2005)

Electronic atlas of the Russian Arctic coastal zone - D. S. Drozdov; F. M. Rivkin; V. Rachold; G. V. Ananjeva-Malkova; N. V. Ivanova; I. V. Chehina; M. M. Koreisha; Yu. V. Korostelev; E. S. Melnikov (Geo-Marine Letters, 2005)

Morphogenetic classification of the Arctic coastal zone - S. L. Nikiforov; Yu A. Pavlidis; V. Rachold; M. N. Grigoryev; F. M. Rivkin; N. V. Ivanova; M. M. Koreisha (Geo-Marine Letters, 2005)

Changes in the pattern of metabolic activity of striate cortex neurons in cats reared in conditions of flashing illumination - N. S. Merkul’eva; F. N. Makarov; E. I. Krasnoshchekova; Yu. E. Shelepin (Neuroscience and Behavioral Physiology, 2005)

Therapeutic effects of dengue 2 virus capsid protein and staphylococcal nuclease fusion protein on dengue-infected cell cultures - C.-F. Qin; E. Qin; M. Yu; S.-P. Chen; T. Jiang; Y.-Q. Deng; H.-Y. Duan; H. Zhao (Archives of Virology, 2005)

Platelet-Derived Growth Factor Requirement for Cultured Descendants of Rabbit Stromal Bone Marrow Precursors - Yu. F. Gorskaya; V. G. Nesterenko; O. V. Lebedinskaya (Bulletin of Experimental Biology and Medicine, 2005)

Relationship between Antitumor Efficiency of Photodynamic Therapy with Photoditasine and Photoenergy Density - Yu. S. Romanko; A. F. Tsyb; M. A. Kaplan; V.V. Popuchiev (Bulletin of Experimental Biology and Medicine, 2005)

Identification of two novel genes for blackleg resistance in Brassica napus - F. Yu; D. J. Lydiate; S. R. Rimmer (Theoretical and Applied Genetics, 2005)

Soft perforation of planar bilayer lipid membranes of dipalmitoylphosphatidylcholine at the temperature of the phase transition from the liquid crystalline to the gel state - Valerij F. Antonov; Andrej A. Anosov; Vladimir P. Norik; Elena Yu. Smirnova (European Biophysics Journal, 2005)

Effects of Acid Precipitation and Aluminum on Carbohydrate Metabolism in Mycorrhizae of Pinus massioniana - J. K. Tan; F. X. Kong; H. S. Cao; Y. Yu; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2005)

Counts of Stromal Precursor Cells in Heterotopic Splenic Transplants in CBA Mice of Different Age - Yu. F. Gorskaya; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2005)

Effect of photodynamic therapy with photodithazine on morphofunctional parameters of M-1 sarcoma - Yu. S. Romanko; A. F. Tsyb; M. A. Kaplan; V. V. Popuchiev (Bulletin of Experimental Biology and Medicine, 2004)

Age-Related Structural and Functional Characteristics of Rabbit Hippocampal Neurons During the Formation of Temporal Associations - F. V. Kopytova; Yu. S. Mednikova; É. N. Popova (Neuroscience and Behavioral Physiology, 2004)

Expression of estrogen receptors-α and -β in primary breast neoplasms and tumors exposed to neoadjuvant hormonal therapy - L. M. Bershtein; T. E. Poroshina; T. S. Zimarina; E. V. Tsyrlina; E. K. Zhil’tsova; A. Yu. Kovalevskii; V. F. Semiglazov (Bulletin of Experimental Biology and Medicine, 2004)

Prediction of the Ability of PAHs to be Photocytotoxic to a Cell Line from the Rainbow Trout (Oncorhynchus mykiss) Gill - J. F. Niu; G. Yu (Bulletin of Environmental Contamination and Toxicology, 2004)

Effects of Temperature on the Spike Activity of Cortical Neurons in Guinea Pigs - Yu. S. Mednikova; N. V. Pasikova; F. V. Kopytova (Neuroscience and Behavioral Physiology, 2004)

Genotyping Possible Polymorphic Variants of Human Mismatch Repair Genes in Healthy Korean Individuals and Sporadic Colorectal Cancer Patients - Jin C. Kim; Seon A. Roh; Kum H. Koo; In H. Ka; Hee C. Kim; Chang S. Yu; Kang H. Lee; Jung S. Kim; Han I. Lee; Walter F. Bodmer (Familial Cancer, 2004)

Wound-Healing Effect of Papaya-Based Preparation in Experimental Thermal Trauma - E. V. Mikhalchik; A. V. Ivanova; M. V. Anurov; S. M. Titkova; L. Yu. Penkov; Z. F. Kharaeva; L. G. Korkina (Bulletin of Experimental Biology and Medicine, 2004)

Identification and molecular characterization of a novel y-type Glu-D t 1 glutenin gene of Aegilops tauschii - Y. Yan; J. Zheng; Y. Xiao; J. Yu; Y. Hu; M. Cai; Y. Li; S. L. K. Hsam; F. J. Zeller (Theoretical and Applied Genetics, 2004)

The Neuroprotective Effects of Semax in Conditions of MPTP-Induced Lesions of the Brain Dopaminergic System - N. G. Levitskaya; E. A. Sebentsova; L. A. Andreeva; L. Yu. Alfeeva; A. A. Kamenskii; N. F. Myasoedov (Neuroscience and Behavioral Physiology, 2004)

Invasive Characteristics of Apathogenic Shigella flexneri 5a2c Mutant Obtained under the Effect of Furazolidone - T. N. Efremova; I. G. Gruzdeva; I. V. Matveev; E. S. Bozhokina; Ya. Yu. Komissarchuk; Z. F. Fedorova; S. Yu. Khaitlina (Bulletin of Experimental Biology and Medicine, 2004)

Concentration Level of Fine Airborne Lead in Beijing, People?s Republic of China - K. B. He; F. K. Duan; Y. L. Ma; F. M. Yang; Q. Zhang; X. C. Yu; S. Cadle; T. Chan; Y. Yan; P. Mulawa (Bulletin of Environmental Contamination and Toxicology, 2004)

Relationship between Changes in Rat Behavior and Integral Biochemical Indexes Determined by Laser Correlation Spectroscopy after Photothrombosis of the Prefrontal Cortex - G. A. Romanova; F. M. Shakova; O. I. Kovaleva; V. V. Pivovarov; N. N. Khlebnikova; M. Yu. Karganov (Bulletin of Experimental Biology and Medicine, 2004)

Interaction of Sensory Neurons and Satellite Cells during Stimulation of Nerve Regeneration - I. S. Raginov; Yu. A. Chelyshev; T. F. Shagidullin (Neuroscience and Behavioral Physiology, 2004)

QTL × environment interactions in rice. I. Heading date and plant height - Z. K. Li; S. B. Yu; H. R. Lafitte; N. Huang; B. Courtois; S. Hittalmani; C. H. M. Vijayakumar; G. F. Liu; G. C. Wang; H. E. Shashidhar; J. Y. Zhuang; K. L. Zheng; et al. (Theoretical and Applied Genetics, 2003)

Genotypic Differences in Effect of Cd on Photosynthesis and Chlorophyll Fluorescence of Barley (Hordeum vulgare L) - F. B. Wu; G. P. Zhang; J. S. Yu (Bulletin of Environmental Contamination and Toxicology, 2003)

Benzo[a]pyrene Induction of Cytochrome P450 1A1/1A2 in the Lymph Nodes of Rats - Yu. I. Borodin; A. F. Safina; I. V. Maiborodin; A. Yu. Grishanova (Bulletin of Experimental Biology and Medicine, 2003)

HMW and LMW glutenin alleles among putative tetraploid and hexaploid European spelt wheat (Triticum spelta L.) progenitors - Y. Yan; S. L. K. Hsam; J. Z. Yu; Y. Jiang; I. Ohtsuka; F. J. Zeller (Theoretical and Applied Genetics, 2003)

Brain Blood Flow Modulates the Neurotoxic Action of Hyperbaric Oxygen via Neuronal and Endothelial Nitric Oxide - A. N. Moskvin; S. Yu. Zhilyaev; O. I. Sharapov; T. F. Platonova; D. R. Gutsaeva; V. B. Kostkin; I. T. Demchenko (Neuroscience and Behavioral Physiology, 2003)

Expression of Estrogen Receptors-β and Aromatase Activity in Primary Mammary Gland Tumors - L. M. Bershtein; T. S. Zimarina; T. E. Poroshina; A. Yu. Kovalevskii; E. V. Tsyrlina; E. K. Zhil'tsova; V. F. Semiglazov (Bulletin of Experimental Biology and Medicine, 2003)

Sensitization of Cells Overexpressing Multidrug-Resistant Proteins by Pluronic P85 - Elena V. Batrakova; Shu Li; Valery Yu. Alakhov; William F. Elmquist; Donald W. Miller; Alexander V. Kabanov (Pharmaceutical Research, 2003)

Hyperoxic Vasoconstriction in the Brain Is Mediated by Inactivation of Nitric Oxide by Superoxide Anions - S. Yu. Zhilyaev; A. N. Moskvin; T. F. Platonova; D. R. Gutsaeva; I. V. Churilina; I. T. Demchenko (Neuroscience and Behavioral Physiology, 2003)

Molecular cytogenetic detection of paternal chromosome fragments in allogynogenetic gibel carp, Carassius auratus gibelio Bloch - M. S. Yi; Y. Q. Li; J. D. Liu; L. Zhou; Q. X. Yu; J. F. Gui (Chromosome Research, 2003)

Detection and Description of Various Stores of Nitric Oxide Store in Vascular Wall - M. A. Vlasova; A. F. Vanin; B. Muller; B. V. Smirin; I. Yu. Malyshev; E. B. Manukhina (Bulletin of Experimental Biology and Medicine, 2003)

Detection and Evaluation of NO Stores in Awake Rats - S. Yu. Mashina; A. F. Vanin; V. A. Serezhenkov; L. N. Kubrina; I. V. Malenkova; I. Yu. Malyshev; E. B. Manukhina (Bulletin of Experimental Biology and Medicine, 2003)

Tumor-Specific Changes in Mouse Serum during Ehrlich Carcinoma Growth - S. M. Sitdikova; B. S. Amandzholov; V. Yu. Sel'chuk; F. V. Donenko (Bulletin of Experimental Biology and Medicine, 2003)

Activating Influence of Nitric Oxide on Ca2+-Activated K+ Channels in Smooth Muscle Cells of the Main Pulmonary Artery - V. S. Telezhkin; Yu. B. Diskina; M. F. Shuba (Neurophysiology, 2003)

Contribution of Different Adrenoreceptor Types to the Relaxing Action of Noradrenaline on Circular Intestinal Smooth Muscles - Yu. B. Diskina; V. S. Telezhkin; M. F. Shuba (Neurophysiology, 2003)

New Approach to Vital Analysis of Functional Activity in ABC Transporters (Markers for Multidrug Resistance) in Solid Tumors by the Method of Flow Cytofluorometry - T. A. Bogush; T. N. Zabotina; E. A. Bogush; E. F. Chmutin; D. V. Komov; Z. G. Kadagidze; A. Yu. Baryshnikov (Bulletin of Experimental Biology and Medicine, 2003)

Scientific Considerations of Pharmaceutical Solid Polymorphism in Abbreviated New Drug Applications - Lawrence X. Yu; M. Scott Furness; Andre Raw; Kathy P. Woodland Outlaw; Nashed E. Nashed; Edwin Ramos; Stephen P. F. Miller; Richard C. Adams; Florence Fang; Rashmikant M. Patel; Frank O. Holcombe; Yuan-yuan Chiu; et al. (Pharmaceutical Research, 2003)

Impact of Fipronil on Crustacean Aquatic Organisms in a Paddy Field-Fishpond Ecosystem - Z. Shan; L. Wang; D. Cai; R. Gong; Z. Zhu; F. Yu (Bulletin of Environmental Contamination and Toxicology, 2003)

Metabolism of PGP Peptide after Administration via Different Routes - Yu. A. Zolotarev; S. E. Zhuikova; I. P. Ashmarin; N. F. Myasoedov; B. V. Vas'kovskii; G. E. Samonina (Bulletin of Experimental Biology and Medicine, 2003)

Satellite antenna phase center offsets and scale errors in GPS solutions - S. Y. Zhu; F.-H. Massmann; Y. Yu; Ch. Reigber (Journal of Geodesy, 2003)

Location and Intensity of IL-8 and TGF-β2 mRNA Production in the Fimbrial Compartment of Fallopian Tubes and IL-10 in the Endometrium in Patients with Pyoinflammatory Adnexal Diseases - A. V. Zhdanov; D. F. Kurbanova; L. Yu. Sosulina; M. P. Davydova; L. S. Ezhova; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2003)

Effect of Semax Peptide on Survival of Cultured Rat Pheochromocytoma Cells during Oxidative Stress - E. R. Safarova; S. I. Shram; Yu. A. Zolotarev; N. F. Myasoedov (Bulletin of Experimental Biology and Medicine, 2003)

Apoptosis in Fimbriae of Fallopian Tubes and Endometrium in Pyoinflammatory Adnexal Diseases - A. V. Zhdanov; D. F. Kurbanova; M. P. Davydova; L. Yu. Sosulina; L. S. Ezhova; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2003)

Antiapoptotic Effect of Heat Adaptation in Cultured Cells - E. A. Monastyrskaya; M. R. Duchen; L. V. Andreeva; F. Viegant; E. B. Manukhina; I. Yu. Malyshev (Bulletin of Experimental Biology and Medicine, 2003)

Local Expression of Cytokine Genes in Uterine Adnexa and Endometrium of Women with Pyoinflammatory Adnexal Diseases - A. V. Zhdanov; M. P. Davydova; D. F. Kurbanova; L. Yu. Sosulina; T. G. Gabuniya; L. V. Van'ko; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2003)

The State of the Immune System in Thyroidectomized Rats - G. D. Bendyug; Yu. A. Grinevich; N. N. Khranovskaya; F. V. Fil'chakov; L. G. Yugrinova; A. G. Kad'kalenko (Bulletin of Experimental Biology and Medicine, 2003)

A framework for integrating the songbird brain - Jarvis E.; Smith V.; Wada K.; Rivas M.; McElroy M.; Smulders T.; Carninci P.; Hayashizaki Y.; Dietrich F.; Wu X.; McConnell P.; Yu J.; et al. (Journal of Comparative Physiology A, 2002)

Expression of Cytokine Genes in Blood Mononuclear Cells in Women with Pyoinflammatory Diseases of Adnexa Uteri - A. V. Zhdanov; L. Yu. Sosulina; D. F. Kurbanova; L. V. Van'ko; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2002)

Effects of Acute and Chronic Caffeine Intake on Intravenous Self-Administration of Morphine in Two Rat Strains - S. K. Sudakov; I. P. Papazov; Yu. V. Lyupina; O. F. Medvedeva; I. V. Figurina; I. V. Rusakova (Bulletin of Experimental Biology and Medicine, 2002)

Allelic and locus heterogeneity in autosomal recessive gelatinous drop-like corneal dystrophy - Zhaoxia Ren; Pei-Yu Lin; Gordon K. Klintworth; Fumino Iwata; Francis L. Munier; Daniel F. Schorderet; Leila El Matri; Veena Theendakara; Surendra Basti; Madhukar Reddy; Fielding J. Hejtmancik (Human Genetics, 2002)

Are puffer fish more toxic in their spawning seasons? - Yu C.-F.; Yu P. (Marine Biology, 2002)

Identification of quantitative trait loci and epistatic interactions for plant height and heading date in rice - S. B. Yu; J. X. Li; C. G. Xu; Y. F. Tan; X. H. Li; Qifa Zhang (Theoretical and Applied Genetics, 2002)

Effect of Platelet Growth Factors on Proliferation of Guinea Pig Bone Marrow and Splenic Stromal Precursor Cells and Proliferation of Cultural Descendants from Bone Marrow Precursor Cells - Yu. F. Gorskaya; E. Yu. Shuklina; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2002)

Role of Lipoproteins Transporting Lipophilic Xenobiotics in the Induction of Microsomal Monooxygenases - L. E. Panin; M. Yu. Pakharukova; L. F. Gulyaeva (Bulletin of Experimental Biology and Medicine, 2002)

Age-Related Changes in Inducible Osteogenic Precursors - Yu. F. Gorskaya; E. Yu. Shuklina; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2002)

Content of Stromal Precursor Cells in Heterotopic Transplants of Bone Marrow in CBA Mice of Various Ages - Yu. F. Gorskaya; A. I. Kuralesova; E. Yu. Shuklina; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 2002)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

Effects of Antibiotics on Reactive Oxygen Species Generation by Neutrophils - N. F. Abdrashitova; Yu. A. Romanov (Bulletin of Experimental Biology and Medicine, 2001)

The Use of Naloxone in Small Doses in Complex Therapy of Postabstinent Heroin Syndrome: Enkephalinase Mechanisms - S. V. Litvinova; A. V. Nadezhdin; V. V. Shul'govskii; A. L. Kalyuzhnyi; S. N. Avdeev; E. Yu. Tetenova; N. N. Terebilina; L. F. Panchenko (Bulletin of Experimental Biology and Medicine, 2001)

Effects of K+ Channel Blockers and Nitric Oxide on the Electrical and Contractile Activities of Smooth Muscles of the Rabbit Main Pulmonary Artery - V. S. Telezhkin; V. V. Tsvilovskii; Yu. B. Dyskina; N. V. Davydovskaya; M. F. Shuba (Neurophysiology, 2001)

Lipid Peroxidation-Antioxidant Activity System in Erythrocytes of Patients with Chronic Bronchitis Inhaling and Not Inhaling Ozone - N. F. Abdrashitova; Yu. A. Romanov (Bulletin of Experimental Biology and Medicine, 2001)

Functional Insufficiency of the System Responsible for Reactive Oxygen Species Generation by Blood Neutrophils - N. F. Abdrashitova; Yu. A. Romanov (Bulletin of Experimental Biology and Medicine, 2001)

Natural environmental associations in a 50-day human electrocardiogram - A. Delyukov; Yu. Gorgo; G. Cornélissen; K. Otsuka; F. Halberg (International Journal of Biometeorology, 2001)

Minimally Invasive Estimation of Systemic Vascular Parameters - Yih-Choung Yu; J. Robert Boston; Marwan A. Simaan; James F. Antaki (Annals of Biomedical Engineering, 2001)

Construction of a bacterial artificial chromosome (BAC) library for citrus and identification of BAC contigs containing resistance gene candidates - Z. Deng; Q. Tao; Y.-L. Chang; S. Huang; P. Ling; C. Yu; C. Chen; F. G. Gmitter; H.-B. Zhang (Theoretical and Applied Genetics, 2001)

Structural and vibrational behaviour of fluorapatite with pressure. Part I: in situ single-crystal X-ray diffraction investigation - P. Comodi; Yu Liu; P. F. Zanazzi; M. Montagnoli (Physics and Chemistry of Minerals, 2001)

Spike Responses of Neurons in the Motor Area of the Cortex of Elderly Rabbits to Specific Stimuli - Yu. S. Mednikova; F. V. Kopytova; T. N. Dish (Neuroscience and Behavioral Physiology, 2001)

Effect of Enterosorbent Noolith on Behavior and Serotonin (1A) Receptors in Mouse Brain - Yu. I. Borodin; D. F. Avgustinovich; M. V. Tenditnik; L. N. Rachkovskaya; A. V. Shurlygina; V. A. Trufakin (Bulletin of Experimental Biology and Medicine, 2001)

The Inhibitory Effect of Selank on Enkephalin-Degrading Enzymes as a Possible Mechanism of Its Anxiolytic Activity - A. A. Zozulya; N. V. Kost; O. Yu. Sokolov; M. V. Gabaeva; I. A. Grivennikov; L. N. Andreeva; Yu. A. Zolotarev; S. V. Ivanov; A. V. Andryushchenko; N. F. Myasoedov; A. B. Smulevich (Bulletin of Experimental Biology and Medicine, 2001)

Microtubule dynamics are involved in stomatal movement ofVicia faba L. - R. Yu; R.-F. Huang; X.-C. Wang; M. Yuan (Protoplasma, 2001)

Effect of Xymedon on Cell Survival in the System Sensory Neuron Schwann Cell - I. S. Raginov; Yu. A. Chelyshev; T. F. Shagidullin (Bulletin of Experimental Biology and Medicine, 2001)

Role of Nitric Oxide and Lipid Peroxidation in Mechanisms of Febrile Convulsions in Wistar Rat Pups - Yu. A. Klyueva; V. G. Bashkatova; G. Yu. Vitskova; V. B. Narkevich; V. D. Mikoyan; A. F. Vanin; S. A. Chepurnov; N. E. Chepurnova (Bulletin of Experimental Biology and Medicine, 2001)

Genetic bases of appearance quality of rice grains in Shanyou 63, an elite rice hybrid - Y. F. Tan; Y. Z. Xing; J. X. Li; S. B. Yu; C. G. Xu; Qifa Zhang (Theoretical and Applied Genetics, 2000)

Clinical Manifestations and Molecular Epidemiology of Late Recurrent Candidemia, and Implications for Management - C. J. Clancy; F. Barchiesi; L. Falconi DiFrancesco; A. J. Morris; D. R. Snydman; V. L. Yu; G. Scalise; M. H. Nguyen (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

The use of antioxidants to prevent glutamate-induced derangement of calcium ion metabolism in rat cerebral cortex synaptosomes - N. F. Avrova; K. I. Shestak; I. O. Zakharova; T. V. Sokolova; Yu. Yu. Tyurina; V. A. Tyurin (Neuroscience and Behavioral Physiology, 2000)

Residuary Toxic Elements And PAHs in Sediments of the Zbiornik Gilow Tailings Pond and Zimmica Stream from Lubin District, Southwest Poland - Yu-Zhuang Sun; A. Leischner; F.-J. Göbbels (Environmental Geochemistry and Health, 2000)

Effect of long-term exposure to ozone on functional activity of human phagocytes - N. F. Abdrashitova; Yu. V. Balyakin; Yu. A. Romanov (Bulletin of Experimental Biology and Medicine, 2000)

Analyzing quantitative trait loci for yield using a vegetatively replicated F2 population from a cross between the parents of an elite rice hybrid - J. X. Li; S. B. Yu; C. G. Xu; Y. F. Tan; Y. J. Gao; X. H. Li; Qifa Zhang (Theoretical and Applied Genetics, 2000)

Pollen‐based biomes for Beringia 18,000, 6000 and 0 14 C yr bp † - M. E. Edwards; P. M. Anderson; L. B. Brubaker; T. A. Ager; A. A. Andreev; N. H. Bigelow; L. C. Cwynar; W. R. Eisner; S. P. Harrison; F.‐S. Hu; D. Jolly; A. V. Lozhkin; et al. (Journal of Biogeography, 2000)
The objective biomization method developed by Prentice et al . (1996) for Europe was extended using modern pollen samples from Beringia and then applied to fossil pollen data to reconstruct palaeovegetation patterns at 6000 and 18,000 14 C yr bp . The predicted modern distribution of tundra, taiga and cool conifer forests in Alaska and north‐western Canada generally corresponds well to actual vegetation patterns, although sites in regions characterized today by a mosaic of forest and tundra vegetation tend to be preferentially assigned to tundra. Siberian larch forests are delimited less well, probably due to the extreme under‐representation of Larix in pollen spectra. The biome distribution across Beringia at 6000 14 C yr bp was broadly similar to today, with little change in the northern forest limit, except for a possible northward advance in the Mackenzie delta region. The western forest limit in Alaska was probably east of its modern position. At 18,000 14 C yr bp the whole of Beringia was covered by tundra. However, the importance of the various plant functional types varied from site to site, supporting the idea that the vegetation cover was a mosaic of different tundra types.

Immunotoxicological characteristics of preparations based on carcinoembryonic antigen and mucin containing CA 125 antigen - S. M. Sitdikova; B. S. Amandzholov; V. Yu. Sel'chuk; N. G. Kormosh; K. P. Laktionov; Yu. S. Lebedin; S. V. Chukanov; A. Yu. Toptygin; L. V. Manzyuk; F. V. Donenko (Bulletin of Experimental Biology and Medicine, 2000)

Antitumor activity of specific immunotherapy with mucin containing CA 125 antigen in mice with CaO 1 ovarian carcinoma - B. S. Amandzholov; S. M. Sitdikova; Yu. S. Lebedin; S. V. Chukanov; A. Yu. Toptygin; L. V. Manzyuk; F. V. Donenko (Bulletin of Experimental Biology and Medicine, 2000)

Improvement of edge effect of the wavelet time-frequency spectrum: application to the length-of-day series - D. Zheng; B. F. Chao; Y. Zhou; N. Yu (Journal of Geodesy, 2000)

Cesium-137 in the environment of the Altay Region (Russia) - F. V. Sukhorukov; V. M. Gavshin; I. N. Malikova; S. I. Kovalev; Yu. I. Malikov; P. A. Romashkin (Water, Air, & Soil Pollution, 2000)

Glutathione S-transferase activity in the liver of mice with different sensitivity to hepatocarcinogenic effects ofo-aminoazotoluene - L. Yu. Zakharova; L. F. Gulyaeva; O. V. Narkhova; V. I. Kaledin (Bulletin of Experimental Biology and Medicine, 2000)

Carbon and nitrogen isotopic composition of the fauna from the Broken Spur hydrothermal vent field - A. L. Vereshchaka; G. M. Vinogradov; A. Yu. Lein; S. Dalton; F. Dehairs (Marine Biology, 2000)

Seven forms of rarity in mammals - Jinping Yu; F. Stephen Dobson (Journal of Biogeography, 2000)
Conservation biologists have identified threats to the survival of about a quarter of the mammalian species; to identify patterns of rarity and commonness of mammals, we studied a global sample of 1212 species (about 28% of the mammals) using the ‘7 forms of rarity’ model (in which species are roughly divided into above and below the median for local population density, species’ range area, and number of habitat types). From a niche‐based hypothesis of abundance and distribution, we predicted that mammals would exhibit a bimodal pattern of rarity and commonness, with an overabundance of species in the relatively rarest and most common categories; and just such a significant bimodal pattern emerged, with over a quarter of the species classified as exceedingly rare and a further quarter very common, supporting the niche‐based hypothesis. Orders that include large mammals, including perissodactyls, primates, diprotodonts, and carnivores, exhibited significantly high proportions of relatively rare species; and tropical zoogeographic regions, especially Indomalaya, had relatively high proportions of species in the rarest category. Significant biases in the available data on mammals included under‐sampling of small species like rodents and bats, and a relative paucity of data on zoogeographic regions outside of North America and Australia. Mammalian species listed as of conservation concern by the IUCN occurred in all cells of the model, indicating that even relatively common species can be listed as threatened under some conditions; but we also found that sixty‐three species were relatively rare in all three criteria of the 7‐forms model but were not listed as threatened, indicating potential candidates for further study. Mammals may be a group of animals where rarity or commonness is a natural aspect of species biology, both confirming and perhaps partly explaining the large proportion of mammals assigned threatened status.

Investigation of some impurity profiles by (n,α) reactions - M. Kadirova; Yu. F. Simakhin; N. Jumaev; M. M. Usmanova (Biological Trace Element Research, 1999)

Thermal adaptation activates HSP70 synthesis, inhibits overproduction of nitric oxide, and protects the body from acute hypotension during heat shock - A. I. Trifonov; N. P. Larionov; E. B. Manukhina; V. D. Mikoyan; L. N. Kubrina; A. F. Vanin; I. Yu. Malyshev (Bulletin of Experimental Biology and Medicine, 1999)

Dynamics of immune response to porine fromYersinia pseudotuberculosis outer membrane - O. Yu. Portnyagina; O. D. Novikova; O. P. Vostrikova; T. F. Solov'eva (Bulletin of Experimental Biology and Medicine, 1999)

Enhanced expression of sarcoplasmic reticulum Ca2+-ATPase gene plays a role in protective effects of nitric oxide - N. P. Aimasheva; E. B. Malenyuk; E. B. Manukhina; G. L. Khaspekov; V. D. Mikoyan; L. N. Kubrina; A. F. Vanin; I. Yu. Malyshev (Bulletin of Experimental Biology and Medicine, 1999)

PBXL Fluorescent Dyes for Ultrasensitive Direct Detection - Steven J. Zoha; Shakuntala Ramnarain; John P. Morseman; Mark W. Moss; F. C. Thomas Allnutt; Yu-Hui Rogers; Bronwen Harvey (Journal of Fluorescence, 1999)

Specific features of digital X-ray diagnostic electrooptical systems - N. N. Blinov; E. B. Kozlovskii; S. I. Luzin; A. Yu. Pervov; A. F. Sonin; I. G. Plutov; V. I. Rodin (Biomedical Engineering, 1999)

The three important traits for cooking and eating quality of rice grains are controlled by a single locus in an elite rice hybrid, Shanyou 63 - Y. F. Tan; J. X. Li; S. B. Yu; Y. Z. Xing; C. G. Xu; Qifa Zhang (Theoretical and Applied Genetics, 1999)

Pre- and postsynaptic mechanisms of the involvement of amygdaloid complex serotonin in the reproduction of a conditioned passive avoidance response in rats - G. F. Molodtsova; R. Yu. Il'yuchenok (Neuroscience and Behavioral Physiology, 1999)

Vitamin status and spermatogenesis in rats during late stages after irradiation in various doses - V. V. Evdokimov; V. M. Kodentsova; L. F. Kurilo; L. V. Shileiko; T. V. Ostroumova; O. L. Vrzhesinskaya; L. M. Yakushina; V. I. Erasova; V. I. Kirpatovskii; I. Yu. Nefedov; I. Yu. Sakharov (Bulletin of Experimental Biology and Medicine, 1999)

Analysis of granulomonocytic precursor cells from fetal liver used for maintenance therapy in children with Gaucher's disease - I. V. Dubrovina; E. A. Kopyl'tsova; L. A. Cheredeeva; V. F. Kudryashova; Yu. A. Blidchenko; N. A. Torubarova; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 1999)

Cadmium-Inducible Metallothionein in Tilapia ( Oreochromis mossambicus ) - S. M. Wu *, , C. F. Weng; M. J. Yu; C. C. Lin; S. T. Chen; J. C. Hwang; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1999)

In Vivo Accumulation of nitric oxide in blood vessels - B. V. Smirin; A. F. Vanin; I. Yu. Malyshev; D. A. Pokidyshev; E. B. Manukhina (Bulletin of Experimental Biology and Medicine, 1999)

Evaluation of growth parameters inParamecium caudatum test model for standardization of biological screening - Yu. A. Ershov; T. V. Pletneva; T. F. Sinyuk; V. A. Dolgopolova (Bulletin of Experimental Biology and Medicine, 1999)

Effects of interleukin-1β and indomethacin on expression of interleukin-1β gene in brain hemispheres - A. Yu. Grebenshchikov; A. F. Poveshchenko; V. V. Abramov; V. A. Kozlov (Bulletin of Experimental Biology and Medicine, 1999)

Age-related changes in the content of stromal clonogenic cells in hemopoietic and lymphoid organs - A. Ya. Fridenshtein; Yu. F. Gorskaya; N. V. Latsinik; E. Yu. Shuklina; V. G. Nesterenko (Bulletin of Experimental Biology and Medicine, 1999)

Digital processing of images in physiological studies - K. N. Dudkin; F. N. Makarov; V. B. Makulov; S. V. Mironov; V. N. Chikhman; Yu. E. Shelepin (Neuroscience and Behavioral Physiology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Soluble fas antigen in serum of cancer patients - S. G. Abbasova; N. E. Kushlinskii; A. N. Murashev; I. A. Kostanyan; M. N. Obusheva; S. O. Nikogosyan; T. A. Britvin; N. F. Bagirova; Yu. N. Solov'ev; V. M. Lipkin; N. N. Trapeznikov (Bulletin of Experimental Biology and Medicine, 1999)

Interactions between natural autoantibodies to tumor-associated human ovarian cancer antigen and murine ovarian cancer cells CaO-1 - B. S. Amandzholov; Yu. S. Lebedin; S. V. Chukanov; A. Yu. Toptygin; S. M. Sitdikova; L. L. Moroz; L. V. Manyuk; F. V. Donenko (Bulletin of Experimental Biology and Medicine, 1999)

Prevention of experimental pseudotuberculosis infection by immunization with porin fromYersinia pseudotuberculosis - I. V. Darmov; I. V. Marakulin; I. P. Pogorel'skii; O. D. Novikova; O. Yu. Portnyagina; T. F. Solov'eva (Bulletin of Experimental Biology and Medicine, 1999)

Effects of bone marrow conditioned media on proliferation of stromal clonogenic cellsin vitro - A. Ya. Fridenshtein; Yu. F. Gorskaya; N. V. Latsinik; E. Yu. Shuklina; L. A. Fonina; S. A. Gur'yanov (Bulletin of Experimental Biology and Medicine, 1999)

Genetic structure of a scleractinian coral, Mycedium elephantotus , in Taiwan - J.-K. Yu; H.-Y. Wang; S.-C. Lee; C.-F. Dai (Marine Biology, 1999)

Integrative activity of cortical neurons in the systems organization of food behavior - Yu. A. Fadeev; V. F. Volkov (Neuroscience and Behavioral Physiology, 1999)

Effects of hydroxystyrene on the expression of the inflammatory cytokine genes and their content in macrophages tolerant to endotoxin - M. I. Dushkin; E. I. Vereshchagin; A. Yu. Grebenshchikov; A. F. Safina; Ya. Sh. Shvarts (Bulletin of Experimental Biology and Medicine, 1999)

Xymedon restores T-cell immune response inhibited by γ-irradiationin vivo: Interrelations with Ca2+-ATPase and DNA-relaxing activities - G. V. Cherepnev; Yu. D. Slabnov; A. P. Tsibul'kin; F. G. Karimova; R. S. Garaev (Bulletin of Experimental Biology and Medicine, 1999)

Synthesis and diversity analysis of lead discovery piperazine-2-carboxamide libraries - Timothy F. Herpin; George C. Morton; Allison K. Dunn; Cedric Fillon; Paul R. Menard; Sheng Yu Tang; Joseph M. Salvino; Richard F. Labaudinière (Molecular Diversity, 1998)

Metal binding to the tetrathiolate motif of desulforedoxin and related polypeptides - Matthew Kennedy; Lian Yu; Maria João Lima; Carla S. Ascenso; Christopher Czaja; Isabel Moura; Jose J. G. Moura; F. Rusnak (JBIC Journal of Biological Inorganic Chemistry, 1998)

Effect of single total irradiation on the reproductive system and vitamin content in rat progeny - V. V. Evdokimov; V. I. Erasova; V. I. Kirpatovskii; V. M. Kodentsova; O. A. Vrzhesinskaya; N. A. Beketova; L. F. Kurilo; T. V. Ostroumova; L. V. Shileiko; I. Yu. Sakharov; I. Yu. Nefedov (Bulletin of Experimental Biology and Medicine, 1998)

Physiological effects of active immunization with triiodothyronine in rats - A. A. Mart'yanov; T. G. Emel'yanova; M. F. Obukhova; N. V. Volkova; M. A. Ryabinina; O. P. Vakulina; I. Yu. Sakharov; I. P. Ashmarin (Bulletin of Experimental Biology and Medicine, 1998)

Pharmacological properties and therapeutic activity of Russian-manufactured pulmonary surfactants - O. A. Rozenberg; L. N. Danilov; V. A. Volchkov; E. S. Lebedeva; V. F. Dubrovskaya; A. A. Val'kovich; O. V. Klestova; Yu. A. Kirillov; A. A. Seiliev; A. A. Shaldzhyan; L. V. Loshakova; A. E. Shul'ga; et al. (Bulletin of Experimental Biology and Medicine, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Is nitric oxide involved in the adaptation to the stress-induced damage? - E. B. Malenyuk; N. P. Aimasheva; E. B. Manukhina; V. D. Mikoyan; L. N. Kubrina; A. F. Vanin; N. P. Larionov; I. Yu. Malyshev (Bulletin of Experimental Biology and Medicine, 1998)

Effect of placental tissue implantation on the morphology and function of rat placenta - A. F. Yakovtsova; V. I. Grishchenko; G. I. Gubina-Vakulik; I. Yu. Kuz'mina (Bulletin of Experimental Biology and Medicine, 1998)

Effect of iodine isotope on the pituitary-thyroid and immune systems of children living on the territories polluted by radionuclides - V. P. Chernyshov; E. V. Vykhovanets; I. I. Slukvin; Yu. A. Antipkin; A. N. Vasyuk; E. F. Klimenko (Bulletin of Experimental Biology and Medicine, 1998)

Activity and inducibility of cytochrome P-450-1A in the liver of mice with different sensitivity to hepatocarcinogenic effect of o-aminoazotoluene - L. F. Gulyaeva; L. Yu. Zakharova; V. V. Lyakhorich; T. S. Morozkova; V. I. Kaledin (Bulletin of Experimental Biology and Medicine, 1998)

Blood flow dynamics in different layers of the somatosensory region of the cerebral cortex on the rat during mechanical stimulation of the vibrissae - Yu. E. Moskalenko; T. A. Woolsey; C. Rovainen; G. B. Weinstein; D. Liu; V. N. Semernya; V. F. Mitrofanov (Neuroscience and Behavioral Physiology, 1998)

Effect of active immunization with plasma aminooxidase on mnestic processes and transmittory systems in rat brain - E. V. Buzinova; E. L. Dovedova; M. Yu. Monakov; T. A. Moskvitina; M. F. Obukhova; Zh. E. Slesareva; I. P. Ashmarin (Bulletin of Experimental Biology and Medicine, 1998)

The TSI-VS-01-D pediatric cystoscope - S. Yu. D'yakonov; E. V. Ezhova; A. B. Karasev; I. M. Lizin; I. A. Lobinskaya; V. F. Matyukhin; A. I. Molev (Biomedical Engineering, 1998)

Effect of pyrimidine derivatives on adenylate cyclase system of immunocompetent cell regulationin vitro - Yu. D. Slabnov; G. V. Cherepnev; F. G. Karimova; R. S. Garaev (Bulletin of Experimental Biology and Medicine, 1998)

Effects of μ-, δ-, and κ-opioid agonists and enkephalinase inhibitor RB101 in two inbred rat strains - S. K. Sudakov; Yu. V. Lyupina; O. F. Medvedeva; I. V. Tyurina; R. Maldonado (Bulletin of Experimental Biology and Medicine, 1998)

Role of inherent and individual acquired factors in the development of morphine sensitivity in WAG/G and Fischer-344 rats - Yu. V. Lyupina; O. F. Medvedeva; I. V. Tyurina; S. K. Sudakov (Bulletin of Experimental Biology and Medicine, 1998)

UBE3A "mutations" in two unrelated and phenotypically different Angelman syndrome patients - David C. Y. Fung; Bing Yu; K. F. Cheong; Arabella Smith; R. J. Trent (Human Genetics, 1998)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)

Donor of nitric oxide improves, while NO-synthase inhibitor impairs resistance and adaptation to strenous physical exercise - N. P. Aimasheva; E. B. Manukhina; M. G. Pshennikova; A. F. Vanin; I. Yu. Malyshev (Bulletin of Experimental Biology and Medicine, 1998)

Regeneration of nerve fibers by laser irradiation of spinal nerve projections - K. I. Saitkulov; G. F. Shaimardanova; Yu. A. Chelyshev (Bulletin of Experimental Biology and Medicine, 1998)

Hypotensive effect and tissue distribution of the dinitrosyl iron complexes, a nitric oxide donor - E. B. Manukhina; I. Yu. Malyshev; E. B. Malenyuk; T. A. Zenina; D. A. Podkidyshev; V. D. Mikoyan; L. N. Kubrina; A. F. Vanin (Bulletin of Experimental Biology and Medicine, 1998)

Possible involvement of nitric oxide in the pathogenesis of experimental convulsions of various genesis - V. G. Bashkatova; G. Yu. Vitskova; V. B. Narkevich; V. D. Mikoyan; A. F. Vanin; K. S. Raevskii (Bulletin of Experimental Biology and Medicine, 1998)

Long-term cardiac protective effect of nitric oxide - I. Yu. Malyshev; E. B. Malenyuk; E. B. Manukhina; V. D. Mikoyan; A. F. Vanin (Bulletin of Experimental Biology and Medicine, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Features of motor cortex neuron responses to specific stimulation in old rabbits - Yu. S. Mednikova; F. V. Kopytova; T. N. Dish (Neuroscience and Behavioral Physiology, 1997)

Interaction between obesity and genetic polymorphisms in the apolipoprotein CIII gene and lipoprotein lipase gene on the risk of hypertriglyceridemia in Chinese - Y.-L. Ko; Yu-Shien Ko; Shy-Meeng Wu; Ming-Sheng Teng; F.-R. Chen; Tsu-Shiu Hsu; Chen-Wen Chiang; Ying-Shiung Lee (Human Genetics, 1997)

Phospholipid composition of liver mitochondria in experimental hemorrhagic shock - G. F. Leskova; Yu. V. Arkhipenko (Bulletin of Experimental Biology and Medicine, 1997)

Benzamide and its derivatives are active against botulinal intoxication - G. A. Ugryumova; I. I. Krasil'nikov; O. F. Alferova; I. D. Vinogradova; Yu. V. Vertiev (Bulletin of Experimental Biology and Medicine, 1997)

Bridges and multipolar mitoses in populations of rat PA-23 rhabdomyosarcoma cells - V. Yu. Kravtsov; S. N. Proshin; A. F. Yakovlev; E. V. Kaminskaya; Yu. B. Vakhtin (Bulletin of Experimental Biology and Medicine, 1997)

Pathophysiological effects of psychoemotional stress and cyclophosphamide - F. I. Ingel'; D. A. Bodyagin; E. R. Pereverzeva; Yu. A. Revazova (Bulletin of Experimental Biology and Medicine, 1997)

A natural "Benchmark" for Ecosystem Function - Yrjö Haila; Patrick J. Comer; Malcolm Hunter; Michael J. Samways; Clive Hambler; Martin R. Speight; Paul Hendricks; Stephen Herrero; F. Stephen Dobson; Andrew T. Smith; Jinping Yu (Conservation Biology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Benthic macrofauna of the mangrove swamp treated with municipal wastewater - Ri-Qing Yu; G. Z. Chen; Y. S. Wong; N. F. Y. Tam; C. Y. Lan (Hydrobiologia, 1997)

Nickel chloride inhibits the DNA repair of UV-treated but not methyl methanesulfonate-treated chinese hamster ovary cells - S. F. Lee-Chen; M. C. Wang; C. T. Yu; D. R. Wu; K. Y. Jan (Biological Trace Element Research, 1993)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Properties of rabies virus (MNIIVP-74 strain) adapted to Japanese quail embryo cell culture - M. S. Bektemirova; D. F. Osidze; E. R. Pille; L. V. Nadaichik; K. Sh. Matevosyan; F. G. Nagieva; N. N. Bogomolova; Yu. S. Boriskin; N. N. Yanova (Archives of Virology, 1979)

Regulation of aquatic diptera by planaria - Hyo-sok Yu; E. F. Legner (BioControl, 1976)

Mass release effects ofchlorohydra viridissima [Coelenterata] on field populations ofAedes nigromaculis andCulex tarsalis in Kern County, California - Hyo-Sok Yu; E. F. Legner; R. D. Sjogren (BioControl, 1974)

Batken virus, a new arbovirus isolated from ticks and mosquitoes in Kirghiz S.S.R. - D. K. Lvov; F. R. Karas; Yu. M. Tsyrkin; S. G. Vargina; E. M. Timofeev; N. Z. Osipova; O. V. Veselovskaya; Yu. I. Grebenyuk; V. L. Gromashevski; K. B. Fomina (Archives of Virology, 1974)

?Sokuluk? virus, a new group B arbovirus isolated from Vespertilio pipistrellus Schreber, 1775, bat in the Kirghiz S.S.R. - D. K. Lvov; Yu. M. Tsyrkin; F. R. Karas; E. M. Timopheev; V. L. Gromashevski; O. V. Veselovskaya; N. Z. Osipova; K. B. Fomina; Yu. I. Grebenyuk (Archives of Virology, 1973)

?Issyk-Kul? virus, a new arbovirus isolated from bats and argas (Carios) vespertilionis (Latr., 1802) in the Kirghiz S.S.R. - D. K. Lvov; F. R. Karas; E. M. Timofeev; Yu. M. Tsyrkin; S. G. Vargina; O. V. Veselovskaya; N. Z. Osipova; Yu. I. Grebenyuk; V. L. Gromashevski; S. N. Steblyanko; K. B. Fomina (Archives of Virology, 1973)